Les racines du hip hop au Québec - Cooke, Marylin (Télé-Québec, 2024)

La « femme·eux·ze » musique québécoise : La recherche sur les genres, les sexualités et autres pratiques non dominantes en musique au Québec (1874-2022) - Blais-Tremblay, Vanessa (Centre de recherche interuniversitaire sur la littérature et la culture au Québec [CRILCQ], 2023)
C’est là un ouvrage de référence qui présente la recherche sur la musique, les genres et les sexualités, et plus largement la vie musicale non dominante au Québec depuis le dernier quart du XIXe siècle jusqu’à aujourd’hui. Issu des travaux réalisés en 202-2022 par le pôle universitaire DIG! Différences et inégalités de genre dans la musique au Québec (D!G), un réseau interdisciplinaire et intersectoriel qui réunit les chercheur·ses, publics, artistes et autres professionnel·les de la musique qui s’intéressent à cette thématique, l’ouvrage comprend une revue de la littérature et une bibliographie de plus de 800 ressources scientifiques.

Les femmes dans l’industrie musicale canadienne francophone - Bissonnette, Joëlle (Fondation Musicaction, 2022)

Au-delà des "vagues" #moiaussi : Cinq ans de mobilisation féministe en musique au Québec (2017-2022) - Blais-Tremblay, Vanessa; Champagne, Lysandre (Intersections: Canadian Journal of Music / Intersections : revue canadienne de musique, 2022)

Closing the Gap: Impact & Representation of Indigenous, Black, and People of Colour Live Music Workers in Canada - Canadian Live Music Association (Canadian Live Music Association, 2022)

Jumol-Julia Edéry’s Wedding in Early 20th Century Morocco - Cohen, Judith R. (Canadian Jewish Studies/Études juives canadiennes, 2022)

Journeys of Attachments, Trajectories of (Mis)fitting: Musicking in Deaf Communities in Montreal - Grenier, Line; Leduc, Véro (Troubling Inheritances: Memory, Music, and Aging, 2022)
This book provides an interdisciplinary focus on music, memory, and ageing by examining how they intersect outside of a formal therapeutic context or framework and by offering a counter-narrative to age as decline. It contributes to the development of qualitative research methodologies by utilizing and reflecting on methods for studying music, memory, and ageing across diverse and interconnected contexts. Using the notion of inheritance to trouble its core themes of music, memory, ageing, and methodology, it examines different ways in which the concept of inheritance is understood but also how it commonly refers to the practice of passing on, and the connections this establishes across time and space. It confronts the ageist discourses that associate popular music predominantly with youth and that focus narrowly, and almost exclusively, on music's therapeutic function for older adults. By presenting research which examines various intersections of music and ageing outside of a therapeutic context or framework, the book brings a much-needed intervention.

Alanis Obomsawin: Lifework - Hill, Richard William; Peleg, Hila; Haus der Kulturen der Welt (Prestel Publishing, 2022)
"One of today's most important documentary filmmakers, Alanis Obomsawin has dedicated her life's work to shining a light on the injustices experienced by Canada's Indigenous people. This retrospective monograph features an extensive interview with Obomsawin and includes stills and reflections on her entire career including her most recent series devoted to the rights of Indigenous children. Never shying away from controversy, Obomsawin's films have played a critical role in exposing ongoing systemic bias towards Indigenous populations-from fishing rights and education to health care and treaty violations. Obomsawin is also a graphic artist, and she incorporates her often dream-inspired etchings and prints into many of her films. This volume includes illuminating essays exploring Obomsawin's practice and mission as well as personal commentary from collaborators, archival materials, and photographs from the filmmaker's personal life and professional exploits. As Obomsawin closes in on her ninth decade of life-and fifth decade behind the camera-this beautifully illustrated record of her astounding body of work and tireless efforts on behalf of Indigenous peoples and culture is an inspiring celebration of the power of film to dramatically change the course of history"– Provided by publisher.

Une médiation de la musique au masculin ? Analyse des dispositifs numériques de médiation de la musique produits par les institutions musicales - Kirchberg, Irina (Digital Studies/Le champ numérique, 2022)
Dans le sillage de l’ouvrage dirigé par Octobre et Patureau (Octobre et Patureau 2018), cet article engage à une réflexion sur le traitement de la question du genre dans les dispositifs numériques de médiation produits par des organismes de diffusion et de production musicale. Les études en sociologie du travail artistique (Coulangeon et Ravet 2003 ; Buscatto 2007 ; Bousquet et al. 2018) ne cessent de montrer que l’ensemble des mondes de la musique, aussi bien classiques que jazz ou pop, est traversé par une double ségrégation genrée horizontale (répartition sexuée selon le type d’emploi) et verticale (moindre accès aux postes à responsabilités). On pourrait imaginer que les producteurs de dispositifs numériques de médiation de la musique, portant des valeurs de vivre-ensemble, d’inclusion sociale et d’agentivité (Perez-Roux et Montandon 2014 ; Carrel 2017), et conscients des effets normatifs et prescriptif des supports éducationnels (Octobre 2014), viennent questionner ces frontières. Le « dénombrement » et l’analyse de « cas » tirés du dépouillement systématique d’une centaine dispositifs numériques consultables en ligne et produits par des organismes de production et de diffusion musicale permettront de montrer que tel n’est pas le cas.

De- and Reterritorializing Identities: The Global Hip Hop Nation at Work in a Youth Hip Hop Recording Studio - Laniel-Tremblay, Édouard; Low, Bronwen (Critical Approaches Toward a Cosmopolitan Education, 2022)
This essay builds on previous studies of the “translanguaging” practices of members of the Montreal Hip Hop community (Low & Sarkar, 2014; Sarkar & Low, 2012) to explore how the challenge to linguistic norms in Quebec is also a challenge to social and identity norms. Our analysis is based on interviews with young musicians attending a community recording studio program in Montreal, the studio’s social media presence, and a track created in collaboration with youth in Paris. Through their relationships in the studio as well as their music, the youth de- and reterritorialize their identities (Papastergiadis, 2000), mobilizing local and global Hip Hop cultural references and communities in ways that challenge dominant narratives of belonging in Quebec and Canada.

"[N]ou rasanble" : rassemblements hétérolingues et hétérogènes dans les chansons de Muzion - Leclerc, Catherine (Analyses, 2022)
Muzion a été parmi les tout premiers groupes de rap québécois à faire résonner une parole locale distinctive. Il le faisait dans un français mâtiné d’anglais et de créole haïtien, multipliant les registres et faisant des emprunts à encore d’autres langues. Cet article se penche sur les chansons du premier album du groupe, Mentalité moune morne, à partir de son hétérolinguisme et des questions d’appartenance que celui-ci soulève. Il examine la manière dont Muzion entrelace les langues, mais aussi les interpellations, défaisant l’association entre langue et identité. Le groupe s’adresse ainsi à la fois à une communauté immigrante locale (d’abord haïtienne, mais également pluriethnique et racisée) qu’il québécise, et à une communauté québécoise élargie qu’il pluralise. Le rap permet en outre à ses membres de faire entendre leurs voix individuelles distinctes, notamment grâce à des usages différenciés de la palette plurilingue du groupe. Ce faisant, ce sont les notions même d’appartenance et de communauté que Muzion se trouve à refaçonner, à l’encontre de toute forme d’homogénéisation, de figement ou de stéréotype.

Parcours professionnels de musiciennes migrantes : de la théorie à l'expérience. Note de terrain à propos du colloque Femmes musiciennes du monde tenu les 26 et 27 novembre 2021 au Centre des musiciens du monde - Marcoux-Gendron, Caroline; Champagne, Lysandre (La Revue musicale OICRM, 2022)

“Before I made fims, I was singing” - Obomsawin, Alanis; Gagnon, Monika Kin (Alanis Obomsawin: Lifework, 2022)

Les rappeuses québécoises sur le devant de la scène : autorité lyrique de la voix féminine chez Donzelle et MCM - Simard, Mathieu; Kirouac Massicotte, Isabelle (Analyses, 2022)

Stories I Might Regret Telling You: A Memoir - Wainwright, Martha (Hachette Books, 2022)
The singer-songwriter's heartfelt memoir about growing up in a bohemian musical family and her experiences with love, loss, motherhood, divorce, the music industry, and more. Born into music royalty, the daughter of folk legends Kate McGarrigle and Loudon Wainwright III and sister to the highly-acclaimed and genre-defying singer Rufus Wainwright, Martha grew up in a world filled with such incomparable folk legends as Leonard Cohen; Suzzy Roche, Anna McGarrigle, Richard and Linda Thompson, Pete Townshend, Donald Fegan, and Emmylou Harris. It was within this loud, boisterous, carny, musical milieu that Martha came of age, struggling to find her voice until she exploded on the scene with her 2005 debut critically acclaimed album, Martha Wainwright, containing the blistering hit, 'Bloody Mother F*cking Asshole,' which the Sunday Times called one of the best songs of that year. Her successful debut album and the ones that followed such as Come Home to Mama, I Know You're Married But I've Got Feelings Too, and Goodnight City came to define Martha's searing songwriting style and established her as a powerful voice to be reckoned with. In her memoir, Stories I Might Regret Telling You, Martha digs into the deep recesses of herself with the same emotional honesty that has come to define her music. She describes her tumultuous public-facing journey from awkward, earnest, and ultimately rebellious daughter, through her intense competition and ultimate alliance with her brother, Rufus, to the indescribable loss of their mother, Kate, and then, finally, discovering her voice as an artist. With candor and grace, Martha writes of becoming a mother herself and making peace with her past struggles with Kate and her former self, finally understanding and facing the challenge of being a female artist and a mother. Ultimately, Stories I Might Regret Telling You offers readers a thoughtful and deeply personal look into the extraordinary life of one of the most talented singer-songwriters in music today.

L’avenir. Les changements que les personnes répondantes souhaitent voir concernant le harcèlement sexuel en milieu de travail dans les domaines des arts de la scène, du cinéma et de la télévision - Aftermetoo (2021)
Keywords: Pas de lien web

L’état des choses. Le harcèlement sexuel en milieu de travail dans les domaines des arts de la scène, du cinéma et de la télévision - Aftermetoo (2021)
Keywords: Pas de lien web

Le suivi. Dénonciation, soutien et qui cause le préjudice? Concernant le harcèlement sexuel en milieu de travail dans les domaines des arts de la scène, du cinéma et de la télévision. - Aftermetoo (2021)
Keywords: Pas de lien web

Les dommages. Les répercussions sur les personnes survivantes du harcèlement sexuel en milieu de travail dans les domaines des arts de la scène, du cinéma et de la télévision - Aftermetoo (2021)
Keywords: Pas de lien web

Principaux constats. Résultats de la toute première enquête sur le harcèlement sexuel en milieu de travail dans les domaines des arts de la scène, du cinéma et de la télévision - Aftermetoo (2021)
Keywords: Pas de lien web

Sur le terrain. La parole aux personnes survivantes. Suggestions écrites concernant le harcèlement sexuel en milieu de travail dans les domaines des arts de la scène, du cinéma et de la télévision - Aftermetoo (2021)
Keywords: Pas de lien web

Naviguer les attentes genrées de la communauté de danse swing de Montréal - Batty, Megan (Les Cahiers de la Société québécoise de recherche en musique, 2021)

Gender and Extreme Metal: Understanding Gender Relations in the Montreal Extreme Metal Scene With Schippers' Gender Framework - Beauchamp, Caroline (Université Concordia, 2021)
Extreme metal is a masculine space, yet more and more women join in. They face a contradiction: as women, they are expected to adopt feminine behaviours; however, they are part of a subculture that valorizes warrior masculinity. I sought to understand the gender expectations of the Montreal extreme metal scene and interpret the contradictions encountered by women in this scene with the help of Schippers’ (2007) theoretical framework on gender. To do so, I conducted 16 individual interviews with women and men who take part in the scene. This research fills a gap in the literature on gender that derives from Connell and Schippers’ writings and addresses issues that the field of metal studies has brushed over. I found that metal men are the “default” participants in the scene. They are expected to be fine music connoisseurs and even become musicians. In contrast, women’s presence is heterosexualized and attributed to a romantic or sexual interest in metal men. Women are suspected of being “poseuses” or groupies with no real interest in the music until proven otherwise. To become legitimate participants, they have to overcome those expectations and prove that they are worthy of being viewed through the prism of masculinity rather than femininity. They do so by proving their exceptionality through manhood acts and distancing themselves from other women. Despite their gender transgressions, women’s presence does not fundamentally question gender relations but reaffirms the overall primacy of masculinity over femininity.

Myriam Boucher + Followup - Boucher, Myriam (Taking the Temperature: Crisis, Curating, and Musical Diversity, 2021)
The caesura in musical production caused by recent global lockdowns has made contemporary music’s crisis of societal relevancy more apparent than ever. Bringing together interviews with music curators, musicians, activist networks and institutional leaders, this book details existing practices and approaches, showing that change is possible but only if the recent wave of interest in curatorial practices, diversity and divestment from a white, European bourgeois aesthetic are taken seriously by the musical establishment. This expanded second edition of Taking the Temperature adds a new preface, five new interviews, as well as followups with previous interviewees. Radiating out from the Ultima Festival and Oslo, ..

Les îles (2011) d’Isabelle Panneton et l’héritage de Philippe Boesmans : généalogie d’une démarche compositionnelle - Brasset, Marie-Pierre (Circuit : musiques contemporaines, 2021)
Dans les années 1980, après ses études auprès de Gilles Tremblay, Isabelle Panneton fait la rencontre de Philippe Boesmans lors d’un passage du compositeur belge à Montréal. Impressionnée par sa musique, elle se rendra en Belgique pour y suivre des leçons de composition avec lui de 1984 à 1987. Cette période sera déterminante pour la compositrice, ouvrant toute grande la porte à l’émergence de sa personnalité musicale. Ce texte retrace les moments forts du passage d’Isabelle Panneton chez le compositeur belge et met en lumière les liens qui les unissent, en guise de prélude à l’analyse de son trio Les îles pour violon, violoncelle et piano.
Publisher: Circuit, musiques contemporaines
Keywords: Belgique; Belgium; Isabelle Panneton; Philippe Boesmans; chamber music; développement motivique; motivic development; musique de chambre

Do We Really Want to Keep the Gate Threshold That High? - Brooks, Grace; Pras, Amandine; Elafros, Athena; Lockett, Monica (Journal of the Audio Engineering Society, 2021)
Drawing upon the survey instruments of Lewis and Neville [1], Nadal [2], and Yang and Carroll [3], we conducted an online survey that captured experiences of discrimination and microaggressions reported by 387 recording engineers, producers, and studio assistants living in 46 different countries. Our statistical analyses reveal highly significant and systemic gender inequalities within the field, e.g., cisgender women experience many more sexually inappropriate comments (p < e-14, large effect size) and unwanted comments about their physical appearance (p < e-12, large effect size) than cisgender men, and they are much more likely to face challenges to their authority (p < e-13, large effect size) and expertise (p < e-10, large effect size). A comparison of our results with a study about women’s experiences of microaggressions within STEM academia [3] indicates that the recording studio workplace scores 33% worse on the silencing and marginalization of women, 33% worse on gender-related workplace microaggressions, and 24% worse on sexual objectification. These findings call for serious reflection on the part of the community to progress from awareness to collective action that will unlock the control room for women and other historically and systemically marginalized groups of studio professionals.

Prendre soin des paroles effacées - Brunette, Edith (Liberté. Art et politique., 2021)

Lise Vachon and “Octobre au mois de mai”: Relistening to the Québécois Revolution - Cancel-Bigay, Mario R. (Sounds that Fall Through the Cracks, and Other Silences and Acts of Love: Decoloniality and Anticolonialism in Puerto Rican Nueva Canción and Chanson Québécoise [thèse de doctorat, Université Columbia], 2021)

Listening to Québec’s 1960s and 1970s with Rouè Doudou Boicel - Cancel-Bigay, Mario R. (Sounds that Fall Through the Cracks, and Other Silences and Acts of Love: Decoloniality and Anticolonialism in Puerto Rican Nueva Canción and Chanson Québécoise [thèse de doctorat, Université Columbia], 2021)

Marie-Claire Séguin: Feminism and Settler Colonialism in “Mater Maria” - Cancel-Bigay, Mario R. (Sounds that Fall Through the Cracks, and Other Silences and Acts of Love: Decoloniality and Anticolonialism in Puerto Rican Nueva Canción and Chanson Québécoise [thèse de doctorat, Université Columbia], 2021)

De l’expression d’un désir gay et du queer dans l’opéra contemporain : le cas d’Elia (2004) de Silvio Palmieri - Champagne, Éric (Circuit: Musiques contemporaines, 2021)

Introduction. Parole queer et musiques contemporaines : vivre et créer hors de la norme - Champagne, Éric; Rhéaume, Martine (Circuit: Musiques contemporaines, 2021)

"If you see me walking alone on the road": Sephardic Songs of Exile, Expulsion, Memory – and Return - Cohen, Judith R. (Armenian and Jewish Experience between Expulsion and Destruction, 2021)

Entretien avec Blxck Cxsper - Danjé, Michaëla (Afrotrans. Perspectives, entretiens, poésie, fiction, 2021)
"Dans cet ouvrage collectif, la parole est donnée exclusivement à des personnes trans noires, vivant en France pour la grande majorité. Ce recueil coordonné par Michaëla Danjé, femme trans membre et co-fondatrice de Cases Rebelles, contient des essais, de la fiction, de la poésie, des interviews, etc. Ce livre est constitué d'une multiplicité de voix, de perspectives et d'expériences diverses. Différentes générations sont également représentées. AfroTrans est beau, complexe, riche de lumière, d'amour et de force! "–Goodreads.com

Gabriel Dharmoo + Followup - Dharmoo, Gabriel (Taking the Temperature: Crisis, Curating, and Musical Diversity, 2021)

Queer Perspectives in New Music - Dharmoo, Gabriel; Brosin, Annette; R. Green, Anthony; Nickel, Luke; Doolittle, Emily; Henry, Symon; Kasahara 笠原 貞野, Teiya (Circuit: Musiques contemporaines, 2021)

David Denada - Farnsworth, Brandon (Taking the Temperature: Crisis, Curating, and Musical Diversity, 2021)

Barbara Scales - Farnsworth, Brandon; Massera, Vanessa (Taking the Temperature: Crisis, Curating, and Musical Diversity, 2021)

Étude patrimoniale sur le katajjaniq - Gadoua, Marie-Pierre (Publications Nunavik, 2021)
Ce livre présente une résumé exhaustif de l’étude effectuée sur le katajjaniq, suite à la désignation de cette pratique à titre de premier élément du patrimoine immatériel québécois.

Rita Baga et Les Reines de Noël explorent le Québec en tournée - Guèvremont, Jean-François (Canadian Theatre Review, 2021)
Une troupe de théâtre musical en tournée, ce n’est pas une première. Une troupe de théâtre musical, composée majoritairement de drag queens, jouant un texte original écrit par l’une d’elles et soutenue par un groupe de musique et des danseurs, ça, c’est une première !
Publisher: University of Toronto Press
Keywords: Montréal; Québec; drag; musical; noël; spectacle; tournée

Interroger l'expérience d'un chœur féministe : le cas du Chœur Maha - Harrison-Boisvert, Catherine (Les Cahiers de la Société québécoise de recherche en musique, 2021)

Altérité et création : comment peut-on s'épanouir artistiquement dans la différence, au-delà des discours sur la diversité ? - Henry, Symon (Les Cahiers de la Société québécoise de recherche en musique, 2021)
Comment le fait d’être métis égypto-québécois·e influe-t-il sur ma manière de composer, d’écrire, de dessiner ? Et le fait d’être queer, neurodivergent·e, pauvre, ou encore d’avoir souffert de troubles de santé mentale ? Autrement formulé : comment, à partir d’une posture intersectionnelle, peut-on s’inscrire dans un cadre artistique donné et communiquer nos codes à un public qui ne les possède majoritairement pas ? Comment parler de ma voix propre, particulièrement minoritaire, afin d’éviter que d’autres s’approprient ma réalité ? Voilà les questions principales qui sont abordés dans cet article où je présente mon travail où partitions graphiques, poésie et arts visuels ont constitué le socle de ma démarche artistique au fil de plus d’une décennie de création. Pour y répondre, j’aborderai certains concepts-clés (intersectionnalité, tiers-espace, etc.) centraux dans ma réflexion, deux projets qui adressent de front ces questions et réalités, et, surtout, de nombreuses digressions proposant des bribes d’imaginaires les sous-tendant. Les projets abordés sont d’abord mon premier opéra, Le Désert mauve, d’après un texte éponyme de Nicole Brossard — chef-d’oeuvre des littératures lesbiennes, queers et québécoises. Puis le spectacle L’Outre-rêve et plus spécifiquement ma pièce L’amour des oiseaux moches, commande de l’Ensemble contemporain de Montréal (ECM+), où mes mots, ma musique et mes visuels donnent vie à quatre personnages imbus de réalisme magique (Djinn, Louve, Vieux Clown et Eunuque que j’aime) par l’entremise de pièces pour voix, scie musicale, accordéon et orchestre.

Black Women Dancers, Jazz Culture, and “Show Biz”: Recentering Afro-Culture and Reclaiming Dancing Black Bodies in Montréal, 1920s–1950s - Jabouin, Emilie (Canadian Journal of History, 2021)
The documentary Show Girls, directed by Meilan Lam, makes an unprecedented contribution to the history of jazz and Black women jazz dancers in Montréal, Quebec, and to the conversation of jazz in Canada. Show Girls offers a glimpse into the lives of three Black women dancers of the 1920s–1950s. This essay asks what the lives of Black women dancers were like and how they navigated their career paths in terms of social and economic opportunities and barriers. I seek to better understand three points: (1) the gap in the study of jazz that generally excludes and/or separates dance and singing from the music; (2) the use of dance as a way to commercialize, sell, and give visual and conceptual meaning to jazz; (3) the importance of the Black body and the role of what I would define as “Afro- culture” in producing the ingenious and creative genre of jazz. My study suggests there is a dominant narrative of jazz, at least in academic literature, that celebrates one dimension of jazz as it was advertised in show business, and that bringing in additional components of jazz provides a counternarrative, but also a restorative, whole and more authentic story of jazz and its origins. More specifically, by re- exploring jazz as a whole culture that relies on music, song, and dance, this essay explores three major ideas. First, Black women dancers played a significant role in the success of jazz shows. Second, they articulated stories of self, freedom, and the identity of the New Negro through jazz culture and dance. Third, Black women’s bodies and art were later crystallized into images that further served to sell jazz as a product of show business.

Dick Montgomery et la personnification féminine afrodescendante en Amérique du Nord, 1935-1960 - Jacques, Raphaël (Histoire Engagée, 2021)

Terri Hron (Canadian New Music Network) - Jakobsson, Anna (Taking the Temperature: Crisis, Curating, and Musical Diversity, 2021)

Black Gold: A Black Feminist Art History of 1920s Montréal - Joachim, Joana (Canadian Journal of History, 2021)
The 1920s have been touted as the golden era of jazz and Black history in Montréal. Similarly, the decade is well known for the Harlem Renaissance, a key moment in African American art history. Yet this period in Black Canadian art histories remains largely unknown. As a first step toward shedding some light on this period in Black Canadian art history, I propose to use what I term a Black feminist art-historical (bfah) praxis to discuss some visual art practices undoubtedly active alongside well-known jazz musicians and cultural producers in 1920s Montréal. This paper presents an overview of critical race art history and feminist art history, as well as Black feminist approaches to visual representation, to outline what might be considered four tenets of bfah praxis. Applying these tenets, I propose that a new art history may emerge from well-known art objects and practices as well as lesser-known ones. I posit that through a deliberately bfah approach, new meanings emerge and the voices of Black women, even when obstructed by mainstream white narratives, may begin to stand out and shed light upon a variety of histories. This praxis aims to underline the subtext lurking at the edges of these images and to make intangible presences visible in the archive and in art history. I propose bfah as a strategy for more nuanced discussion of the work of Black Canadian artists and histories that have by and large been left out of official records.
Publisher: University of Toronto Press

Nueva vida : Mener la danse avec un trouble de santé mentale - K, Florence (2021)
« Un trouble de santé mentale impose souvent le travail d'une vie, soit un profond apprentissage de soi, de sa maladie et de la maîtrise de celle-ci. Pour arriver un jour à valser avec son état et à mener la danse. » Nueva vida, c'est le récit d'un cheminement vers une nouvelle vie. C'est la preuve que, comme les chats, on peut retomber sur ses pattes neuf fois, sinon plus. Après la parution de Buena vida, alors que tout devrait bien aller, Florence K sent encore le trou noir qui la guette. Puis un psychiatre pose enfin un diagnostic sur le précipice au bord duquel elle marche depuis plusieurs années : celui de la bipolarité de type II. À partir de ce moment, avec un suivi et un traitement adapté, elle a pu atteindre un équilibre durable. Dans ce récit touchant, elle se livre avec transparence, pour briser les tabous et la solitude, plaider pour un meilleur accès aux soins et apporter de l'espoir à tous ceux qui connaissent les aléas vertigineux d'un trouble de santé mentale.

Énonciation, sexualités et genre en musique chez Philémon Cimon, Pierre Lapointe et Ariane Moffatt - Konaté, Khady (Les Cahiers de la Société québécoise de recherche en musique, 2021)
Dans ce texte est proposée une « lecture du genre » (Boisclair 2002) des oeuvres de Philémon Cimon (L’été, Les femmes comme des montagnes), Pierre Lapointe (Pierre Lapointe, Sentiments humains) et Ariane Moffatt (Aquanaute, Le coeur dans la tête, Tous les sens). L’étude des chansons contenues sur ces albums prend pour point de départ une interrogation des subjectivités genrées de ces trois artistes, entre personne réelle et persona, et montre que ces dernières façonnent leurs compositions. La sollicitation du concept de sexe/genre ouvre dès lors la porte à l’exploration des représentations des identités sexuelles et de genre dans ces chansons, où les identités des artistes se trouvent mises en abîme. En s’intéressant à l’énonciation et au discours (en particulier, au discours amoureux) contenu dans le texte des chansons sélectionnées, il est possible de rendre compte de la reproduction des injonctions à l’hétérosexualité et des poncifs qui cloisonnent le genre, ainsi que des glissements et brouillages qui autorisent des resignifications du genre. Ainsi, chez Cimon, on observe la reconduite du point de vue masculin où la valeur du féminin réside dans sa capacité à émerveiller le sujet et à susciter son désir. À l’opposé, les textes de Lapointe et Moffatt dépeignent des personnages et des récits queer, bien que leur identité queer n’ait pas été revendiquée à l’heure de la parution de leurs oeuvres.

Une chanteuse épanouie : Renée Claude (1939-2020) - Laberge, Yves (Cap-aux-Diamants : la revue d'histoire du Québec, 2021)
Un article de la revue Cap-aux-Diamants, diffusée par la plateforme Érudit.
Publisher: Les Éditions Cap-aux-Diamants inc.

Étude sur la création du sentiment d'appartenance de jeunes Montréalais·e·s racialié·e·s membres de la communauté d'un studio d'enregistrement Hip Hop - Laniel-Tremblay, Édouard (Université McGill, 2021)
Cette recherche examine comment des pratiques artistiques influencées par la culture Hip Hop se déroulant dans un studio d’enregistrement communautaire participent au développement personnel et social de jeunes Montréalais·e·s racialisé·e·s. Il est soutenu qu’en incarnant des principes et valeurs associées au Hip Hop, le studio canalise et stimule un cadre permettant aux jeunes l’exploration de leurs identités multiples et marginalisées ce qui s’accompagne d’une part, d’une prise de conscience et d’émancipation en mobilisant des éléments de la culture Hip Hop pour stimuler une croissance personnelle reposant sur la liberté créatrice. D’une autre part, cette communauté ouvre la porte à la création du sentiment d’appartenance pour les jeunes Montréalais·e·s racialisé·e·s reposant sur la constitution de fondations et réseaux alternatifs au sein de la communauté du studio, de la scène locale et mondiale du Hip Hop. Ce faisant, le studio engendre l’émergence de solidarités affinitaires lui conférant un rôle de carrefour et de point d’ancrage pour cette communauté.

Nos mains qui vibrent – Un texte à huit mains sur une recherche-création en musiques sourdes - Leduc, Véro; Saunders, Daz; Youssouf, Hodan; Witcher, Pamela (Canadian Journal of Disability Studies, 2021)
“Deaf music?” Faced with this question, many people think about the attempts to give Deaf people "access" to music, used here in its normative hearing form (eg a musical soundtrack). Translation of vocal songs in various sign languages, transformation of sound tracks into vibratory experience, musical rhythms broadcast by visual speakers... accessibility initiatives are numerous, but more often than not unidirectional: they aim to make hearing music accessible to Deaf people, reputed to live in a "world of silence". Our vibrant hands aim to deconstruct this concept of accessibility: what if hearing people had access to signed music? You can’t sign? Enjoy these creation by letting yourself be captivated by the vibrations. Inspired by the Deaf artist Christine Sun Kim who reclaims sound, Our vibrant hands is a research-creation carried out thanks to the collaboration of four Quebec Deaf artists of various origins. Four workshops held in 2018 allowed us to explore signed music, using (Quebec and American) sign languages, gestures and vibrations. Screened for the first time at the VIBE symposium: Challenging ableism and audism through the arts, it is here the subject of an eight- handed reflexion, produced in 2019. What attachment do we have with music? How is signed music different from hearing music? What does it mean for us to deconstruct audism in music? These are the questions that guided this multilingual exchange in Quebec sign language, French and English.
Number: 2

Chronologie de plus de cent ans de présence féminine dans la création d'œuvres musicales au Québec : un premier survol - Lefebvre, Marie-Thérèse (Les Cahiers de la Société québécoise de recherche en musique, 2021)

Lynda Lemay. Il était une fois mes chansons - Lemay, Lynda; Vignol, Baptiste (Éditions Gründ, 2021)

Genre, rap et enjeux de la visibilité dans l'espace public des rappeuses à Montréal : de la gestion de l'apparence physique pour être reconnue en tant qu'artiste - Lesacher, Claire (Les Cahiers de la Société québécoise de recherche en musique, 2021)

Socialisation musicale et sociabilités urbaines. Parcours de personnes immigrantes originaires d'Afrique du Nord à Montréal - Marcoux-Gendron, Caroline (L'interculturel contemporain au carrefour des disciplines, 2021)

Socialisation musicale, frontières culturelles et sociabilités urbaines. Les parcours des personnes immigrantes d'origine maghrébine à Montréal - Marcoux-Gendron, Caroline (Institut national de la recherche scientifique, 2021)

Avant-propos. Björk, Montréal et le Nunavut - McKinley, Maxime (Circuit : musiques contemporaines, 2021)
An article from Circuit, on Érudit.
Publisher: Circuit, musiques contemporaines

Avant-propos. Position d’écoute - McKinley, Maxime (Circuit: Musiques contemporaines, 2021)
Keywords: Inclure l'avant-propos ?

Mary Travers Bolduc ou Madame Édouard Bolduc, pionnière de la chanson populaire au Québec - Melançon, Johanne (Les Cahiers de la Société québécoise de recherche en musique, 2021)
Longtemps dénigrée par une certaine élite et plus ou moins ignorée des ouvrages sur la chanson, Mary Travers Bolduc (1894-1941) est aujourd’hui considérée comme étant la première autrice-compositrice-interprète, ainsi que la toute première vedette de la chanson populaire québécoise. À une époque où les femmes bénéficient de peu ou pas d’autonomie, sa carrière semble à la fois une anomalie et un exploit. Cependant, l’image de la femme indépendante qui gère sa carrière et organise ses tournées apparaît en contradiction avec les chansons où elle reste fidèle aux valeurs traditionnelles de sa génération et de son public quant au rôle de la femme dans la société. Réécouter les chansons de Mme Bolduc et parcourir les archives permettent de mieux comprendre qui était celle que l’on surnommait « La Bolduc », — à la fois femme, épouse et mère, ainsi qu’artiste autodidacte et « reine de la chanson comique », à mi-chemin entre le folklore et la chanson populaire —, et aident à la compréhension de ce pourquoi sa réception critique a été aussi longtemps mitigée. On peut également mieux mesurer la valeur de son oeuvre en lien avec la société dans laquelle elle a évolué, ainsi qu’émettre le constat que la condescendance de certains à son égard au cours de sa carrière, tout comme le silence qui a suivi son décès, relèvent de préjugés ; non pas parce qu’elle était une femme, mais à cause de la classe sociale à laquelle elle appartenait et dont elle a été le miroir. Ce n’était pas tant le propos de ses chansons qui dérangeait mais bien son niveau langue, le ton parfois grivois et le style de sa musique, ce qui a pourtant garanti son succès auprès des spectateurs. Sa réhabilitation au cours des années 1960, dans le contexte d’une revalorisation du folklore et de l’âge d’or de la chanson joualisante, s’explique par l’évolution de l’horizon d’attente et du goût du public.

Dream visions: The Art of Alanis Obomsawin - Obomsawin, Alanis (Perceval Press, 2021)

The Double Bind That Is Not a Bond: Cohen and Women - Pally, Marcia (From This Broken Hill I Sing to You: God, Sex, and Politics in the Work of Leonard Cohen, 2021)
Leonard Cohen's troubled relationship with God is here mapped onto his troubled relationships with sex and politics. Analysing Covenantal theology and its place in Cohen's work, this book is the first to trace a consistent theology across sixty years of Cohen's writing, drawing on his Jewish heritage and its expression in his lyrics and poems.Cohen's commitment to covenant, and his anger at this God who made us so prone to failing it, undergird the faith, frustration, and sardonic taunting of Cohen's work. Both his faith and ire are traced through: · Cohen's unorthodox use of Jewish and Christian imagery · His writings about women, politics, and the Holocaust · His final theology, You Want It Darker, released three weeks before his death.
Keywords: Music / General; Religion / Judaism / Theology; Religion / Theology

« Je ne m’apitoie plus sur le fait » : homosexualité et engagement identitaire dans les écrits et prises de parole de Claude Vivier - Rhéaume, Martine (Circuit: Musiques contemporaines, 2021)

Alys Robi a été formidable. Nouveau regard sur une figure d'avant-garde - Ringuet, Chantal (Québec Amérique, 2021)
Flamboyante et indépendante, Alys Robi a marqué le Québec en étant sa première star internationale puis en voyant sa carrière s’interrompre brutalement, à vingt-cinq ans à peine, lorsqu’elle est internée contre son gré. Mais au-delà de ces deux grands axes à partir desquels on la raconte toujours, qui était-elle ? Pourquoi a-t-elle été internée ? Pourquoi, surtout, a-t-on oublié à quel point elle a été formidable ?Chantal Ringuet a plongé dans les archives de cette femme qui était sa grand-tante afin d’en brosser enfin un portrait exhaustif et de réhabiliter la mémoire d’une artiste exceptionnelle. Dans cette émouvante biographie qui flirte avec l’essai littéraire, elle nous entraîne dans l’envers du décor, sur les traces de cette diva qui a été tour à tour reine de la chanson, féministe avant l’heure, traductrice littéraire, porte-parole pour la santé mentale, incarnation du kitsch et égérie de la communauté gaie. Une femme qui, malgré les épreuves inouïes qu’elle a affrontées, a poursuivi son chemin la tête haute.

Les femmes et la chanson au Québec : quels cadrages ? pour quelles histoires ? - Savoie, Chantal (Les Cahiers de la Société québécoise de recherche en musique, 2021)

Black Minstrelsy on Canadian Stages: Nostalgia for Plantation Slavery in the Nineteenth and Twentieth Centuries - Thompson, Cheryl (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2021)
Le blackface minstrelsy, qui a vu le jour dans le nord-est des États-Unis dans les années 1820 et 1830, mettait en scène des artistes blancs, principalement des hommes, qui franchissaient les frontières raciales en imitant des Afro-Américains avec la musique, l’humour et la danse prétendument « authentiques », courants dans les plantations du sud. Dans les années 1860, les Afro-Américains nouvellement émancipés se produisaient également sur scène en blackface. À la fin du XIXe siècle, cependant, les acteurs noirs ne se grimaient plus en noir, mais ils devaient toujours perpétuer les stéréotypes de la plantation. Ces troupes étaient dirigées par des directeurs noirs et blancs qui présentaient leurs spectacles comme « authentiques » et « nostalgiques ». Ces éléments du spectacle de minstrel noir — surtout ses représentations soi-disant « réelles » du Sud des États-Unis et de l’esclavage dans les plantations — ont trouvé un écho auprès du public canadien. Ils constituent donc une autre perspective d’approche — en dehors des politiques d’immigration et Jim Crow de facto — pour expliquer la présence du racisme et de la xénophobie anti-Noirs au Canada à la fin du XIXe siècle et au début du XXe siècle. En examinant le contenu de la minstrelsy noire, le rôle joué par les directeurs dans ses productions et la promotion dans les journaux, cet article soulève des questions sur l’étendue à laquelle les Canadiens ont été historiquement complices du dénigrement des Noirs.
Publisher: The Canadian Historical Association / La Société historique du Canada

Black Media Reporting on Theater, Dance, and Jazz Clubs in Canada: From Shuffle along to Rockhead’s Paradise - Thompson, Cheryl; Jabouin, Emilie (Journal of Communication Inquiry, 2021)
Canada has a history of de facto Jim Crow (1911–1954). It also has a historical Black press that is intimately connected to Black America through transnational conversations, and diasporic migration. This article argues that Canada’s Black newspapers played a pivotal role in promoting Black performance during a time when they were scarcely covered in the dominant media. Drawing on news coverage from the 1920s through 1950s of black dance, musicals, and jazz clubs this article examines three case studies: Shuffle Along (1921–1924), the first all- Black Broadway musical to appear at Toronto’s Royal Alexandra Theater, Alberta-born dancer Len Gibson (1926–2008), who revolutionized modern dance in Canada in the 1940s and 1950s, and the Montreal jazz club Rockhead’s Paradise (1928–1980), a pivotal site in the city’s Little Burgundy, a Black neighborhood that thrived in the 1930s through 1950s. The authors argue that when Black people were excluded from and/or derogatorily portrayed in the dominant media, Canada’s Black press celebrated collective achievement by authenticating Black performance. By incorporating Canada’s Black Press into conversations about Jim Crow and performance, we gain a deeper understanding of Black creative output and resistance during the period.
Publisher: SAGE Publications Inc

Situer les femmes dans l'Electronic dance music culture (EDMC) à Montréal, entre 1950 et 1955 : premier survol - Van Vliet, Kiersten (Les Cahiers de la Société québécoise de recherche en musique, 2021)

Quadruple défi pour les artistes femmes, immigrantes et allophones : Le cas du premier Sarau das Minas Montréal - Vasconcellos de Carvalho, Dalila (Les Cahiers de la Société québécoise de recherche en musique, 2021)

When it Comes to Race and Feminism, How Do Quebec Media Institutions Always Fail Us? - Vertus, Aïsha C (Never Apart, 2021)

Fracturing Patriarchal Objectivity through Electro-Pop: Purity Ring and the vicissitudes of sight - Watkinson, Philip (Performance Research, 2021)
This article examines the deviated modes of seeing in the work of Canadian electro-pop band Purity Ring. Bringing their recent music into conversation with the theory of Tim Ingold and Eugenie Brinkema, I suggest that Megan James and Corin Roddick perform seeing as a granular, augmented act that continually shapes the boundaries between our bodies and the world around us. Particular attention is paid to James and Roddick’s creative engagement with optical touch and the formal capability of music to engage affectively with the act of seeing.By integrating musical examples, Tallulah Fontaine’s artwork for the band and the poetry of Kiran Millwood Hargrave, this article offers an expanded reading experience that spans the textual, the aural and the visual. I argue that the political crux of Purity Ring’s performance of perception lies in them moving beyond a reactionary response to patriarchal objectivity and towards a creative refiguration of perception as a form of subjectivation. The eyes that Purity Ring instantiate do not passively observe the world; they change it, both consoled and engulfed by the vicissitudes of perception.

« Changer le monde un hit à la fois » ? Programmation et diversité à CKOI-FM - Watson, Jada (Les Cahiers de la Société québécoise de recherche en musique, 2021)
En mars 2019, Stéphanie Vallet a publié un article dans La Presse portant sur la sous-représentativité des artistes féminines dans le palmarès Billboard « Canadian Hot 100 ». Les résultats de son étude démontrent une forte décroissance de la présence des femmes dans l’industrie musicale canadienne — un écosystème dans lequel les ondes radio continuent de jouer un rôle important quant à la découvrabilité et à la professionalisation des artistes. Cependant, au-delà des questions de genre abordées par Vallet, les enjeux liés à la représentativité des artistes issu·es de la diversité ethnoculturelle et linguistique à la radio doivent également être soulevés. Les théories de « social remembering » (Misztal 2003 ; Strong 2011) offrent un cadre critique pour se pencher sur les « Big Data » compilées par des industries où les femmes et les artistes racisé·es semblent systématiquement désavantagé·es. Dans le but d’entamer le portrait de la représentativité sur les ondes de la radio commerciale au Québec, cet article aborde la représentativité des artistes minorisé·es sur les ondes de CKOI-FM (96.9) de Montréal. CKOI-FM a été choisie non seulement parce qu’il s’agit d’une station francophone « top 40 » (diffusant tous les genres musicaux), mais aussi parce qu’entre 2015 et 2017 elle utilisait le slogan « Changeons le monde un hit à la fois » (Girard 2017) — un message à fortes résonances avec les slogans militants visant la justice sociale. Ce projet offre donc l’occasion d’investiguer la validité des déclarations faites par une radio qui se vante de « changer le monde ». En adoptant une approche féministe intersectionnelle à l’analyse des données appelée « data feminism » (d’après D’Ignazio et Klein 2020), cette étude évaluera les différents taux de représentativité à CKOI-FM parmi les 100 chansons les plus jouées chaque année entre 2010 et 2020 afin de considérer le rôle que jouent les ondes radio dans la formation de la culture musicale populaire au Québec et, par extension, de la mémoire sociale.

La SQRM 1980-2005 : Une première approche historique - Bail, Louise (Les Cahiers de la Société québécoise de recherche en musique, 2020)
En 2005, l’ARMuQ/SQRM fêtait son 25 e anniversaire d’existence. Répondant aux questions de la rédactrice en chef des présents Cahiers , Sylvia L’Écuyer, l’auteure expose d’abord les motifs qui ont poussé les membres fondateurs à créer ce qui s’appelait alors l’Association pour l’avancement de la recherche en musique du Québec (ARMuQ). Cette section est suivie d’un aperçu des différentes phases de l’évolution de l’association. Enfin, dans une troisième section intitulée « Problématiques et souhaits d’avenir », Louise Bail tente de dégager très brièvement les liens que l’ARMuQ/SQRM a développés avec les institutions d’enseignement supérieur et de circonscrire la place que prennent les chercheurs indépendants au sein de l’organisme. Son propos s’emploie à faire ressortir les problèmes particuliers que posent le fonctionnement et l’existence d’une telle association. Enfin, elle propose des réflexions et suggère quelques pistes d’avenir à partir de son implication en tant que membre fondateur, membre régulier et présidente sortante du conseil d’administration. , In 2005, the ARMuQ/SQRM celebrated its twenty-fifth anniversary. Responding to questions from the Cahier’s current Editor-in-Chief, Sylvia L’Écuyer, the author begins by discussing the motives that gave rise to the Association pour l’avancement de la recherche en musique du Québec, as it was then called. This is followed by a survey of the association’s various transformations over the years. In a third section entitled “Problématiques et souhaits d’avenir” (“Challenges and wishes for the future”), Louise Bail describes the ties that bind the ARMuQ/SQRM to post-secondary education institutions, and identifies the role of independent scholars within the organisation. The aim of her study is to discern the particular challenges that the existence and operations of such an association create. Finally, she reflects and advises on the association’s future from the perspective of her own role as founding member, regular member, and past Chair of the Board of Directors.

Recourir à la musique pour favoriser le bien-être et l’intégration des personnes réfugiées à Québec - Arsenault, Stéphanie; Moreno Sala, Maria (Nouvelles pratiques sociales, 2020)
Cet article porte sur une intervention musicale et interculturelle de groupe qui visait l’amélioration du bien-être psychologique et l’intégration des personnes réfugiées dans la ville de Québec. L’expérience a regroupé 20 personnes, dont 10 Québécois de longue date et 10 personnes réfugiées nouvellement arrivées, qui se sont réunies à 10 occasions pour échanger et jouer de la musique ensemble. Les propos recueillis avant, pendant et après la démarche démontrent que l’activité a contribué à l’amélioration du sentiment de bien-être des réfugiés, mais aussi d’une majorité des Québécois de longue date. Les propos montrent que la démarche a aussi contribué à l’intégration des réfugiés.
Publisher: Université du Québec à Montréal
Keywords: Quebec; Québec; integration; intervention sociale; intégration; music; musique; refugee; réfugié; social intervention

Sounding the Arctic in Chantal Bilodeau’s Climate Change Plays - Balestrini, Nassim W. (Nordic Theatre Studies, 2020)
Quebec-born playwright Chantal Bilodeau has been responding to the challenges of dramatizing anthropogenic climate change by developing an eight-part Arctic Cycle, each play of which is set in one of the nations that claims Arctic territory. Sila (2014) immerses audiences into a complex network of humans, animals, and mythical beings crisscrossing the Canadian Arctic. These movements circle around the Inuit concept of sila, which is the life-giving force of breath and voice. Thus, the sonic world of Sila focuses on voices speaking words, on performance poetry, and on the sounds of breath and wind. Bilodeau’ s second Arctic Cycle play, Forward (2016), addresses the long-term impact of Fridtjof Nansen’s polar exploration of the 1890s on Norway’s economy and society. In terms of sound, Forward features multiple musical performances rangingfrom traditional songs to European opera arias and Lieder to contemporary Norwegian electro-pop. The sonic features of both plays stress interdependence across time, space, as well as (non-)human, earthly, and metaphysical realms. Sila and Forward address climate change in a non-universalizing manner which promotes a heterarchical (rather than hierarchical) aesthetic fit for a growing awareness of planetary relationality.
Keywords: Theory and practice

Gender and Embodiment in the Contemporary Montreal Swing Dance Community - Batty, Megan (Université McGill, 2020)
"This thesis explores embodiment and gender within the contemporary Montreal swing dance community. Drawing on scholarship in musicology, dance studies, jazz studies, and gender studies, I investigate the relationship between dancers and musicians/DJs. I explore the many facets of this choreomusical conversation and trace this dialogic and collaborative relationship on the social dance floor. The contemporary community is a product of the swing revival and navigating issues of authenticity thus becomes an important consideration for dancers, musicians, and DJs alike. One product of this revival is the set of heteronormative values that underpin the contemporary community. I investigate to what extent these values are reified, challenged, or altogether subverted by participants through musical and choreomusical choices. To this end I conducted interviews with six informants, each of whom has experience as both a dancer and musician and/or DJ. Their privileged position arising from their dual experience affords them insight on the ways in which dancers and musicians/DJs function within the community. This thesis builds on existing scholarship by situating the voices of individuals with choreomusical experience in dialogue with existing scholarship, and ultimately revalues the importance of both embodied knowledge and gender within the swing community"– Author's abstract

Louise Campbell. Une médiatrice dans l’être - Bertomeu, Fanny (Revue musicale OICRM, 2020)
Formed as a musician and a clarinetist, Louise Campbell is now a music mediator. Based in Montreal, she practices her profession through several structures and for a wide variety of audiences (schoolchildren, professionals, people with disabilities ...) all around Canada, but mainly in Quebec. In this interview, Louise Campbell recounts her experience as a mediator, her (non)-formation in this profession, as well as many aspects in her practice. With the musical object and the creation at the heart of her workshops, Louise Campbell always seeks to establish a “horizontal” exchange relationship with each person she meets.
Publisher: Observatoire interdisciplinaire de création et recherche en musique (OICRM)
Keywords: Louise Campbell; creation; création; music mediation; médiation de la musique; partage; relation; relationship; sharing

“Maple Leaf Rag” in Maple Leaf Country: Impressing Jazz upon Vera Guilaroff - Blais-Tremblay, Vanessa (Women and Music: A Journal of Gender and Culture, 2020)
Publisher: University of Nebraska Press

Pauline Julien, intime et politique (2018) - Carlos, Jean-Philippe (Bulletin d'histoire politique, 2020)

Bïa Krieger versionista: Três cançoes de Chico Buarque em francês [Bïa Krieger, versionista. Trois chansons de Chico Buarque en français] - Cassiano, Raissa Conde (Université de São Paulo, 2020)

TAGS de Joane Hétu et TanGRAM de Danielle Palardy Roger : signatures plurielles et figure continue - Dall’Ara-Majek, Ana (Circuit : musiques contemporaines, 2020)
TAGS by Joane Hétu and TanGRAM by Danielle Palardy Roger are two written works that showcase graphic scores in improvised music. TAGS creates an encounter between Ensemble SuperMusique, the saxophone quartet Quasar, and the Bozzini Quartet. The musicians make “sound graffiti” on an imaginary wall represented by a sequence of timed sections on a descriptive score where the composer uses different instrumental combinations. Using an aesthetic of articulated gestures, the work is made through these multiple signatures. TanGRAM brings together twenty instrumentalists from Ensemble SuperMusique. The game of Tangram is represented in the form of a graphic score where each piece has specific musical properties to be interpreted by the musicians. Rich in combinatorial and symmetrical games, the work presents Orion: a continuous figure, a slowly moving flow where each musician seeks their own way in a global sound.
Publisher: Circuit, musiques contemporaines
Keywords: Analyse musicale; Danielle Palardy Roger; Joane Hétu; Musical analysis; graphic score; improvised music; musique improvisée; partition graphique

Visions multigénérationnelles de l’art sonore à Montréal - Dall'Ara-Majek, Ana (Circuit, 2020)
Partant d’une caractéristique de l’environnement artistique à Montréal - le décloisonnement des esthétiques et des formes d’expressions -, cette enquête compile les propos de six créateurs et artistes sonores de trois générations distinctes qui ont vécu ce contexte : Monique Jean et Jean-François Laporte (génération 1960), Patrick Saint-Denis et Cléo Palacio-Quintin (génération 1970), Adam Basanta et Émilie Payeur (génération 1980). Chacun se prononce sur quatre thématiques principales : la définition de leur pratique artistique, leurs réflexions sur la pluridisciplinarité ou la polyvalence, la perception de l’environnement artistique entre leurs débuts et aujourd’hui, et leur rapport à l’enseignement institutionnel versus l’apprentissage en autodidacte. Les réponses mettent en lumière la diversité des perceptions alimentant la diversité des pratiques, les sensibilités du contexte propres à chaque génération, ainsi que des visions personnelles de la ville quant à ses institutions et activités artistiques.

Blondie B, rappeuse des premières heures au Québec - Desfossés, Félix B. (Les racines du hip-hop au Québec. Tome 1, 2020)

Wavy Wanda et Baby Blue, pionnières du rap à Montréal - Desfossés, Félix B. (Les racines du hip-hop au Québec. Tome 1, 2020)

Mouffe. Au cœur du showbiz - Dumas, Carmel; Monfette, Claudine (Éditions La Presse, 2020)
La parolière d’Ordinaire et du Mur du son, c’est elle. La muse du jeune Charlebois, c’est encore elle. La metteure en scène de spectacles mythiques (Magie rose, J’ai vu le loup, le renard, le lion) et d’innombrables galas, c’est toujours elle. « Elle », c’est Mouffe, figure légendaire du Québec en marche, née Claudine Monfette, alouette ! Diplômée de l’École nationale de théâtre, interprète de chansons en duo et de rôles d’ingénue, éternelle tête chercheuse, semeuse de bonnes idées et mentore de la relève, elle a contribué à faire de notre milieu artistique ce qu’il est. Journaux personnels de Mouffe, entrevues avec celle-ci mais aussi avec sa famille, ses amis, ses collègues : Carmel Dumas a remonté pendant plus de dix ans le fil de cette vie palpitante et trace ici le portrait d’une femme omniprésente et effacée, fantaisiste et sage. Une vieille âme enveloppée de candeur, extraordinaire survivante.
Keywords: Biography & Autobiography / Artists; Architects; Photographers

Sacred Song Sisters: Choral and Solo Vocal Church Music by Women Composers for the Lenten Revised Common Lectionary - Elliott, Lisa A. (Université du Nevada, 2020)
This document explores sacred music by women composers for the Revised Common Lectionary (RCL) of the Catholic and Christian churches. The study researches exclusively choral and vocal solo music by women composers for the church season of Lent. Other primary limitations include music in English, and music from the nineteenth century to the present. The main question answered in this document is: what sacred music has been published by women composers that may be programmed in church services? This question is answered in the included appendices. These appendices list the music by women composers appropriate for the specific RCL readings for each Sunday of Lent, as well as the holidays of Ash Wednesday, Maundy Thursday, and Good Friday. There are also appendices of choral and solo vocal pieces that are generally appropriate for the Lenten season. Every attempt was made to be as thorough as possible in identifying this music, with the understanding that no one compilation of this kind can ever be complete. Additionally, selected works by six composers are explored in this document: Emma Lou Diemer (b. 1927), Arletta O’Hearn (b. ca 1928), Jane M. Marshall (1924 – 2019), Rebecca Clarke (1886 – 1979), Violet Archer (1913 – 2000), and Undine Smith Moore (1904 – 1989). These composers are representative of the variety of styles, diversity, history, and levels of musical complexity within this body of music.
ISBN: 9798662554733
Keywords: Choir; Christ; Female; Service; Sing; Worship

Renée Claude. Donne-moi le temps - Girard, Mario (Éditions La Presse, 2020)
À l’aube des années 1960, Renée Claude fait ses débuts de chanteuse en interprétant Ferré, Béart et Brassens, mais aussi, et surtout, les siens (Ferland, Léveillée, Vigneault, DesRochers, Lelièvre). Sa rencontre avec l’auteur-compositeur Stéphane Venne, puis son association avec le parolier Luc Plamondon marqueront un point tournant dans sa carrière. Pendant plus d’une décennie, Renée Claude enchaînera les succès. « C’est notre fête aujourd’hui », « Le début d’un temps d’un nouveau », « Le tour de la terre », « Viens faire un tour », « Tu trouveras la paix », « Un gars comme toi », « Ce soir je fais l’amour avec toi » ... Au début des années 1980, alors que d’autres chanteuses de sa génération rendent les armes, Renée Claude connaît une incroyable renaissance avec un cycle d’hommages à Clémence DesRochers, Georges Brassens et Léo Ferré. Offerts aux quatre coins du monde pendant plus de 30 ans, ces spectacles confirmeront son grand talent d’interprète. Grâce à des dizaines d’entretiens, le journaliste Mario Girard retrace le fascinant parcours de plus de 50 ans de cette artiste incomparable. À travers son histoire, il raconte aussi celle du Québec qui a émergé de la Grande Noirceur pour se tailler une identité à sa mesure. Et on peut affirmer que Renée Claude y a largement contribué.
Keywords: Biography & Autobiography / Entertainment & Performing Arts; Biography & Autobiography / General; Biography & Autobiography / Music

Identités de position queer dans la musique populaire au Québec - Girard, Stéphane (QuébeQueer. Le queer dans les productions littéraires, artistiques et médiatiques québécoises, 2020)
En plus d’offrir un portrait des productions culturelles queer au Québec tant francophones qu’anglophones, dont certaines autochtones, cet ouvrage s’attarde à révéler le caractère queer de celles qui ne le sont pas de facto. Il se présente comme un manuel de référence sur le sujet, avec des essais critiques – qui portent autant sur la littérature et le monde du spectacle que sur les arts médiatiques ou la presse gay – et des textes expérimentaux – fictions, dessins, récits autobiographiques. Plus de 27 œuvres de fiction publiées entre 1965 et 2017 y sont analysées sous différents aspects, avec des méthodologies diverses, mais toujours sous l’éclairage queer (un terme à la nature instable, paradoxale, que calque la forme éclatée de l’ouvrage). Du polyamour à l’inceste, en passant par le racisme, l’urbanité, le suicide, le non-désir d’enfant, l’alimentation ou les processus de production, le queer met en scène des personnages hétéros ou homosexuels, intersexués, cis, trans, travailleur·euse·s du sexe, gros et plusieurs autres… Cette juxtaposition d’états, de genres, de thèmes, de formes et de pratiques constitue l’une des forces de ce livre qui intéressera bien sûr un lectorat d’intellectuel·le·s et de personnes issues des communautés LGBTQIA2S+, mais pas seulement. Il deviendra, sans nul doute, une ressource indispensable pour l’enseignement de nouvelles perspectives dans le cadre des sciences humaines et sociales.

Resoundingly Entangled: Ageing and Memory in Étoile des aînés in Quebec - Grenier, Line; Sawchuk, Kim; Valois-Nadeau, Fannie (A Senior Moment: Cultural Mediations of Memory and Ageing, 2020)

College Boy (2013) de Xavier Dolan : pérenniser “le backward feeling” - Hakeem, Hasheem (Contemporary French Civilization, 2020)
En 2013, Xavier Dolan, cinéaste, acteur et metteur en scène québécois prolifique, réalise le vidéoclip College Boy, chanson du groupe de musique français Indochine qui s’articule autour d’un jeune garçon queer qui est victime d’homophobie dans un internat. Cet article propose une analyse de ce vidéoclip en se focalisant sur la mise en scène de la violence et des affects négatifs. Nous étudions d’abord le débat provoqué par la diffusion et la censure du clip en France. Ensuite, à partir de la théorie du “backward feeling” développée par Heather Love dans Feeling Backward: Loss and the Politics of Queer History (2007), nous analysons la manière dont la représentation de la violence dans l’œuvre de Dolan remet en question l’ordre hétéronormatif. Nous défendons la thèse qu’en s’attaquant de front aux institutions qui sont les véritables agents de la violence homophobe, College Boy contribue à la conservation archivistique de l’expérience queer et crée ainsi une possibilité d’émancipation face à l’hétéronormativité.

Jocelyne Binet's Cycle de Mélodies: Unearthing a Forgotten Song Cycle - Hoch, Matthew (Journal of Singing, 2020)
Montreal composer Jocelyne Binet's "Cycle de Melodies sur des Poemes de Paul Eluard" was programmed in 1955 by the French baritone Gerard Souzay in a performance that was most likely the world premiere. Unfortunately, Binet's song cycle never was published, and the work soon was forgotten. In the fall of 2016, the author discovered Bineet's original handwritten manuscript pages in holdings of Bibliotheque et Archives Nationales du Quebec and began the process of reconstructing the score. This article discusses the editorial journal undertaken when resurrecting Binet's forgotten song cycle, which was subsequently published in 2018 by Classical Vocal Reprints.
Keywords: Archives & records; Education; French language; Manuscripts; Music; Musical performances; Online data bases; Piano; Spelling; Vocal music

(Re)Presenting Indigenous Activism in the Nation's Capital: Signifying Resistance across Time and Place through Music in Alanis Obomsawin's Trick or Treaty? (2014) - Hoefnagels, Anna (Contemporary Musical Expressions in Canada, 2020)

Music, Geography and the Greatest Rewards: A Geohistorical Analysis on the Prestigious Awards of Céline Dion - Iconic Artist - Jucu, Ioan-Sebastian (Review of Historical Geography and Toponomastics, 2020)
In the present academic research connecting geography and music,a real gap remains in the study of different issues associated with both music and geography and, particularly, to the recent music geographies. This paper advances a new geographical approach in music geography highlighting the relevance of time and space in music, in the artist‟s outstanding contribution to music and in their recognition from the local to the global. Particularly the study is focused on one of the most emblematic music artists of the world, analyzing through a spatio-temporal investigation the prestigious awards achieved by the singer Celine Dion, since this singer remains both a real music legend and an iconic artist gaining multiple awards and thoroughly appreciated and admired for her outstanding contribution to music and global popular culture. The research bases on such specific methods as internet research, visual methodologies, bibliographical analysis and geographic information systems (GIS). The latter is used to provide a professional map illustrating the spatio-temporal distribution of the multiple awards received by Dion the artist. The findings of the research highlight the highest scale of appreciation an artist can receive. The results of the study also suggest that the outstanding contribution of the greatest artists of the world, acknowledged by the highest national, international and global forums, provide significant information about their artistic involvement in the global popular culture. They have a strong relevance both in space and in time, thus labeling different cultural decades and distinct places and spaces throughout the world.

Chaakapesh - Kingsley, Justin; Frappier, Roger (Fragments Distribution, 2020)
L'Orchestre symphonique de Montréal et son célèbre maestro Kent Nagano partent en tournée dans la grande toundra nordique du Québec pour visiter les communautés cries, innues et inuites, et partager avec eux un opéra de chambre autochtone où l'on apprend à l'homme blanc à rire et, par le fait même, à aimer davantage. Chaakapesh le périple du Fripon - écrit par Tomson Highway, composé par Matthew Ricketts et interprété par l'Orchestre symphonique de Montréal - est l'exemple le plus probant et moderne de collaboration interculturelle.

Death and Fairy Tale: Queer Autothanatography in Claude Vivier - Kingston, Andrew (differences, 2020)

Représentations du féminin et énonciation lyrique dans la chanson québécoise contemporaine : perspectives sur le sexe/genre chez Ariane Moffatt, Pierre Lapointe et Philémon Cimon - Konaté, Khady (Université d'Ottawa, 2020)
Cette thèse se propose de faire une analyse du discours sur les représentations du féminin et les implications du sexe/genre dans la chanson québécoise contemporaine, à travers les œuvres et la persona de trois auteur·ice·s-compositeur·ice·s-interprètes (ACI): Ariane Moffatt, Pierre Lapointe et Philémon Cimon. Notre analyse part d’abord du constat que les chansons de Moffatt, Lapointe et Cimon figurent des sujets lyriques, dont la parole et le geste sont modulés par les enjeux énonciatifs que posent le lyrisme. Pour rendre compte de la spécificité de la chanson comme pratique poétique réunissant paroles, musique et interprétation, nous proposons de faire une étude sémantique des chansons pour chacun·e des ACI, en nous attardant dans un premier temps aux questions soulevées par le lyrisme, puis en faisant la somme des aspects relevant du sexe/genre présents dans leurs univers sonores respectifs avec le renfort de la théorie féministe et des études de genre, d’après une perspective postmoderne. Notre lecture cherche à souligner les reconduites et les poncifs liés au féminin, mais également à saisir les propositions et les configurations qui s’écartent des lieux communs, tant pour les modèles féminins valorisés que pour les modèles amoureux et les rapports sociaux de sexe et de genre suggérés par les chansons. La comparaison entre les chansons des trois artistes permet ainsi de dégager des points de convergence, tout en révélant les particularités de leurs œuvres.

Monique Leyrac : notre grande dame de la chanson québécoise du XXe siècle - Laberge, Yves (Cap-aux-Diamants : la revue d'histoire du Québec, 2020)
Un article de la revue Cap-aux-Diamants, diffusée par la plateforme Érudit.
Publisher: Les Éditions Cap-aux-Diamants inc.

Céline, es-tu queer ? - Leblanc, Thomas (QuébeQueer. Le queer dans les productions littéraires, artistiques et médiatiques québécoises, 2020)
En plus d’offrir un portrait des productions culturelles queer au Québec tant francophones qu’anglophones, dont certaines autochtones, cet ouvrage s’attarde à révéler le caractère queer de celles qui ne le sont pas de facto. Il se présente comme un manuel de référence sur le sujet, avec des essais critiques – qui portent autant sur la littérature et le monde du spectacle que sur les arts médiatiques ou la presse gay – et des textes expérimentaux – fictions, dessins, récits autobiographiques. Plus de 27 œuvres de fiction publiées entre 1965 et 2017 y sont analysées sous différents aspects, avec des méthodologies diverses, mais toujours sous l’éclairage queer (un terme à la nature instable, paradoxale, que calque la forme éclatée de l’ouvrage). Du polyamour à l’inceste, en passant par le racisme, l’urbanité, le suicide, le non-désir d’enfant, l’alimentation ou les processus de production, le queer met en scène des personnages hétéros ou homosexuels, intersexués, cis, trans, travailleur·euse·s du sexe, gros et plusieurs autres… Cette juxtaposition d’états, de genres, de thèmes, de formes et de pratiques constitue l’une des forces de ce livre qui intéressera bien sûr un lectorat d’intellectuel·le·s et de personnes issues des communautés LGBTQIA2S+, mais pas seulement. Il deviendra, sans nul doute, une ressource indispensable pour l’enseignement de nouvelles perspectives dans le cadre des sciences humaines et sociales.

Les pratiques artistiques des personnes sourdes ou handicapées au Canada - Leduc, Véro; et autres (Conseil des arts du Canada, 2020)

Venus On Venus: CKUT’s Women’s Collective Music Show Dishes on Feminist Radio - Leventhal, Anna; McInnis, Catherine; Wilson, Angela (Women in Radio: Unfiltered Voices from Canada, 2020)
Three volunteer hosts and programmers of a feminist music show at a campus-community radio station, Anna Leventhal, Catherine McInnis, and Angela Wilson, sat down in 2008 to chat about feminist radio. They discussed the concept of a feminist music show and the possibilities and limitations of female-only spaces; the “fem-con” concept that campus-community radio stations be mandated to play a certain amount of music by women, in the same way they are mandated by the CRTC to play Canadian content; the transformative social and political potential of community radio; and the inclusion of trans and gender-nonconforming voices on the show.

Ageing with Waves: The Im/material Worlds of Two Quebec Ondists - Madden, David (A Senior Moment: Cultural Mediations of Memory and Ageing, 2020)
Ageing and memory - two aspects of life everybody has to face eventually. The contributions to this volume explore the cultural mediations of these categories. Through a series of approaches focused on practices and acts of memory, narratives, reminiscence, representation and collective memory, they seek to better understand and critically reflect on how ageing is experienced in variegated ways across the lifespan. By covering a variety of phenomena, from biopics, music by the elderly, and artefacts, among other, they all contribute to further the understanding of memory as a cultural process always in the making - situated in particular contexts, and shaped by its material conditions of existence.

Imaginary Women, Imaginary Audience: Gender and Top 40 Radio in Montréal - Maki, Christine (Women in Radio: Unfiltered Voices from Canada, 2020)
Though they no longer call themselves Top 40, popular music radio stations remain present on the dial today, complete with loud, mostly male DJs, hoping to attract a mainly female audi ence. Using the talk on two Montréal music stations, which hire mainly male announcers who select music assumed to fit wom en’s tastes, Christine Maki examines the continuing perception that women’s voices aren’t low or authoritative enough and that emotional issues prevent them from presenting difficult news stories. Her conclusion: the overall medium remains relatively unchanged over the decades, despite massive evolution in the wider media landscape.

Mapping as a Complementary Perspective on the Dynamics of Participation in a City’s Musical Life - Marcoux-Gendron, Caroline; De Alvarenga, Bernardo (Bulletin of Sociological Methodology/Bulletin de Méthodologie Sociologique, 2020)
Maps and map-making have been used in a range of research about musical phenomena in cities. Yet, most of these studies focus on musicians; few have attempted to understand how people take part in a city’s musical life in terms of event attendance. Likewise, little has been said about the attendance habits of immigrants, despite the quick transformation of urban populations due to the expansion of human migration. Approaching a subject that has received so little attention as the dynamics of participation of immigrants in a city’s musical life therefore requires an inventive research design. Building from a methodology combining semi-structured interviews and observation, I used maps and map-making to deepen the analysis of North African immigrants’ cultural practices in Montreal. Trying to give a spatial legibility to their musical activities in the city generated many technical and theoretical concerns, but was also helpful for reflecting on the project differently and highlighting some characteristics of the data that were not obvious from the initial fieldwork. In brief, maps and map-making proved to be efficient complementary tools to ethnography, bringing new insights and raising new queries about the practices being considered.
Keywords: audiences; cartes; cartographie; cities; cultural participation; cultural practices; ethnographie; ethnography; immigration; map-making; maps; music; musique; participation culturelle; pratiques culturelles; publics; villes

Shekhinah in the Music Videos of Leonard Cohen - Měsíc, Jiří (From Page to Screen: Modification and Misrepresentation of Female Characters in Audiovisual Media, 2020)

Tuning a Room: Designs for Hearing According to Nancy Tobin - Rewa, Natalie (Canadian Theatre Review, 2020)
In this review, I discuss the architectonics of sound composition according to sound artist and designer Nancy Tobin. This chapbook advocates for a comprehensively integrated presence of a sound artist in the processes of rehearsal and espouses a dramaturgy of hearing. Tobin’s distinction between hearing and listening gives forth onto a series of self-studies of her experience of spatial and temporal arrangements presented in the form of e-mails to mentees. Her appreciation for the acoustics of the performance space extends to the composition of sound to be heard (on occasion as boldly interventionist) and the technologies of broadcasting it: the choice and placement of speakers, as well as their interaction with the performers. Tobin argues for a definition of sound composition for performance as a complex collaboration with the production—curatorial in terms of the space of ephemerality. My review concurs with the efficacy of her approach by my recognition of the moments in productions that have remained as some of the most memorable of my theatregoing.
Keywords: Nancy Tobin; acoustic space; rehearsal processes; sonic/acoustic dramaturgy; sound artist; speaker specifications and broadcasting sound

Gendered Pirates: Women’s Roles in Temporary Autonomous Radio - van der Zon, Marian (Women in Radio: Unfiltered Voices from Canada, 2020)
Taking over the airwaves in a small neighbourhood in Montréal was the first step in the creation of the Temporary Autonomous Radio, a pirate station open to women and serving its community when needed. From Montréal, founder Marian van der Zon moved TAR to the West Coast, temporarily on the airways in Victoria, Nanaimo, and rural Vancouver Island. Pirate radio under five watts is usually overlooked in Canada. Beyond music festivals, TAR serves to provide information about issues not often covered in mainstream media. Most importantly, it allows women to be themselves and explore their identities through a non-gendered medium

Blue Oil, premier groupe punk féminin au Québec - Desfossés, Félix B. (Ici Radio-Canada, 2019)

Palmarès musicaux: où sont les femmes? - Vallet, Stéphanie (La Presse, 2019)

L'adaptation de chanson dans l'album ”Cœur vagabond” de Bïa. Une brise de Brésil - Abbrugiati, Perle (ATeM – Archiv für Textmusikforschung, 2019)
Perle Abbrugiati's article explores Coeur vagabond/Coraçao vagabundo, the fourth record by the French-Brazilian artist Bïa, released in 2006. The bilingual album comprises an equal number of Brazilian-Portuguese adaptations from French songs and French adaptations from Brazilian songs. The aim of the present article is to identify the strategies applied in the translation of songs. To this end, the article's author herself uses translation within the framework of a comparative approach, confronting Bïa's translations with her own literal translations (not suitable to be sung) of the original lyrics. The objective is not to trace 'mistranslations' but to point out in how many different and intricate ways a translation can be faithful while being creative, and in what way and to what degree the song translator may take the liberty of 're-semantisation'.
Keywords: Chanson; traduction

Hip-Hop et pauvreté : entre résistance culturelle et créativité économique - Atséna Abogo, Marie-Thérèse (Reflets, 2019)
Dans la ville de Québec, la culture hip-hop permet de mettre en lumière les acteurs qui proviennent de milieux défavorisés et de l’immigration. À partir de textes de rap et d’entrevues avec des rappeurs, des entrepreneurs producteurs de hip-hop et leurs proches réalisées dans le cadre d’une recherche ethnographique, j’analyse comment de jeunes immigrants noirs utilisent le hip-hop et l’entrepreneuriat culturel comme une stratégie de contestation et de résistance face à la pauvreté et aux discriminations auxquelles ils sont confrontés. Selon une approche intersectionnelle (Hall,1980a; Crenshaw, 1994; Chauvin et Jaunait, 2015), cette étude met en lumière comment des propriétés originellement marginalisantes (race, lieu de résidence et dispositions sociales) peuvent être converties en des potentiels légitimés.
Publisher: Reflets, Revue d’intervention sociale et communautaire
Keywords: Pauvreté; Poverty; Quebec City; capital; cultural entrepreneurship; entrepreneuriat culturel; groupes sociaux racisés; hip-hop; intersectionality; intersectionnalité; racialized social groups; resistance; résistance; ville de Québec

Une approche sensible du son - Bertin, Raymond (Jeu : revue de théâtre, 2019)
Article sur l'artiste sonore Nancy Tobin.

Gorgeous Girlies in Glittering Gyrations! Capital érotique et danse jazz dans l’entre-deux-guerres québécois - Blais-Tremblay, Vanessa (Recherches féministes, 2019)
Dans la littérature sur la danse exotique de la première moitié du xxe siècle, la danseuse noire apparaît soit comme la victime d’une industrie du divertissement capitalisant sur les mises en scène érotisantes, exotisantes et primitivisantes de son corps, soit comme la parodie subversive du stéréotype dit « primitif-exotique » incarné sur scène. Pour paraphraser bell hooks, le plaisir corporel, voire charnel, lié à la danse est avant tout abordé en tant que réalité à laquelle il faut résister, qui doit être masquée ou transcendée, ce qui force ainsi un processus de distanciation entre le travail artistique de la danseuse et le capital érotique de son corps. Dans cet article, l’auteure s’appuie sur une collection d’entretiens réalisés dans le contexte du travail de recherche ayant mené à la production cinématographique Show Girls: Celebrating Montreal’s Legendary Black Jazz Scene (1999) avec des danseuses qui travaillaient dans l’industrie du spectacle durant l’« âge d’or » du jazz montréalais (1925-1955). Les récits que révèlent ces entretiens permettent d’aller au-delà des questions de représentation dans la littérature sur la danse exotique pour poser un regard sur l’agentivité artistique de ces femmes qui résistent à la désarticulation entre leur travail artistique et le capital érotique de leurs corps.
Publisher: Revue Recherches féministes

“Where You Are Accepted, You Blossom”: Toward Care Ethics in Jazz Historiography - Blais-Tremblay, Vanessa (Jazz & Culture, 2019)
Publisher: University of Illinois Press

“Portrait en Noir et Blanc”: Chico Buarque em francês por Bïa Krieger [“Portrait en Noir et Blanc”: Chico Buarque en français par Bïa Krieger] - Cassiano, Raissa Conde (Tradução em Revista, 2019)

L'improvisation jazz : une pratique fondamentale dans le processus de reconnaissance des musiciennes de Montréal - Champagne, Lysandre (Université du Québec à Montréal, 2019)
À partir des dimensions spatiale, temporelle et musicale, ce mémoire expose les modalités de reconnaissance des improvisatrices de jazz dans les jam-sessions de Montréal. En se référant au concept de Jeu chez Mead, l'autrice montre que l'authentification des musiciennes en situation d'improvisation est le produit de la communication mise en forme par ce type d'interaction. Toutefois, le contexte des jam-sessions montréalais maintient un «entre-soi» masculin défavorable à la reconnaissance des musiciennes comme improvisatrices distinctes dans ce jeu musical. Ainsi, l'improvisation dans ces événements de jazz participe à la reconduction des inégalités de genre.

"Rocking your Nation" : le pow-wow de Kanhesatà:ke et les identités autochtones - Contant-Joannin, Sandrine (Université Laval, 2019)

Jouer les femmes : les concerts de musique contemporaine au Québec - Couture, Ariane (Recherches féministes, 2019)

Festivals de musique québécois : où sont les femmes ? - Croteau, Laurianne (Ici Radio-Canada, 2019)

Sexisme en musique : des trucs pour s’assurer une programmation paritaire et inclusive – Partie 1 - Daguzan Bernier, Myriam (Gazette des femmes, 2019)

Sexisme en musique : des trucs pour s’assurer une programmation paritaire et inclusive – Partie 2 - Daguzan Bernier, Myriam (Gazette des femmes, 2019)
Solutions constructives pour des rendez-vous musicaux plus vivants, diversifiés et… paritaires!

Les multiples résonances du teuehikan (tambour) des Ilnuatsh de Mashteuiatsh dans le renouvellement d’une éthique de l’attention - Delamour, Carole (Revue d'anthropologie des connaissances, 2019)
Cet article propose une réflexion sur la manière dont les actes et savoir-être musicaux, médiatisés par les tambours, peuvent nourrir une éthique relationnelle entre partenaires autochtones et non autochtones, dans un contexte de recherche collaborative. L’article se base sur des recherches menées avec la Première Nation des Ilnuatsh de Mashteuiatsh. L’étude de leurs tambours, appelés teuehikan, a permis d’interroger et d’analyser des principes relatifs au respect, à l’attention et à la réciprocité. À travers ces principes, l’article revient sur les reconfigurations éthiques, méthodologiques et épistémologiques que la relation au teuehikan permet de conceptualiser. Il interroge plus spécifiquement comment la relation que les Ilnuatsh entretiennent avec le teuehikan s’inscrit au sein d’une éthique de l’attention dont les principes sont susceptibles de nourrir nos propres pratiques de recherche.
Bibliographie_available: 1 Cairndomain: www.cairn.info Cite Par_available: 0 Publisher: S.A.C.

Reflets de la colonialité dans la scène des musiques nouvelles - Dharmoo, Gabriel (Intersections: Canadian Journal of Music / Intersections : revue canadienne de musique, 2019)
Certains membres de la scène des musiques nouvelles souhaitent en décentrer ses racines eurocentriques et en critiquer ses tendances colonialistes. Avant même de discuter des stratégies qui pourraient constituer un cadre décolonisateur, il est utile d’identifier comment la colonialité se reflète dans cette scène. L’auteur, lui-même membre actif de celle-ci, partage des pistes de réflexion portant sur l’homogénéité culturelle du milieu, les questions d’accès, l’héritage de la musique classique, le concept de l’excellence européenne, la présomption d’universalité, la coexistence de statuts de légitimité et de marginalité, la relation ambigüe avec l’appropriation culturelle et les fondements de l’attribution du mérite.

Keyboard Fantasies: The Beverly Glenn-Copeland Story - Dixon, Posy (Greenwich Entertainment et Modern Films, 2019)

Monique Leyrac. Le roman d'une vie - Dompierre, François (Éditions La Presse, 2019)

We Appreciate Power: A Multimodal Critical Discourse Analysis of Grimes' Music Video Posted on YouTube - Enguídanos Gómez, Adrià (Université autonome de Barcelone, 2019)
The aim of this dissertation is to produce a multimodal critical discourse analysis of Grimes' video We Appreciate Power. This will serve to explore issues of ideology, identity and multilingualism in both the music video and the YouTube polylogues generated in the same web page. In this work I suggest that Grimes adopts a poststructuralist view that inherits Haraway's cyborg concept (1991) in this piece of multimedia. I claim that Grimes wanted to show the conflictive moral boundaries that the idea of the cyborg and trans-humanism casts upon Western civilization, such as the loss of free will but also the transgression of problematic dichotomies. The fact that the comment section of the video is available to use might signal that Grimes wanted to raise awareness about trans-humanism. By doing virtual ethnography research, examples of discussion about the relationship between the video and the studied polylogues will be examined regarding the notions of the cyborg and multilingualism.

Experiments in Cultural Diplomacy: Music as Mediation in Canadian-Brazilian Relations (1940s-1960s) - Fillion, Eric (Université Concordia, 2019)

Je donnerai de la joie. Entretiens avec Dina Bélanger - Gauthier, Jacques (Éditions Novalis, 2019)
Dina Bélanger (1897-1929) s’est donnée très jeune au Christ, ne voulant que lui plaire dans l’intimité de la prière. À vingt-quatre ans, elle renonce à une brillante carrière de pianiste pour entrer au couvent des Religieuses de Jésus-Marie à Québec. Elle expérimente l’union mystique avec la Trinité par le cœur eucharistique de Jésus. Béatifiée par Jean-Paul II en 1993, elle laisse à l’Église et au monde un héritage spirituel d’une richesse exceptionnelle, qui rappelle celui de Thérèse de l’Enfant-Jésus, qu’elle avait prise pour patronne, avec sainte Cécile. Dans le sillage de ses ouvrages sur Thérèse de Lisieux et Marie-Léonie Paradis, Jacques Gauthier nous offre un autre entretien chaleureux et instructif avec une «?amie de Dieu?» qui avait dit avant de mourir, à trente-deux ans?: «?Je donnerai de la joie.?» Ses questions pertinentes facilitent cet échange intime avec Dina qui, par l’intermédiaire de son autobiographie, témoigne d’une sainteté unique et inspirante.

Why Lhasa de Sela Matters - Goodman, Fred (University of Texas Press, 2019)

Bruit blanc; suivi de Les dispositifs sonores dans la poésie de Marie Uguay et de Joséphine Bacon - Henry, Cassandre (Université de Montréal, 2019)
Ce projet de recherche-création explore les avenues narratives d'une pensée de contrôle du corps par le sonore. Le travail de création réfléchira les mécanismes, les sentiments, les contraintes conscientes ou inconscientes de personnages face à l'environnement sonore urbain. Ces mécanismes, qu'ils soient intériorisés ou non par les personnages, permettront de penser le dispositif sonore, au sens de Foucault puis interprété par Agamben. Le dispositif crée, entre l'être sur lequel il agit et l'ensemble des dits et non-dits qu'il contient, un « processus de subjectivation », ou de « désubjectivation »: il se fait contrôle, s'organise en rapports de force. La partie création met en scène des personnages qui sont habités par des idéaux d'une libération du corps par la musique, que cette libération − ou son échec − soit spatiale, temporelle, sociale ou psychique. Ce travail se consacrera également à une analyse du recueil de Joséphine Bacon Un thé dans la toundra/ Nipishapui nete mushuat (2013) et du recueil L'Outre-vie (1979) de Marie Uguay. Ces autrices créent une dimension sonore et vocale évidente dans leurs poèmes, une sensibilité, voire une sursensibilité à l'ouïe − notamment par le teueikan (tambour) chez Bacon et par les « racines sonores » pour Uguay. Le son devient un vecteur qui permet de penser la subjectivité dans des possibles spatiaux et temporels simultanés que le corps paraît empêcher. R. Murray Schafer nomme « schizophonie » la séparation de la source d'émission du son par sa reproduction, par la multiplication des enregistrements. Ce rapport différé à la musique produite à distance du corps des musiciens − s'il s'agit de musique instrumentale − joue un rôle dans ce réseau de rapports de force, dans ce dispositif qui nous intéresse. Les sources sonores se sont aujourd'hui multipliées et apparaissent, par l'enregistrement, souvent déplacées et séparées de leur contexte de production original. Comment penser ces effets de décontextualisation? Le travail de création s'intéressera aux modalités et aux effets d'une voix énonciative travaillée par ces diverses représentations d'un corps qui entend, récepteur de réalités différées, d'une pensée du corps disséminé. Pour parler non pas seulement d'écoute, mais plutôt de ce que qui l'excède, de ce vers quoi tend l'écriture poétique: possibilité de l'écoute de l'autre, ou de l'écoute de ce qui est autre.

The “Manic Pixie Dream Girl of the Synth-Pop World” and Her “Baby Doll Lisp”: Grimes and the Disabling Logics of the Feminization and Infantilization of Lisping - Holmes, Jessica A. (Journal of Popular Music Studies, 2019)
Audible in speech and song, electro-pop singer Grimes’s so-called “baby doll” lisp generates endless buzz online, ranging from light-hearted adoration, to infantilization, to sexual fetish and even to ableist, misogynist anti-fandom. This article uses the reception of her lisp to build an intersectional theory of lisping across its medical and socio-cultural constructions, bridging work in disability studies, dysfluency studies, voice studies, and popular music studies in the process. I situate the slippage between adoring, infantilizing, fetishistic, and violent characterizations of Grimes’s lisp as reflective of the infantilization of “communicative disorders” in speech language pathology, and the dysfunction associated with feminine coded-speech patterns (e.g. vocal fry and up talk) in the popular imaginary. Lisping is profitably understood as an audible form of “liminal” difference relative to visible physical disabilities (St. Pierre), and to certain ableist, gendered, and racialized conceptions of normative vocality. Ultimately, in the English-speaking world, the lisp is symbolically-coded feminine while exceeding the norms of female vocality, thereby giving rise to a polarizing set of associations that work against female authority and, by extension in Grimes’s case, female musical authorship. Grimes’s reception thus offers a valuable case study for interrogating how misogynist fantasies regarding femininity are thought localized in the female voice, and the symbolic ties between disability and femininity.
Publisher: University of California Press

Musical Geographies and Iconic Music Legends: Mapping Céline Dion's Outstanding Contribution to Music and Global Popular Music Culture - Jucu, Ioan-Sebastian (Territorial Identity and Development, 2019)
Between music geography and iconic music legends, a strong connection has been established in terms of spatial and temporal analysis of popular music and the representation of national identities in the contemporary global cultures of popular music. The existing literature unveils a gap in the analysis of music geography and famous musicians, real global music icons identified with particular cultures. This paper argues that such music legends must be geographically studied to unveil their outstanding contribution to the world music cultures. Against such a background, a geographical approach that takes Canadian singer Céline Dion as a case studyis developed. The research aims to analyse Dion’s outstandingcontribution to global music culture in both spatial and temporal terms. Based on the music industry emergence, the paper focuses on how and why Céline Dion appeared in global music culture and examines her outstanding contribution with specific referenceto music cartographies and statistical research.National identity and related cultural issues beyond the music, lyrics, and performances are also addressed.The empirically led study is based on a multi-method approach and makes use of statistical data analysis, GIS methods, biographicalinquiry, the analysis of lyrics and visual methodologies,all suggesting that Dion’s contribution has greatly influenced the global popular music culture of the last few decades.Although the topics in question cannot be fully discussed within the limits of this paper, it highlights the importance of these issues and calls for further in-depth research to provide a new critical understanding of the intimate connections between popular music, legendary music icons and the recent perspectives in music geographies

Ton métier, le mien, le Québec. Fragments de correspondance amoureuse et politique 1962-1993 - Julien, Pauline; Godin, Gérald (Leméac Éditeur, 2019)
Dix ans après la parution de La renarde et le mal peigné,quatre cents nouvelles lettres échangées entre Gérald Godin (1938-1994) et Pauline Julien (1929-1998) ont été découvertes dans leurs fonds d’archives respectifs. Soixante-dix d’entre elles ont été choisies par Emmanuelle Germain et Jonathan Livernois, dans cette édition qui vient compléter le portrait forgé en 2009. On y retrouvera les débuts de la relation entre le journaliste et la chanteuse, les longues tournées en Europe de Pauline Julien, la maladie de Godin, puis celle, en filigrane, de Julien. De nouveaux aspects apparaîtront également : l’érotisme de plusieurs de leurs échanges ; les rapports d’amitié ; les aléas d’une vie familiale où un jeune homme de vingt-cinq ans doit s’occuper de deux adolescents, alors que Julien doit concilier sa vie professionnelle et sa vie de mère ; l’épuisement des dernières années, tandis que les tournées européennes sont de plus en plus difficiles pour Julien. Les lettres réunies ici permettront également aux lectrices et aux lecteurs de revivre de grands moments de l’histoire québécoise, vue à la hauteur de ses acteurs : le « Vive le Québec libre ! » lancé par Pauline Julien à Niamey, en 1969, interrompant le ministre fédéral Gérard Pelletier ; la crise d’Octobre et l’emprisonnement sur lequel on ne reviendra guère ; la campagne électorale de 1976, l’enthousiasme et la victoire, inattendue ; l’engagement du député puis ministre Gérald Godin. Ce n’est donc pas un hasard si ce petit livre est sous-titré « Fragments de correspondance amoureuse et politique ». La suture des deux univers, de l’intime et du public, de l’amour et du politique, y est plus claire que jamais.

The Women’s Art Society of Montreal and Its Place in History, 1894-2019 - Keays, Cathy (Autoédition, 2019)

La mélancolie dans la chanson québécoise contemporaine : Tu m'intimides de Mara Tremblay, La forêt des mal-aimés de Pierre Lapointe, À Paradis City de Jean Leloup - Laliberté St-Pierre, Audrey (Université Laval, 2019)
La chanson québécoise actuelle paraît réconcilier la chanson dite «à texte» et la chanson populaire, comme ce fut le cas pour la chanson engagée des années 1970. Si le thème de l’engagement soutenait plusieurs œuvres chansonnières de cette décennie, celui de la mélancolie semble pouvoir définir une certaine tendance actuelle. Ce mémoire s’intéresse au thème de la mélancolie dans la chanson québécoise contemporaine et plus précisément dans les albums Tu m’intimides de Mara Tremblay, La forêt des mal-aimés de Pierre Lapointe et À Paradis City de Jean Leloup. À la fois auteurs, compositeurs et interprètes, ces trois artistes s’inscrivent dans le champ populaire de la chanson québécoise en créant des œuvres où le texte et la musique mettent la mélancolie en valeur. Dans cette étude, la mélancolie est étudiée en fonction de trois aspects, soit l’être mélancolique, la temporalité mélancolique et l’espace mélancolique. C’est à travers l’exploration de ces trois aspects que sont analysées les chansons du corpus, surtout à partir des textes, mais en considérant aussi certains éléments musicaux.

Musiques et diversité à Montréal. Un orchestre dans une communauté d’immigrants roumains et moldaves - LeBlanc, Sébastien; Sako, Hatouma; Fernando, Nathalie (Cahiers d’ethnomusicologie, 2019)
Au sein de la province du Québec, la majorité des immigrants choisissent de vivre à Montréal et y forment des communautés au sein desquelles leurs pratiques musicales du pays d’origine perdurent au-delà du processus migratoire. Depuis trois ans, notre équipe de recherche travaille à Montréal auprès de diverses communautés issues de l’immigration pour comprendre comment le musical participe au « Vivre ensemble ». Nous émettons l’hypothèse que la musique est pour les immigrants un outil pertinent d’intégration et de négociation identitaire afin de vivre au sein d’une société conviviale et d’y contribuer. La perspective comparative qui est la nôtre vise à faire ressortir ce qui est privilégié selon les cas de figures par les communautés elles-mêmes tant au sujet des répertoires musicaux que des processus de reconstruction identitaires à travers la musique. Dans cet article, nous présenterons nos observations au sujet de la communauté issue de l’immigration roumaine et moldave. Le groupe ainsi nommé est loin de représenter une homogénéité quelconque en dehors de l’origine qui est mentionnée sur les fiches de données produites par Statistiques Canada. Nous nous appuyons sur des exemples précis issus de nos travaux de terrain auprès de cette communauté afin de démontrer que nous avons affaire à un cosmopolitisme musical qui trouve pleinement sa place et son expression dans un tel contexte urbain.
ISBN: 9782884744843 Number: 32 Publisher: Infolio Editeur / Ateliers d’ethnomusicologie

Hubert Lenoir et les révélations de l’affliction - Leguerrier, Louis-Thomas (Sens public, 2019)
Quand Hubert Lenoir, lors de son entrevue à Tout le monde en parle, a déclaré : « J’ai un peu le goût de me crisser en feu ces temps-ci », s’attirant les remontrances des animateurs qui jugeaient de mauvais goût le fait de dire une telle chose à la télévision, et de surcroît sur un plateau où se trouvait un invité ayant déjà fait une tentative de suicide, cela a provoqué un certain émoi dans le public, et on reprocha d’un côté au chanteur de banaliser le suicide et de l’autre aux animateurs d’avoir banalisé la détresse peut-être tout à fait sérieuse de celui-ci. Plutôt que de prendre part à ce débat, ou encore de proposer des stratégies pour briser les tabous au sujet du suicide, je voudrais aborder la dimension littéraire de ce fameux malaise télévisuel, qui est liée au malaise de l’époque contemporaine face à ce que j’appellerai ici la mise en scène de l’affliction.
Keywords: Hubert Lenoir; Susan Sontag; affliction; impudeur; indecency; literary; littéraire

« Cohérence d’une œuvre métissée » : extrait de thèse de doctorat (2007) - Makdissi-Warren, Katia (Circuit, 2019)
Publisher: Circuit, musiques contemporaines

Représentation et redéfinition de la relation avec les Premiers peuples dans la chanson québécoise depuis 1960 : de la prise de conscience à l’émergence d’une chanson des Premiers peuples - Melançon, Johanne (Études canadiennes / Canadian Studies. Revue interdisciplinaire des études canadiennes en France, 2019)
La chanson populaire constitue un moyen privilégié pour faire changer les perceptions et revoir l’image que nous avons construite des Premiers peuples et elle permet de redéfinir les relations entre Autochtones et Allochtones. C’est ce que démontre un parcours de la chanson populaire québécoise de 1960 à 2019, qu’il s’agisse de chansons d’Allochtones (Gilles Vigneault, les Séguin), de chansons d’Autochtones, surtout à partir du succès de Kashtin au début des années 1990, de Chloé Sainte-Marie qui choisit de chanter en innu-aimun, ou du métis Samian dans les années 2000 qui multiplie les collaborations, pour arriver à l’émergence d’une chanson autochtone au Québec.
Number: 87 Publisher: AFEC
Keywords: Autochtones; chanson québécoise; identité; postcolonialisme

Katia Makdissi-Warren : étapes et œuvres marquantes - Pascal, Noémie (Circuit, 2019)
Publisher: Circuit, musiques contemporaines

L’univers de Katia Makdissi-Warren (un diagramme) - Pascal, Noémie (Circuit, 2019)
Publisher: Circuit, musiques contemporaines

"A Jewish Maestra and a Lady too": Reflections on Femininity in the Career of Ethel Stark - Rachwal, Maria N. (Canadian Jewish Studies, 2019)
Ethel Stark (1910-2012) was one of the most important conductors and concert violinists in Canada in the Twentieth century. This article highlights how an Austro-Canadian Jewish woman who lived outside the constraints of conventional domesticity, both navigated through and defied the ideals of the “Cult of True Womanhood” and spearheads a movement of feminism in music. I argue that Stark’s exposure to Jewish cultural traditions of social justice and womanhood in her childhood formed a critical dimension of her feminist activism later in her life, and in particular in the founding of The Montreal Women’s Symphony Orchestra (1940).

“Saw You in the Dark”: Exploring Rufus Wainwright’s Emotional Vulnerability in Fan-Captured Live Performance Videos - Salerno, Stephanie (Performance Matters, 2019)

The Expression of the Tragic in the Chamber Cantata Dați-Mi Lampa Lui Aladin [Give Me Aladdin's Lamp] by Dora Cojocaru - Seraz, Roxana Maria (Musicology Papers, 2019)
Dora Cojocaru is recognized as an outstanding representative of the Cluj school of composition, but also as a strong voice in Romanian musicology. While her musicological output includes books, studies, articles, radio programs, conference papers, master classes and scientific communication sessions, her most important contribution remains the book entitled Creația lui Gyӧrgy Ligeti în contextul stilistic al secolului XX [Gyӧrgy Ligeti's Work in the Stylistic Context of the Twentieth Century], which was the first book about Ligeti that appeared in the Romanian musicological landscape. Dora Cojocaru’s compositional portrait can be drawn by following the language characteristics and compositional devices used in the chamber cantata Dați-mi lampa lui Aladin [Give Me Aladdin's Lamp]. The composer’s work is characterised by a propensity for chamber music. The composer confesses that it is also a consequence of the fact that this genre comes with a plethora of expressive possibilities. In terms of the musical language used by the composer, its first characteristic is the concern to avoid repetition in expression and the variation of an already used musical material. This is strikingly evident in the chamber cantata Dați-mi lampa lui Aladin [Give Me Aladdin's Lamp]. Another peculiarity is the construction based on a developmental discourse, while a third characteristic is the frequent construction of the discourse based on an economy of means and on a musical material consisting of only a few notes. In the case of this cantata, it is essential to note the historical context, which is closely linked to the symbolic title suggesting the composer’s desperate desire to bring her brother back to life, although she is aware that this is only possible by magic. The composer’s choice of lyrics is derived from the fact that Trakl’s and Rilke’s texts allude to the theme of death, which is one of the frequent themes of late Expressionism, and are therefore pervaded by a tragic note, in tune with the composer’s musical intentions. If we follow the text-music relationship, we notice some extremely significant moments, in which music creates sonic images that are suggestive of the message of the text.

Serving Each Other: Sharing Economies and Affective Labour in Montréal's Kiki Scene - Tailor, Jesse (Université Carleton, 2019)
Against a tense socio-political backdrop of white supremacy, intensifying pressures of neoliberal fiscal austerity, and queer necropolitics, this thesis addresses performance-based activist forms of place-making for urban-based queer, trans, and gender nonconforming communities of colour. Using participant observation and qualitative interviews with pioneering members of Montréal’s Kiki scene and Ottawa’s emerging Waacking community and interpreting my findings through the theoretical lens of queer of colour theory, critical whiteness studies, queer Latinx performance studies and Chicana feminism, I argue that Kiki subculture, which is maintained by pedagogical processes of ‘each one, teach one’, is instrumental in facilitating i) life-affirming queer kinship bonds, (ii) alternative ways to simultaneously embody and celebrate nonnormative gender expression with Black, Asian, and Latinx identity, iii) non-capitalist economies of sharing, and iv) hopeful strategies of everyday community activism and resilience to appropriative processes during economic insecurity and necropolitical turmoil.

Reality Sounding: Annesley Black’s not thinking about the elephants - Tan, Anthony (Circuit, 2019)
This paper presents an analysis of Annesley Black’s not thinking about the elephants (2018), for saxophone quartet and live electronics. Written for Montreal’s Quasar Saxophone Quartet, this work explores concepts of suppression and emergence through traditional musical dimensions such as melody, counterpoint, and form, but also through contemporary musical dimensions such as psychoacoustics (difference tones), theatrical elements, and live electronics. Black’s practice engages critically with the compositional process itself by formulating dialectic relationships between material and compositional strategies (both intuitive and systematic). This work encourages the listener to engage in a multidimensional listening experience where conceptual extremes become a catalyst for the building of narrative and tension.
Publisher: Circuit, musiques contemporaines

Mon Starmania. Par la première serveuse automate - Thibeault, Fabienne (Éditions Flammarion Québec, 2019)
Né il y a 40 ans de la collaboration entre Michel Berger et Luc Plamondon, le phénomène Starmania est probablement le plus grand succès musical franco-québécois. Outre les Français Daniel Balavoine et France Gall, la distribution originale réunissait quatre immenses interprètes d’ici : Claude Dubois, Diane Dufresne, Fabienne Thibeault et Nanette Workman. La carrière de chacun a été marquée par cette aventure qui a aussi laissé sa trace indélébile dans notre imaginaire collectif. Fabienne Thibeault, qui avait 26 ans à l’époque, nous fait partager cette épopée dans l’intimité du couple formé par Michel Berger et France Gall chez qui elle a vécu à Paris. Pour compléter son récit, elle se remémore des anecdotes personnelles et donne la parole aux artisans moins connus (choristes, doublures, musiciens) de cette réalisation magistrale qui surprend toujours par son actualité.

Création contemporaine et partage des traditions : à la rencontre de Katia Makdissi-Warren - Tremblay, Vicky (Circuit : musiques contemporaines, 2019)
Un article de la revue Circuit, diffusée par la plateforme Érudit.
Publisher: Circuit, musiques contemporaines

Revitalising language through music: a case study of music and culturally grounded pedagogy in two Kanien’ke:ha (Mohawk) language immersion programmes - Vallejo, Jessie M. (Ethnomusicology Forum, 2019)
Since the 1990s scholars, teachers, and policy makers have debated over the importance of culturally grounded or culture-based education (CBE) approaches in primary and secondary programmes. For Indigenous communities, CBE methods are often regarded as decolonising tools that support linguistic and sociocultural revitalisation efforts. A majority of Indigenous educational projects have prioritised teaching language above other cultural components, such as music, which has largely been overlooked as a powerful tool due to the pervasive assumption that traditional musical practices rely on the language to survive. This article explores how cultural components have a symbiotic rather than a hierarchical relationship, focusing on the interdependence between language and music. Based on ethnographic fieldwork and observations with four Indigenous language immersion teachers, I argue that music is a linchpin pedagogical tool that promotes intergenerational interactions, builds social relationships, and facilitates the daily use of language in and outside the classroom.
Keywords: Haudenosaunee; Indigenous; Iroquois; culture-based education; decolonisation; language immersion

Empowering Diversity: A Study Connecting Women in Leadership to Company Performance in the Canadian Music Industry - Women In Music Canada (Women In Music Canada, 2019)
Gender diversity in the music industry is low, both in Canada and internationally. The lack of diversity may represent a competitive disadvantage, as diversity is known to promote innovation and broad thinking, which is precisely what the music industry needs as it undergoes rapid change. This study, performed by Women in Music Canada in collaboration with PwC, assesses the impact of gender diversity of leadership within the Canadian music industry and the impact on company performance.

A Landscape of Memories through the Music of Hope Lee - Feliz, Juro Kim (Nomadic Sound Worlds, 2018)
Produced by Juro Kim Feliz under the Canadian Music Centre Library Residency, Nomadic Sound Worlds is a four-part blog/podcast series exploring Canadian contemporary music through the lens of present-day global migration. A collection of essays named Letters of Transit: Reflections on Exile, Identity, Language, and Loss (ed. André Aciman, 1999) informs and inspires this project, with trajectories branching out from related themes including mobility, displacement, loss, reconciliation of polarized truths, and invention of selves. In this regard, the series will feature selected immigrant Canadian composers whose musical worlds collide with various personal stories of immigration.

Ana Sokolović. Robots musicaux et kolo serbe - Harman, Brian (La création musicale au Québec, 2018)
Code: La création musicale au Québec

Their Own Agenda: The History, Development, and Culture of Women's Orchestras Outside the United States - Alger, Bonnie Eve (Université du Maryland, 2018)
Women have been active as performers of instrumental music since the Medieval period, and yet their contributions are often overlooked. This dissertation examines the history of women’s orchestras outside the United States, and explores their development, as well as reasons for existing. Several factors regarding their development are taken into consideration, including time period, country, and culture in which the ensemble is present. The birth of the women’s orchestra is traced from the ospedali of the 18th century Venice to today. All-female ensembles from England, Canada, Cuba, and Afghanistan are profiled, as well as the Women’s Orchestra in Auschwitz. Two modern-day women’s orchestras – the Allegra Chamber Orchestra in Vancouver, British Columbia, and my recital orchestra at the University of Maryland – were surveyed in an attempt to learn more about the culture of women’s orchestras. This paper seeks to answer the questions “What is the culture of women's orchestras today, and should they continue to exist?”

Jazz, gender, historiography: a case study of the "Golden Age" of jazz in Montreal (1925-1955) - Blais-Tremblay, Vanessa (Université McGill, 2018)
This dissertation maps the interaction between jazz, identity, modernity and nation during the so-called "golden age" of jazz in Montreal (1925-1955). Drawing on the fields of musicology, women's studies (black feminist theory and feminist research methods in particular), critical dance studies, and cultural studies, this project provides a critical re-writing of the history of Montreal jazz, one which acknowledges various roles that racialized and ethnicized women played in the shaping of modern identities, pleasures and sounds in Quebec. Montreal's particular status as a "showtown" makes it a rich laboratory to study the collaborative creative relationships between jazz music and dance on the black variety stage in the first half of the twentieth century. I also map the specific parameters that articulate the discursive relationship between jazz and vice, in particular as these relate to the gendered and racialized embodiment of morality in interwar Quebec. Finally, this dissertation produces the first extensive biographical accounts and critical listening of several prominent Montreal-based female jazz artists, including pianists Vera Guilaroff and Ilene Bourne, all-girl groups such as The Spencer Sisters and the Montreal Melody Girls Orchestra, black women performers such as Tina Baines Brereton, Bernice Jordan Whims, Marie-Claire Germain, Mary Brown, Natalie Ramirez, as well as piano teacher Daisy Peterson Sweeney and dance teachers Ethel Bruneau and Olga Spencer Foderingham.

Entrevista com a cantora e compositora Bïa Krieger [Entretien avec l'autrice-compositrice-interprète Bïa Krieger] - Cassiano, Raissa (Tradterm, 2018)
Radicada há mais de vinte anos na França e no Canadá, Bïa Krieger conquistou um público cativo nesses países, onde recebeu prêmios importantes, como o Grand Prix de l’Académie Charles Cros (França), Prix de l’Adisq (Canadá) e Félix du Meilleur Album Musiques du Monde (Canadá). Esta entrevista contempla o seu trabalho como versionista, com enfoque nas versões em francês para canções de Chico Buarque.

Aller à la quête de l’œuvre : Véronique Lacroix et les 30 ans de l’ECM+ - Champagne, Éric (Circuit : musiques contemporaines, 2018)
Publisher: Circuit, musiques contemporaines

Broadcasting Queer Feminisms: Lesbian and Queer Women Programming in Transnational, Local, and Community Radio - Copeland, Stacey (Journal of Radio & Audio Media, 2018)
Notable radio scholars including Christine Ehrick, Phylis A. Johnson, and Caroline Mitchell have explored critical challenges of gender and sexuality radio research and its importance in relation to communities. A major issue faced in studying the early years of women’s history in broadcast is the ephemeral nature of the medium as many of the voices are lost in the ether, unrecorded or once deemed inessential to archive. Web-based radio and podcast archives provide renewed avenues for listening to lesbian and queer women’s radio across transnational borders yet many long running shows in Canada such as The Lesbian Show on Vancouver Co-Op Radio have only recently begun to surface as digital collections. As personal and institutional archives of lesbian and queer women radio begin to reach a public audience, analysis of radio works across decades of LGBTQ2+ activism and feminisms must be traced to understand the role of radio and digital radiogenic media in creating space and identity for queer activism. A turn to the past brings forward questions of analog and digital futures for radio and podcasting space as place to construct and shape queer and especially lesbian communities and identities in the North American broadcasting industry. Through research of notable live and pre-produced content including Dykes on Mykes on CKUT 90.3 FM, and The Lesbian Show on Vancouver Co-Op Radio, this work offers an exploration of radio and radiogenic media’s role in creating sonic space for queer and feminist subjectivities.
Publisher: Routledge _eprint: https://doi.org/10.1080/19376529.2018.1482899

Diane Dufresne. Aujourd'hui, hier et pour toujours - Dufresne, Diane (Éditions Libre Expression, 2018)
Diane Dufresne est l'une des plus célèbres voix de la chanson québécoise et figure parmi les artistes les plus importantes de notre époque. Sa virtuosité et sa créativité est reconnue tant au Québec qu'en Europe. À soixante-quatorze ans, elle poursuit activement sa carrière. Sa popularité est immense et, au fil des ans, elle a reçu de nombreuses distinctions. Cet ouvrage, élaboré en collaboration avec son époux, l'artiste sculpteur Richard Langevin, propose une rétrospective d'un parcours riche en événements et en succès. De Tiens-toé ben j'arrive! à Magie rose en passant par Les Violons du Roy, ce livre relate les grandes étapes de la vie professionnelle et personnelle de la chanteuse à partir de photos souvenirs et d'images inédites. Un véritable devoir de mémoire.

Pauline Julien, intime et politique - Ferland, Pascale (Office national du film du Canada, 2018)
Suivant un minutieux choix d'extraits d'entrevues, de spectacles et de photos, puisés à même un colossal et riche fonds d'archives, Pauline Julien, intime et politique nous entraîne dans le sillage de cette femme résolument libre et engagée, figure emblématique de la chanson et d'une époque charnière de l'histoire du Québec.

On feeling mighty real: devenir gay à Montréal pendant l’ère disco dans Funkytown, de Daniel Roby - Foerster, Maxime (Contemporary French Civilization, 2018)
Our catalogue of journals

Représentation de soi et matérialité des lettres dans la correspondance amoureuse entre Pauline Julien et Gérald Godin (1962-1993) - Germain, Emmanuelle (Université Laval, 2018)
Pauline Julien et Gérald Godin ont entretenu une correspondance amoureuse s’étendant sur plus de trente ans, soit de 1962 à 1993. Quelques-unes de leurs lettres ont fait l’objet d’une publication, La Renarde et le mal peigné (Leméac Éditeur, 2009), grâce à Pascale Galipeau, fille du comédien Jacques Galipeau et de Pauline Julien. Mais c’est avant tout le corpus inédit de plus de 400 lettres non reprises, découvertes dans les fonds d’archives à BAnQ, qui feront l’objet de nos recherches. Outre sa « fonction documentaire » (Jaubert, 2010a : 74), cette correspondance permet de voir la mise en scène par laquelle s’élabore la construction du moi de Julien et de Godin. Au fil de leur échange épistolaire, chacun joue sur l’impression qu’il tente de produire sur l’autre, de manipuler la mise en scène du moi qui régule leur interaction amoureuse. Dans l’ensemble des lettres, cette présentation de soi relève d’une complexion plus vaste que celle qui se dégage des choix éditoriaux effectués dans La Renarde et le mal peigné, restreinte à la relation amoureuse. Permettant d’éclairer la relation personnelle entre Julien et Godin, ainsi que leurs trajectoires artistiques respectives, cette correspondance constitue le lieu d’une négociation entre leurs postures publiques (poète journaliste puis ministre et chanteuse engagée) et intimes (homme de lettres au foyer et femme de profession). De fait, même si leurs échanges restent intimes, il y a là une présentation de soi qui se confronte à la nécessité de négocier avec la médiatisation de leur figure publique, celle-ci influençant leur part de contrôle sur la figure intime qu’ils tentent de dessiner dans leur correspondance. Des textes de Ruth Amossy (La présentation de soi. Ethos et identité verbale et Images de soi dans le discours : la construction de l’ethos), d’Anna Jaubert (« L’éthos de l’épistolier au miroir de l’autre ») et d’Arlette Farge (Le goût de l’archive), constitueront les bases théoriques de notre étude.
Accepted: 2018-12-07T00:01:21Z

La renarde et le mal peigné - Julien, Pauline; Godin, Gérald (Leméac Éditeur, 2018)
Dans ces « fragments de correspondance amoureuse », on découvre Pauline Julien et Gérald Godin comme jamais on ne les avait vus, comme jamais plus on ne les verra. Lui, jeune loup puis loup mature, passionné, dévoué à la cause et amoureux. Elle, mère, chanteuse, absente souvent, incertaine et amoureuse. Elle que le doute assaille, toujours. Lui, de plus en plus sûr. C’est un magnifique tango qui se déroule sous nos yeux, on s’attire et se repousse dans le même paragraphe. Et c’est beau. Que c’est beau! La poésie qui les habite en permanence est suffisante pour rendre n’importe quel esprit jaloux, suffisante pour affadir n’importe quel amour. Pascale Galipeau, fille de Pauline Julien, a dû braver objections et réprimandes pour publier ces lettres. On ne peut que la remercier à genoux et lui baiser les mains de ne pas avoir cédé.

Les épreuves du travail musical : la persévérance des musiciens et musiciennes au Québec - Lavoie-Ricard, Olivier (Université de Montréal, 2018)

A Rich Musical Legacy from Québec: Baroque Motets of the Ursuline and Hôtel-Dieu Monasteries of New France - MacIsaac, Elizabeth Kathleen Norah (Université de Washington, 2018)
Carefully preserved in the archives of the Ursuline and Hôtel-Dieu Monasteries of Quebec are several manuscripts containing Canada’s first sacred works for female voices. The manuscripts contain dozens of intricate motets composed in the French Baroque style, a repository of music which has not been sung for hundreds of years. These motets form a neglected part of Canada’s musical heritage which is waiting to be unearthed and explored. Ursuline and Augustinian nuns arrived to the French territories of the New World to educate and evangelize young women. Singing formed a core element of their teaching and worship. For over one hundred years (1639-1760), church music provided a backbone to Canada’s vibrant musical culture. When the French territories were lost to Britain and Spain, musical culture shifted radically and the sacred French music simply faded into obscurity. An overview of the sweeping events of the French Baroque era includes discussion of France’s social conditions, the political and religious climate, the flowering of the arts and the exploration of the New World. In France, the seventeenth and eighteenth centuries were a time of great strife which heralded the massive social changes to come in the nineteenth century. France’s struggles directly impacted the colony of New France, including that of its religious institutions and music. This study traces the musical activities in the Ursuline community of New France as the nuns lived their mission on the frontier, teaching Aboriginal and colonial girls. The evolution of female emancipation stemming from religious evangelism is considered. Examination of a trove of 160 motets located in the female monasteries of Québec City reveals the high caliber of music practiced by the nuns. No interpretive editions for performance purposes exist. Newly transcribed works have been generated from the manuscripts, with period performance guidance for appropriate ornamentation and ensemble requirements. An in-depth discussion of New France Baroque vocal and choral musical styles is provided, with reference to historical records of how it was taught, as described in contemporaneous music treatises and many original documents specific to these religious female communities.

Avant-propos. Pour des musicien·ne·s organiques ? - McKinley, Maxime (Circuit, 2018)
Publisher: Circuit, musiques contemporaines
Keywords: Inclure l'avant-propos ?

L’intermédialité autochtone dans l’œuvre de Natasha Kanapé Fontaine : mémoire, oralité et territoire - Morin-Martel, Florence (Université de Montréal, 2018)
Ce mémoire explore la notion d’intermédialité autochtone au sein de l’oeuvre de Natasha Kanapé Fontaine. Les imbrications entre les médias seront notre point d’appui pour penser les questions de l’esthétique dans l’art autochtone actuel. Par le biais de la représentation d’un média dans un autre, nous aborderons ainsi la réactualisation des traditions orales telles que le conte, le mythe, le chant et le tambour au sein des productions de cette artiste. Notre parcours observera les structures intermédiales qui mettent en exergue la mémoire ainsi que les connaissances ancestrales. Les croisements entre l’identité et le territoire seront également discutés dans l’optique des représentations intermédiales. Ainsi, les phénomènes d’affirmation et de réactualisation des savoirs se déploient par l’utilisation de divers médias. De ce fait, la résistance environnementale et culturelle ainsi que la néo-oralité sous-tendent l’oeuvre de l’artiste et s’expriment à travers les territoires imaginaires et médiatiques.

Isabelle Panneton. De la rigueur à la liberté de création - Nattiez, Jean-Jacques (La création musicale au Québec, 2018)
Code: La création musicale au Québec

"The Canadian Inhabitants are Remarkably Fond of Dancing": Reading the African Musicians in George Heriot's Minuet of the Canadians (1807) - Nelson, Charmaine A. (Towards an African Canadian Art History: Art, Memory, and Resistance, 2018)
Towards an African Art History: Art, Memory, and Resistance, is the first book to consoloidate the field of African Canadian Art History. In this book, Charmaine A. Nelson and her colleagues–a group of established and up-and-coming artists, scholars, and cultural critics–argue for an African Canadian Art History that can simultaneously examine the artistic contributions of black Canadian artists within their unique historical contexts, critique the colonial representation of black subjects by white artists, and contest the customary racial homogeneity of Canadian Art History. Challenging the traditional notions of artistic value, this groundbreaking book examines art, artists, and visual and material culture from the eighteenth century to the present, analyzing "high," "low," and popular art across various media, with a focus to offer a new perspective on Canadian Art History–an African Canadian Art History

Le hip-hop avec des gants blancs - Néméh-Nombré, Philippe (Liberté, 2018)
Réflexion sur la dépolitisation et l’éclaircissement du hip-hop lors de son passage dans la culture de masse.

Du teweikan à l'électro : voyage aux sources de la musique autochtone - O'Bomsawin, Kim (Société Radio-Canada, 2018)
Il y a très longtemps, hommes, femmes et enfants de tous âges, clans, allégeances et nations se sont unis au son des vibrations du teweikan, qui signifie tambour traditionnel. Entre les mains des auteurs-compositeurs-interprètes Pakesso Mukash (Cri/Abénaquis), Shauit (Innu) et Moe Clark (Métis), il s’avère toujours un puissant outil de communion. Sous des airs désormais folk, électros ou reggae, le teweikan s’efforce encore aujourd’hui de créer des ponts entre les générations, les vivants et les morts, les territoires, ainsi que les conquis et les insoumis. Nous en profiterons pour remonter le fil de l’histoire de la musique des Premières Nations, du teweikan à l’électro, de Montréal à la baie d’Hudson, des plaines canadiennes à la Côte-Nord.

Lhasa de Sela et la traversée des espaces - Proulx, Robert (Archiv für Textmusikforschung, 2018)
The singer-songwriter Lhasa de Sela (1972-2010) launched her career and produced her three records in Montreal where she arrived in 1991. Not only did she change the face of migrant song in Quebec, but she also enjoyed international success, embarking on long world tours and selling more than a million records. This analysis will focus on the songs from her second album, The Living Road, and will show that Lhasa de Sela transcended linguistic and artistic frontiers by crossing the geographical border when she made Montreal her home and creative hub.

Guerre ou pas, j'irai danser la veille du jour de l'an. Chroniques d'une danseuse invétérée - Roquigny, Peggy; Saint-Jacques, Denis; Des Rivières, Marie-Josée (Les médias parlent et chantent. Chroniques de la vie culturelle à Montréal durant la crise et la guerre, 2018)

Alys vue par Rita - Savoie, Chantal (Les médias parlent et chantent. Chroniques de la vie culturelle à Montréal durant la crise et la guerre, 2018)
Durant la Crise et la Deuxième Guerre mondiale, on imagine Montréal sans ressources pour la culture, Montréal ligotée, bâillonnée. C’est bien mal la connaître. Au contraire, elle s’engage alors dans une des grandes révolutions du siècle, soit celle des médias qui parlent et qui chantent. Le cinéma, la radio, le disque y recomposent l’environnement du divertissement et des arts d’une manière surprenante. Et ces nouveaux médias ne remplacent pas la presse, le concert ou le théâtre, ils s’y ajoutent, multipliant l’offre à un point qu’on n’avait encore jamais vu. Cela révolutionne la vie chez soi où, en plus du journal et du magazine, dont les tirages explosent, le piano rencontre deux nouveaux concurrents, le gramophone et le récepteur radio. Sans être riche, on peut entendre des concerts, même de musique autochtone et de grandes vedettes, chez soi, on peut « swinger » sur le jazz chez soi. On peut aussi sortir, ce que facilite un urbanisme stimulé par les nouvelles gares. Les salles de cinéma, de danse, se multiplient. C’est là qu’on se laisse emporter par le jazz ou « Tico, tico ». On se plaint chaque année que le théâtre se meurt ? Ça n’empêche pas une rencontre entre Shakespeare et Alfred Pellan. Ou d’aller entendre un transethnique prêcher l’écologie. Et aussi de s’habiller à la mode pour aller skier sur la montagne. Ce bouleversement transforme le visage de la ville, comme nous le révèlent les peintres juifs, les radioromans, ou deux œuvres majeures du temps, Two solitudes et Bonheur d’occasion. On ne verra plus jamais Montréal avec les mêmes yeux, on n’entendra plus jamais Montréal avec les mêmes oreilles. Avec des textes de Marie Beaulieu, Justin Bur, Marc H. Choko, Marie-José des Rivières, Dominic Hardy, Lorne Huston, Germain Lacasse, Laurier Lacroix, Marie-Thérèse Lefebvre, Renée Legris, Jocelyne Mathieu, Sandria P. Bouliane, Adrien Rannaud, Peggy Roquigny, Lucie Robert, Mario Robert, Denis Saint-Jacques, Chantal Savoie, Esther Trépanier et Elspeth Tulloch.

Music from the Wrong Place: On the Italianicity of Quebec Disco - Straw, Will (Criticism, 2018)
One of my favorite compilation CDs of the last few years is Unclassics: Obscure Electronic Funk and Disco, 1975–1985, released in 2004 on the Environ label. The thirteen tracks on Unclassics were collected and remixed by house/techno artist Morgan Geist, who offers them as all-but-forgotten dance music gems from just outside an Anglo-American musical axis, from places like Spain and Italy. The style that ostensibly unites these tracks is “Eurodisco,” though, as we shall see, that label does not accurately subsume all of them. “Italo-disco” seems an even cruder reduction, but circulates among critics, fans, and collectors as a meaningful label for much of the music gathered here. While some of the cuts on Unclassics have long been the idiosyncratic favorites of DJs or dance music collectors, more is going on here than the resurrection of cultish or neglected treasures. Unclassics is one milestone within the significant rehabilitation of European and Italian disco that has unfolded over the last decade. Mixed Up in the Hague, Vol. 1, a compilation first released privately in 1999, was a key event in this rehabilitation; other collections, like I-Robots: Italo Electro Disco Underground Classics and Confuzed Disco: A Retrospective of Italian Records, have followed. Zyx, the Germany-based label that dominated the field in the 1980s and early 1990s, is actively marketing dozens of compilations of its own Italo-disco from that period. The garish red and green covers of Zyx’s Italo anthologies, which filled the discount cassette bins of European airport stores fifteen years ago, have been redesigned so that they now look authoritative and curatorial. Radio and DJ sets devoted to this music now abound on the Internet. Think Italy. Without claiming mind-reading powers, it’s a comfortable prediction you’ve already got tacky piano sample records and frenzied all-night clubbing in mind, a nation that when it isn’t knocking out club records by the cartload likes nothing more than to party all night on a hillside by the sea. Italian music has been in and out of style more often than the flares revival. There are enough piew-piew-piew zaps during these 55 minutes to wipe out a small nation of roller skaters. For almost two decades, tracks like those collected on Unclassics held the status of morbid symptoms, reminders of the decay and dispersion of dance music in the years between disco and house music. Even as they reclaim these tracks as lost gems, the liner notes to Unclassics embrace that morbidity, relishing the ways in which so many of these pieces are seen to have gotten things wrong. My favorite track on Unclassics is a Spanish cut from 1979, “Margherita,” whose guiltless dishing out of pleasures betrays the compilation’s broader sensibility. Piercing little synth notes alternate with thick, rolling movements that could drive an army forward. Mariachi horns interweave with tinny keyboard glissandos in rounding out sections. Changes come precisely when we want them; each gimmicky sound or flourish dutifully returns just as we start to miss it. As “Margherita” moves in unstoppable fashion around its wheel of styles and sections, it is easy to think that this is music trying too desperately to be liked. Dominant understandings of the European contribution to disco read its influence selectively, focusing on the robotic, synthesized sounds of Kraftwerk or Giorgio Moroder. These versions of Eurodisco’s history link such figures as Can, Patrick Cowley, Afrika Bambaataa, and Juan Atkins in a heroic story that sends disco to Europe so that it may return, reinvented, to an American underground able to realize its radical potential. When Eurodisco is remembered for its sleek mechanical control, however, what gets forgotten is the lush extravagance that seemed to mark so much of it. As early as 1977, North American critics had recourse to a well-entrenched moral geography in characterizing disco music from continental Europe as “florid,” given to flamboyant passion and bombastic overlays of effects.1 Arguably, the peculiarity of so much Eurodisco came from the ways in which its extravagant lushness often went hand in hand...

“Come One, Come All”: Blackface Minstrelsy as a Canadian Tradition and Early Form of Popular Culture - Thompson, Cheryl (Towards an African Canadian Art History: Art, Memory, and Resistance, 2018)
Towards an African Art History: Art, Memory, and Resistance, is the first book to consoloidate the field of African Canadian Art History. In this book, Charmaine A. Nelson and her colleagues–a group of established and up-and-coming artists, scholars, and cultural critics–argue for an African Canadian Art History that can simultaneously examine the artistic contributions of black Canadian artists within their unique historical contexts, critique the colonial representation of black subjects by white artists, and contest the customary racial homogeneity of Canadian Art History. Challenging the traditional notions of artistic value, this groundbreaking book examines art, artists, and visual and material culture from the eighteenth century to the present, analyzing "high," "low," and popular art across various media, with a focus to offer a new perspective on Canadian Art History–an African Canadian Art History

La scène travestie qui est à l’origine du punk à Montréal - Desfossés, Félix B. (Vice, 2017)

À l’assaut de Montréal : les chanteurs country-western dans les studios de la métropole, 1942-1958 - Lefrançois, Catherine (Mens, 2017)
L’imaginaire campagnard associé à la chanson country-western masque une réalité méconnue. Entre 1942, année du premier enregistrement sur disque de Roland Lebrun, et 1958, année de la fondation de la première maison de disques indépendante spécialisée dans la production d’enregistrements country-western, le genre se structure en partie autour de pratiques artistiques et de réseaux urbains. Cet article propose une histoire culturelle de la chanson country-western par l’intermédiaire, notamment, de ses pratiques médiatiques. Au premier plan de cette analyse se trouve la radio, qui, en faisant une place inédite aux amateurs, permet aux premiers chanteurs country-western non seulement de se faire connaître et de se professionnaliser, mais aussi de développer une relation de grande proximité avec le public. Un bref portrait du rôle du studio d’enregistrement et des maisons de disques, qui offrent un revenu stable à ces artistes, révèle un genre largement apprécié. D’un studio à l’autre, Montréal, aux côtés de villes industrielles importantes (Drummondville et Trois-Rivières, par exemple), joue un rôle prédominant. , This paper examines a few aspects of the cultural history of country-western music in Quebec. The rural imagery of the songs, with their cowboys, their farms, their mountains, hides an important phenomenon; at its beginnings, the genre heavily relies on urban networks and urban cultural practices. This is especially important during the structuration of the genre, between 1942, when Roland Lebrun records his first songs, and 1958, when the genre finally has its own independent record companies. During these 16 years, among other strategies, country-western artists use the media to start and promote their careers. Here, the radio plays an important role; with its openness to amateurs, it allows these artists to become professionals and to develop an intimate relationship with their audience. Recording studios provide them with a regular income between touring seasons. From one studio to another, Montreal, as well as important industrial cities of the time (Drummondville, Trois-Rivières), is an important protagonist in the structuration and the dissemination of the new genre, which deeply relies on urbanity and modernity despite the traditional image it tries to project at the same time.

Laura Niquay. Vivre et s’affirmer au féminin attikamekw - Audet, Véronique (Cahiers du CIÉRA, 2017)

Innu Nikamu. Chanter la résistance - Bacon Hervieux, Kevin (Vidéographe Distribution, 2017)
Un voyage à travers l'histoire et l'évolution du festival de musique Innu Nikamu, l'un des événements les plus importants des Premières Nations du Canada.

L’apport de Maryvonne Kendergi à la SMCQ - Bail, Louise (Circuit : musiques contemporaines, 2017)
To measure Maryvonne Kendergi’s contributions to the smcq, it is necessary to revisit her career in Quebec, which was based on the solid academic and professional training she received at Parisian institutions from 1929 to 1952. Thereafter, in Montreal, she was hired by Radio-Canada for her exceptional voice, and in September 1956, she embarked on a brilliant radio career as a promoter of contemporary music. Kendergi gradually introduced the listening public to the arcana of the Montreal avant-garde. In this endeavour she was encouraged by Stockhausen’s arrival in Montreal in 1958, by composers’ efforts in organizing International Music Week in 1961, by the foundation of the smcq in 1966, and by the influence of the latter organization, particularly in its collaboration with the Université de Montréal in establishing the Musialogues in 1969. The role of Kendergi’s exceptional skills in broadening the influence of the smcq is explored in this article.
Publisher: Circuit, musiques contemporaines
Keywords: Maryvonne Kendergi; Musialogues; Société de musique contemporaine du Québec (smcq); animatrice; host; music journalist; musicographe de radio

D’exil et d’américanitude : un entretien avec Linda Bouchard - Bertrand, Simon (Circuit : musiques contemporaines, 2017)
Quebec composer Linda Bouchard (born 1957) is an extremely prolific composer, particularly active on the new music scene in the u.s. where she has lived for lengthy periods since 1989. She has composed a rich and diverse catalogue of works, ranging from orchestral music to more intimist instrumentations, and also using multimedia or improvisation. In this interview, the composer reflects on the question of exile and identity in light of her own experience, thus reliving her own artistic path while also addressing some still burning questions about the place of music creators in the global culture.
Publisher: Les Presses de l’Université de Montréal
Keywords: composer; compositrice; exil; exile; identity; identité; parcours; society; société; trajectory

Femmes et jazz dans le Québec de l’entre-deux-guerres : entre le récit historique, les archives et le passé - Blais-Tremblay, Vanessa (Les Cahiers de la Société québécoise de recherche en musique, 2017)
Cet article porte sur les rôles que les femmes ont joué dans le développement d’une scène jazz à Montréal. Les archives témoignent de l’importance des pianistes Vera Guilaroff et Ilene Bourne, de l’enseignante de piano Daisy Peterson Sweeney, des enseignantes de danse Olga Spencer Foderingham et Ethel Bruneau, ainsi que des danseuses de variétés dans le développement de la plus grande scène jazz du Canada au cours de la première moitié du xxe siècle. Cet article contextualise la présence des femmes dans ces espaces performantiels précis (le piano, l’enseignement, la danse) et explore les processus historiographiques liés à leur exclusion des récits historiques.
Publisher: Société québécoise de recherche en musique

30 ans d'arts autochtones au Québec, 1986-2016. Bilan et synthèse - Côté, Jean-François; Cyr, Claudine; Tirel, Astrid (Groupe de recherche interdisciplinaire sur les affirmations autochtones contemporaines, 2017)
Ce rapport de recherche porte sur la création artistique autochtone au Québec des trente dernières années. Il propose un bilan de la période 1986-2016, en termes d’artistes et de productions, en se basant sur des données recueillies selon les sources présentement accessibles, et en répertoriant sept disciplines artistiques (arts visuels, cinéma, conte, danse, littérature, musique, théâtre). Le bilan que nous présentons, bien que ne pouvant prétendre à l’exhaustivité, contient néanmoins suffisamment d’informations pour donner une très bonne idée de l’état de la création artistique autochtone des trois dernières décennies, en évaluant son essor et son développement actuel en termes de nombre d’artistes, de volume de production, de contributions selon l’ensemble des communautés autochtones du Québec, et selon la répartition femmes/hommes parmi les artistes et disciplines ; enfin, il présente des données sommaires quant au financement accordé aux productions artis- tiques autochtones, mais pour une partie seulement de la période étudiée. Dans ce sens, ce rapport doit être lu en lien aux autres rapports produits ces dernières décennies sur la question de la création artistique autochtone, notamment ceux des principaux conseils des arts (Conseil des arts du Canada, Conseil des arts et des lettres du Québec – le Conseil des arts de Montréal, bien qu’étant un acteur présent dans le soutien aux arts autochtones, n’a pas produit de rapports dans ce domaine).

Claudette Dion: La soeur de... - Girard, Jean-Yves (Éditions La Presse, 2017)
Ce livre donne la parole à une femme authentique, sereine, pétillante et attachante qui sait son privilège de s'appeler Dion, tout en portant fièrement son prénom. Avec humour et tendresse, elle révèle ce que c'est que d'être la sœur de... Entre une mère très médiatisée et une petite sœur devenue mégastar, au milieu de treize frères et sœurs, Claudette a su trouver sa place au soleil. Un regard unique. Des propos inédits.
Keywords: Biography & Autobiography / Entertainment & Performing Arts; Biography & Autobiography / General; Biography & Autobiography / Personal Memoirs; Biography & Autobiography / Women

Beverly Glenn-Copeland: Inspiring stories and advice from a boundary-breaking musician - Hockin, Johnny (Red Bull Music Academy, 2017)

Buena vida - K, Florence (2017)
« Il y a de ces moments où l'on peut avoir l'impression de patauger dans une boue solide, presque opaque, à travers laquelle la lumière peine à passer. Et pourtant, lorsqu'on s'y attarde un peu, combien de fois tirons-nous nos initiatives les plus courageuses, nos créations les plus belles, nos décisions les plus sages au moment où nous sommes nous-mêmes couverts de boue, lorsque nous nous retrouvons dans la merde jusqu'au cou ? » Florence K a vécu une enfance de saltimbanque. Elle baigne dans la musique et les tournées. Dans Buena vida, elle livre un récit rempli d'humanité, de musique, de voyages, et dévoile une partie de son existence qu'elle surnomme « l'abysse ». Sa vingtaine a été parsemée de grandes joies, entre le bonheur de la maternité et celui d'avoir réussi à faire de la musique son gagne-pain. Mais Florence est aussi passée par un trou noir qui a bien failli l'engloutir et duquel elle est sortie encore plus amoureuse de la vie. C'est en toute transparence qu'elle partage sa descente aux enfers et sa renaissance, car « la vie, c'est tout ce qu'on a ».

Musique et intégration à Montréal : le cas de l’Orchestra Rapsodia Româna - LeBlanc, Sébastien (Université de Montréal, 2017)

Cool Control, Occam, and Océan: The Radigue and Bozzini Game - Majeau-Bettez, Emanuelle (Les Cahiers de la Société québécoise de recherche en musique, 2017)
Cet article analyse la nouvelle collaboration entre la compositrice et pionnière de musique électronique, Éliane Radigue, et le Quatuor Bozzini. Débutant vers la fin des années 1960, la carrière d’Éliane Radigue se caractérise par de très longues oeuvres de musique électronique qui semblent de prime abord ne pas changer, et dans lesquelles les micro-oscillations naturelles entre les hauteurs remplacent la rythmique traditionnelle. Depuis 2001, Radigue ne travaille plus qu’avec des instrumentistes et utilise un « processus de composition intuitif » semblable à la « transmission orale de musiques traditionnelles anciennes » (Sonami 2017). Alors que les quelques intellectuels qui ont fait montre d’intérêt envers la musique de Radigue ont concentré leur attention sur l’aspect oral de ses compositions, cet article cherche ici à amener l’analyse au-delà des paramètres formels « non-écrits » de sa musique afin d’explorer comment la sonorité d’une pièce de Radigue génère de nouvelles manières de concevoir la performance et la composition. Les notes d’observation de l’auteure, la correspondance entre l’auteure, la compositrice et le quatuor, et les enregistrements des rencontres entre les Bozzini et Radigue seront utilisés pour retracer les moments de grande réaction émotionnelle causés par la sonorité très particulière que demande la musique de Radigue. Ces réactions affectives du côté de Radigue et du quatuor révèlent des points de tension entre différentes conceptions de la création collective, et réorientent complètement ce que cela signifie que de posséder, transmettre, interpréter et composer de la musique. Des spectrogrammes et des enregistrements des tentatives entreprises par les Bozzini seront utilisés dans l’étude de ces points de tension, et démontreront qu’afin de pouvoir jouer avec succès une pièce instrumentale de Radigue, les Bozzini doivent reproduire chaque élément des pièces électroniques de la compositrice; le quatuor à cordes doit se « transformer » en un étrange instrument.
Publisher: Société québécoise de recherche en musique

Björk Digital : escale à Montréal - Marcotte, Nicolas-Alexandre (Circuit : musiques contemporaines, 2017)
An article from Circuit, on Érudit.

L'âme en tannage de Natasha Kanapé Fontaine : Souveraineté orale, territoriale et mémorielle - Marcoux, Gabrielle (Canadian Review of Comparative Literature / Revue Canadienne de Littérature Comparée, 2017)

A performer's perspective on three works for pianist and moving images : analysis with performance and practice strategies for Michel van der Aa's 'Transit', Nicole Lizée's 'Hitchcock Études', and 'Surface Tension' by Eve Egoyan and David Rokeby - Morano, Christopher (Université de Colombie-Britannique, 2017)
Interest in audio-visual works of art that are performed by a live pianist while integrating projected moving visual images has waxed and waned over a period of almost 300 years. The past twenty years or so has seen a re-emergence of this genre of classical music composition which places extra demands on the pianist performing these works. This dissertation explores the history of this genre, proposes a framework for analysis of these pieces, and examines from both analytical and performance perspectives three contrasting works for this medium: Michel van der Aa’s 'Transit', Nicole Lizée’s 'Hitchcock Études', and 'Surface Tension' by Eve Egoyan and David Rokeby. This research was

Présence arabe, berbère et nord-africaine au Québec. Cinquante ans de musiques plurielles (1962-2017) - Nabti, Mehdi (Éditions L'Harmattan, 2017)
Ce livre présente l'apport culturel des musicien(ne)s et chanteurs/chanteuses d'ascendance arabe, berbère et nord-africaine au Québec de 1962 à 2017. Qui sont les artistes issus de ces cultures les plus importants au Québec ? Qu'ont-ils produit ? Quelles sont leurs démarches artistiques et quelles difficultés éprouvent-ils ? Comment les médias et le secteur culturel québécois les accueillent-ils ?
Keywords: Art / General; Music / General; Social Science / Sociology / General

Partition pour femmes et orchestre. Ethel Stark et la Symphonie féminine de Montréal - Rachwal, Maria Noriega (Éditions du remue-ménage, 2017)
En 1940, deux femmes élégantes prennent le thé dans le lobby du Ritz-Carlton. Ne vous fiez pas aux apparences: leur rencontre annonce un grand chambardement dans l’univers de la musique classique. La mécène Madge Bowen et la violoniste Ethel Stark fondent à Montréal ce qui deviendra le premier orchestre symphonique canadien composé uniquement de femmes. […]

L'incertitude matérielle et existentielle de la carrière musicale au prisme des relations interpersonnelles - Rheault, Dominique (Université du Québec à Montréal, 2017)
La précarité du domaine musical professionnel au Québec se traduit pour les musicien-ne-s par l'expérience de l'incertitude matérielle et existentielle, conséquence d'un cadre d'emploi flexible (Bain et McLean, 2012). Ce mémoire vise à comprendre leur trajectoire professionnelle et se situe dans la perspective des études organisationnelles sur les carrières « sans frontières » (Arthur et Rousseau, 1996). La première forme d'incertitude rencontre la nécessité : 1) de développer un savoir/savoir-faire flexible à l'emploi; 2) de multiplier des métiers au sein du domaine musical; 3) et de cultiver un réseau professionnel. La seconde se définit par l'« équivocité » (Weick, 1995, 1996, 2005) et est liée : 1) à l'acquisition du savoir-être; 2) à la question du sens de la carrière; 3) et au soutien social. Nous inscrivons également cette recherche dans cette nécessité d'effectuer plus d'études empiriques sur le rôle des relations interpersonnelles dans la carrière musicale (Di Maggio, 2011; Cummins-Russell et Rantisi, 2012; Azam, 2014; Menger, 2014). Ainsi, comment vivent-elles-ils les incertitudes de la carrière musicale? En quoi leur réseau de relations interpersonnelles leur permet-il de les réduire? Cela nous a amenés à rencontrer six musicien-ne-s professionnel-le-s québécois-es pour les questionner sur leur parcours, leurs enjeux professionnels et cartographier leur réseau de collaboration selon la « méthode du générateur de noms » (Saint-Charles et al., 2008) et plus largement la démarche de analyse de réseaux sociaux (Wasserman et Faust, 1995). Nos résultats indiquent que la réduction de l'incertitude matérielle passerait par un processus de professionnalisation aux frontières des organisations du domaine musical et l'entretien de relations interpersonnelles de confiance. Pour elles/eux, la carrière musicale se distingue des carrières « typiques » puisqu'il s'agit surtout d'une « histoire de passion » où le succès professionnel est déterminé par la capacité à se lier aux autres et à vivre cette « expérience de sociabilité » du domaine musical. Ce mémoire vise à explorer un phénomène peu documenté et à identifier certaines pistes de recherches futures sur ce sujet.

Claude Vivier ou la machine désirante - Richard, Robert (Éditions Varia, 2017)
"Claude Vivier, compositeur méconnu au Québec, est né à Montréal en 1948. Il meurt assassiné à Paris en 1983. Il a fait ses études avec Gilles Tremblay et Karlheinz Stockhausen. Son œuvre – qui contient une quarantaine de titres – est inclassable, s'inspirant de ou bougeant à travers des époques très différentes de l'histoire de la musique, depuis le Moyen Âge jusqu'à la musique dite « spectrale » des années 1980. C'est une œuvre d'une grande originalité, qui a choisi la fuite hors des attentes ou des formes prévues et qui a cherché à délirer les continents, les langues, les peuples."–From publisher's website

Louise Beaudet. De Lotbinière à Broadway - Saint-Pierre, Marjolaine (Éditions du Septentrion, 2017)

Les mondes du Lindy Hop : appropriation culturelle et politiques de la joie - Sékiné, Anaïs Leï (Université de Montréal, 2017)
Le Lindy Hop et les danses Jazz africaines américaines du début du XXe siècle font aujourd'hui l'objet d'une sous-culture internationale. Leur popularité se nourrit en grande partie de la mise en valeur de leur joie et d'un cadre social hospitalier. Bien que cette culture soit aujourd'hui majoritairement investie par des danseurs non africains-américains, elle bénéficie d'une relation privilégiée avec plusieurs aînés, anciens habitués du Savoy Ballroom de Harlem, le lieu mythique où la danse s'est initialement développée. À leur côté, les processus de recréation, d'actualisation et de transmission de ces danses historiques présentent le terrain complexe d'une appropriation culturelle, celle d'un savoir situé afrocentrique et de la représentation de sa joie inhérente. À partir du paradigme épistémologique de la théorie critique, féministe et intersectionnelle du point de vue, cette recherche examine la démarche de traduction transculturelle, où le sens des récits des aînés et l'expression de leur affect en viennent à être substitués par des stratégies racialisées d'équivalence et d'identité et des rapports savoir/pouvoir non examinés. L'analyse s'est particulièrement centrée sur une lecture du cadre idéologique de la sous-culture, de sa « volonté de savoir » et du rapport « mythologique » (Roland Barthes) des danseurs à l'histoire et à l'authenticité. Le terrain s'est défini par une approche interdisciplinaire, multisite, ethnographique et phénoménologique située, représenté par trois études de cas localisées. Une observation participante a eu lieu dans le plus grand rassemblement international annuel de danseurs au Herräng Dance Camp suédois (1). Elle a mis en lumière un système de référence dominant et hégémonique qui perpétue les bases d'une marginalisation sociale et racialisée, malgré l'importance donnée à l'africanité de la danse et la promotion de valeurs d'ouverture, de participation, de communauté et de liberté proactive. Cette communauté culturelle, caractérisée par une volonté libérale de « bonne pratique » sociale, a aussi été le contexte d'émergence de figures « killjoy » (Sara Ahmed) (2) mettant en évidence l'homogénéité sociale structurelle de la sous-culture. L'affirmation féministe noire de ces dernières a également permis de contextualiser et de situer la dynamique politique, raciale, genrée et économique du récit des Anciens et de leur expérience du Harlem Renaissance qui a donné naissance à la danse. À partir d'une posture éthique et critique contre-hégémonique, soutenue par une articulation de la pensée d'Hannah Arendt et de la théorie postcoloniale, la conclusion de la recherche s'est réalisée autour d'une recherche-action participative dans l'école de danse Cat's Corner à Montréal (3). Elle a été le terrain d'une remise en cause appliquée d'un système culturel et pédagogique stabilisé par un régime hégémonique de la blanchité. Les résultats se sont concrétisés dans une réforme pédagogique de l'enseignement des danses Jazz, fondée sur une approche plus holistique et non conformiste de leur tradition et sur l'intégration d'une éthique renouvelée de la relation.

Le son au théâtre et en danse contemporaine : les principes conceptuels récurrents de ma pratique - Tobin, Nancy (Université du Québec à Montréal, 2017)
Ce mémoire-création porte sur la conception sonore pour le théâtre et la danse contemporaine. Il vise à fournir des connaissances qui puissent faciliter l'intégration du son au sein d'une création scénique. La recherche dont il est question ici se concentre uniquement sur les aspects conceptuels et non techniques, toutes deux intrinsèques au processus de création du son. Me basant sur mon expérience de concepteure sonore, plus précisément à partir de l'étude de mes notes de chantier de création entre 1999 et 2014, je dégage dix principes récurrents qui indiquent des conditions optimales pour concevoir le son. Ce mémoire-création est l'analyse d'une approche personnelle et le processus méthodologique a été autopoïétique et heuristique. L'étude se présente en trois sections. La première s'intéresse aux récits des processus de création où chaque principe émerge à partir de l'expérience qui est racontée. Dans la deuxième section, les principes s'explicitent davantage au travers l'étude de textes sur la conception du son. Un corpus d'auteurs, surtout des praticiens de la création sonore, est déterminé pour cette partie. Un livret compose la troisième section. Il incarne la partie « création » de ce mémoire. Il s'agit encore de préciser les principes, mais cette fois au travers de dix lettres fictives, destinées à des étudiants-es. Chaque lettre, dont le sujet est un problème rencontré en cours de processus de création, vise à expliquer un principe dans un contexte concret. Le titre du livret est La conception sonore selon Nancy Tobin 01. Mon nom apparaît dans le titre pour signifier qu'il est surtout question de mon approche personnelle. La mention des chiffres « 01 » indique que le livret démarre une série où d'autres personnes conceptrices sont invitées à écrire sur leur propre expérience. Peu de textes sur la conception sonore - sur l'expérience concrète du faire - existent. Ce mémoire-création vise à combler en partie cette lacune et à inviter d'autres créateurs à écrire sur leur pratique. L'expression par le sonore est riche et diversifiée. Plus les pratiques seront partagées et diffusées, plus il sera possible de multiplier les possibles de l'espace de l'écoute.

Bilan et perspectives sur la situation des compositrices au Québec : vers un décloisonnement des identités - Tremblay, Vicky (Les Cahiers de la Société québécoise de recherche en musique, 2017)
In the field of composition in Quebec, women composers are still less numerous than men composers. While the profession of composer has difficulty being recognized in Quebec society, women composers are twice as marginalized. Many of give evidence to the challenges they face when it comes to integrating into the musical community, and several musicologists have tried to better understand—and eventually solve—the problems specific to women in the field of composition.
Publisher: Société québécoise de recherche en musique

Animating the Object: Marcelle Deschênes and acousmatic education in Quebec - Valiquet, Patrick (Organised Sound, 2017)
This article examines the early reception of Pierre Schaeffer’s theoretical work in Quebec through the teaching of Marcelle Deschênes, principal author of the first electroacoustic theory and ear training curricula at both Université Laval and Université de Montréal. An account of Deschênes’s educational career is provided, along with remarks on the contents of her early courses in Morpho-typology and her listening workshops for children, using newly excavated primary material from her private archives. While existing scholarship presumes that Schaefferian thinking arrived in Quebec with the ‘orthodox’ acousmatic approach of Francis Dhomont, this article asserts that a pluralist and multidisciplinary interpretation of Schaeffer’s work can be discerned which pre-dated Dhomont’s teaching and has had an equally lasting impact overall. A methodological argument is also made for including education and other forms of ‘reproductive labour’ in the history of electroacoustic music.

Nicole Lizée : adepte de la hantologie - Van Vliet, Kiersten (La Scena Musicale, 2017)

Nightclubbing: Montréal’s Lime Light - Pemberton, Rollie (Red Bull Music Academy, 2016)
The Lime Light and its innovative DJ Robert Ouimet made Montreal a disco city during the ’70s. This is the club's story.

Montréal Rave: An Oral History - Borzeix, Olivier (Red Bull Music Academy, 2016)
Tiga, Christian Pronovost, Jeff Waye and more remember the golden era of raves in Montréal.

C'est vital. Portraits dynamiques de la production culturelle autochtone en milieu urbain au Québec - Abitbol, Jonathan; Audet, Véronique; Gaudet, Janice Cindy; Guimont Marceau, Stéphane; Maltais-Landry, Aude; Lumsden, Mélanie; Parent, Marie-Josée (DestiNATIONS : Carrefour International des Arts et Cultures des Peuples autochtones, 2016)
DestiNATIONS est un projet culturel fédérateur autochtone d’envergure internationale basé à Montréal. Il émerge du RÉSEAU pour la stratégie urbaine de la communauté autochtone à Montréal, une association qui représente plus de 950 membres organisationnels et individuels de la communauté autochtone de Montréal. Le RÉSEAU a fait de ce projet d’ambassade culturelle autochtone une priorité transversale. DestiNATIONS s’est incorporé en mars 2014 et a tenu son assemblée générale de fondation le 21 mai 2015. DestiNATIONS a pour mandat de diffuser, promouvoir, produire, rechercher, soutenir et commanditer des produits artistiques, éducatifs et culturels multidisciplinaires (films, jeux vidéo, réalités virtu elles, danses, sculptures, musiques, artisanats, etc.) des Peuples autochtones, d’éduquer les publics sur les cultures autochtones traditionnelles et contemporaines et d’accueillir des rassemblements artistiques, politiques et culturels. DestiNATIONS est un lieu de rassemblement pour les Autochtones. DestiNATIONS est aussi un pôle de diffusion et de production de calibre international dédié à la découverte des cultures autochtones pour le plus grand plaisir des visiteurs et touristes internation aux. En 2015, DestiNATIONS s’est associé à Tourisme Autochtone Québec pour poursuivre la réalisation du projet d’infrastructure culturel et touristique de 6000 mètres carrés, basé à Montréal, appelé Legs des Premières Nations et des Inuits.

Where Is She? Finding the Women in Electronic Music Culture - Abtan, Freida (Contemporary Music Review, 2016)
The author discusses the visibility and participation of women in electronic music culture. She argues that most electronic music social networks privilege male inclusion and success, and that skill-sharing is an important strategy to encourage women in the field. To seed this discussion, the author examines her own history with reflections on the gender dynamics within electronic music communities outside the academy, and the role that social and technical currencies play within them. She also discusses Ladies club, a music distribution project that led to several solo female electronic musicians taking the stage and organising events in Montreal during 2007.
Keywords: Culture; Electronic Music; Feminism; Gender; Skills-Sharing

The Transmemoric Process: The Journey of Italian-Québécois Artists - Aloisio, Anita (Université Concordia, 2016)
The author focuses on the multilayered social identities internalized by seven second-generation Italian-Quebec artists and how it is manifested in their artwork. She examines how Quebec's political landscape, especially the impact of Quebec's linguistic, nationalist and cultural debates, and the subjects' parents' experience of immigration, impinged on the artistic process and production. The author demonstrates how these artists connect their Italian ethnicity to a creative practice to achieve a sense of balance between family traditions, personal identity, and belonging. The seven artists are: Vittorio Rossi (Playwright, Actor); Agata De Santis (Documentary Filmmaker, Producer, Blogger); Sandra Coppola (Filmmaker, Scriptwriter); Luisa Pepe (Singer, Songwriter); Franco Taddeo (Comedian); Michaela Di Cesare (Playwright, Actor); and Marco Calliari (Author, Composer, Musician).

La réception du hip-hop chez des rappeurs afro-québécois dans la ville de Québec : appropriation intersectionnelle de problématiques multidimensionnelles - Atséna Abogo, Marie Thérèse (Université Laval, 2016)

Creative layers and continuities: A case study of Nicole Lizée and the Kronos Quartet - Bayley, Amanda; Lizée, Nicole (Musicae Scientiae, 2016)
This study examines the creative layers and continuities evident within the composition and rehearsal processes of Nicole Lizée’s Golden Age of the Radiophonic Workshop (Fibre-Optic Flowers), written for the Kronos Quartet in 2012. Lizée’s compositional approach to the historic and the new, and the mechanical and the human, are interpreted through Simon Emmerson’s three themes of combination, transformation, and control, and his three “impulses within composition” that combine live and acousmatic soundworlds – integration, antithesis, and co-existence. These concepts also help to articulate the way the players engage with the physical, psychological, and expressive demands of the piece. Discussions arising from the Kronos Quartet rehearsing the piece with the composer reveal how extensions are made to the performers’ mind and body experiences when they are required both to initiate and integrate sounds emanating from unfamiliar, analogue machines into their acoustic, yet amplified soundworld. Creative layers and continuities are seen to evolve from compositional experimentation and from composer–performer and co-performer dialogues in rehearsal in the BBC Maida Vale studio prior to the world premiere at a BBC Prom concert on 24 July 2012.
Publisher: SAGE Publications Ltd
Keywords: Delia Derbyshire; Kronos Quartet; Radiophonic Workshop; composition; creativity; electronic sounds; interaction; notation; rehearsal; string quartet

Le Club musical de Québec : 125 ans - Bernier, Emmanuel (Cap-aux-Diamants, 2016)

Robert Ouimet and Pierre Gagnon - Burns, Todd L. (Redd Bull Music Academy, 2016)
Explore the Red Bull Music Academy archive, tracing the global music institution’s more than 20-year history

Éva Gauthier. La voix de l’audace - Cazelais, Normand (Fides, 2016)

De l’homosexualité à l’opéra - Champagne, Éric (L’Opéra : revue québécoise d’art lyrique, 2016)
Créée à l’Opéra de Montréal, l’œuvre de Kevin March, Les Feluettes, sur un livret de Michel Marc Bouchard, aborde de front une histoire d’amour entre deux hommes. Si les sujets homosexuels nous semblent communs dans la littérature, le théâtre et le cinéma, il faut se rendre à l’évidence qu’ils sont, du moins jusqu’à tout récemment, peu présents dans le monde de la musique, tous styles confondus. On entend beaucoup dire ces jours-ci que le genre de l’opéra, au public réputé conservateur, ne s’intéresse à cette thématique que depuis peu. Il s’agit en fait d’une demi-vérité, car s’il est vrai que l’homosexualité comme sujet principal n’est présent explicitement que dans des créations récentes, il se retrouve occasionnellement, caché ou crypté, dans diverses œuvres qui traversent son histoire vieille de plus de 400 ans.

The Songs of Violet Archer: Tracing the Evolution of One of Canada's Most Prominent Composers - Dauphinais, Paul (Université de Boston, 2016)
In this study, four sets of songs composed by Violet Archer are examined, all of which were written at different points in her career. Archer studied with Paul Hindemith in 1948 – 49, and his teachings had a tremendous impact on the young composer. The first set of songs to be analyzed, Moon Songs, was written before her time with Hindemith, and will provide a baseline from which her later, post-Hindemith, works can be compared. Following her studies with Hindemith, Archer wrote three songs, “Cradle Song,” “April Weather,” and “First Snow,” all of which show evidence of Hindemith’s influence. Her later, more mature works, Northern Landscape and Caleidoscopio Quatro, demonstrate a refined compositional technique; one in which Archer has created her own style, while maintaining aspects of the approach taught by Hindemith at Yale. This study will elaborate on the aspects of Archer’s music that evolved throughout her compositional career.
ISBN: 9781369365658
Keywords: Archer; Communication and the arts; Hindemith; Music analysis; Paul; Social sciences; Violet

Paroles inuites : création et transmission dans la chanson du Nunavik - Duvicq, Nelly (Recherches amérindiennes au Québec, 2016)
Among the forms of oral history, the song, within the Inuit culture, was general practice and quite versatile. Inheriting this tradition, the contemporary Inuit song has risen in popularity starting in the 1970’s and has not diminished since. Within the literary field, the lyrics to the Inuit songs demonstrate a remarkable vitality in which the author-composers explore various aesthetics, navigate languages and transmit a part of their culture. Taking into consideration the historical context, this article aims to reflect on the formal evolution of the modern Inuit song and examine the relations that are maintained through more traditional portrayals. Finally, the ultra-contemporary body of musical works in Nunavik is notable for being particularly trilingual yet reveals an upsurge of texts in Inuktitut. What significance will this have on the overall discourse?
Publisher: Recherches amérindiennes au Québec
Keywords: Inuit literature; Inuit songs; Inuktitut; Nunavik; canción inuit; chanson inuite; inuktitut; literatura inuit; littérature inuite; oralidad; orality; oralité

Claude Vivier at the End - Goldman, Jonathan (Contemporary Music and Spirituality, 2016)

Entendu dans Cette ville étrange : « Fuck toute ! » – une génération de compositeur·e·s décomplexe sa marge - Henry, Symon (Circuit, 2016)
Publisher: Les Presses de l’Université de Montréal
Keywords: Pas sur genres ou/et sexualités

Rap, genre, langage et québéquicité : enjeux et tensions sociolinguistiques de l’accès aux espaces médiatiques à Montréal - Lesacher, Claire (Cahiers internationaux de sociolinguistique, 2016)
Bibliographie_available: 1 Cairndomain: www.cairn.info Cite Par_available: 0 Publisher: L'Harmattan

DJ Mini and Montreal’s Vulgar Dance Music - Madden, David (Dancecult, 2016)
This article advances claims about Montreal’s electronic dance music scene through mapping the career of one of the key actors who shaped the electroclash scene from the early 2000s onwards—music producer/DJ Mini (née Evelyne Drouin). By way of detailing the career of DJ Mini, this text attempts to add to the queer musical narratives currently emerging from music scene analyses. Counter to the experiences of many women DJs and musicians participating in heterosexual and male-dominated music scenes, Drouin received extensive mentoring and support from various informal queer social networks spread throughout the circuits of the city. Not only did she gain access to a local production network of equipment and skill sharing, Drouin was also given access to spaces where she was able to develop production skills on her own time and at her own pace. DJ Mini’s story offers a telling case for the ways in which the politics of access—institutional, social, technological—remain central to the vitality and inclusivity of local music scenes.

Analyses of Organ Etudes Opp. 38, 66 and 72 by Rachel Laurin - Mateva, Silviya (Université d'Oklahoma, 2016)

Listening to "Mes lames de tannage": Notes toward a Translation - Moyes, Lianne (Canadian Literature, 2016)

On the Internet by Means of Popular Music: The Cases of Grimes and Childish Gambino - Ohlendorf, Kristopher R. K. (Université Western Ontario, 2016)
What is the internet? It began as a military research experiment, but the internet has since become a sweeping cultural phenomenon. One of the most prevalent areas of the internet’s cultural dominance is in popular music, and this thesis addresses how the internet is being understood and discussed by popular music artists. I study the works of Grimes and Childish Gambino, two popular music artists who grew up alongside the internet’s rise to cultural dominance and explicitly address this experience as an integral component of their lives and works. I look specifically at discourse surrounding Grimes’ “post-internet” music and Childish Gambino’s expansive conceptual work Because the Internet (2013). This research concludes by addressing how popular music artists like Grimes and Childish Gambino are helping produce the ways in which we understand and discuss the cultural phenomenon of the internet, and how they provide a foundation for future artists and research to build upon.

« La terre qui nous a vus grandir ». Le sujet et le monde chez Mara Tremblay, Ariane Moffatt et Salomé Leclerc - Pirie, Nathan (Université de Waterloo, 2016)
Cette étude inclut les œuvres de Mara Tremblay, Ariane Moffat et Salomé Leclerc et vise un objectif double : d’une part, il s’agit d’analyser des textes lyriques qui ont une indéniable qualité poétique et d’autre part, de réaliser une étude intermédiale alliant texte, musique et clip-vidéo afin de voir comment le sens d’un de ces éléments est infléchi, modifié ou complété par celui des autres éléments. L’hypothèse de recherche est qu’aujourd’hui, les auteurs-compositeurs-interprètes conçoivent leur art à travers trois langages esthétiques (le texte, la musique et la vidéo), faisant de la musique une expérience plurisensorielle et intermédiale. Pour faire émerger le message de ces artistes, on mobilisera les théories du care et l’écoféminisme afin d’analyser le discours portant sur le sujet et le monde. On vise à dégager les grands thèmes de ces œuvres à travers une synthèse de ces trois approches critiques. L’analyse du corpus vise à déterminer la qualité poétique des textes et la vision du monde que ces trois artistes diffusent.

True Loves, Dark Nights: Queer Performativity and Grieving Through Music in the Work of Rufus Wainwright - Salerno, Stephanie (Université d'État de Bowling Green, 2016)

Vers une reconstitution de la vie culturelle des femmes à Montréal dans les années 1940 - Savoie, Chantal (Voix et Images, 2016)

Écritures chorégraphiques et sonores imbriquées : récits de collaborations avec Danièle Desnoyers - Tobin, Nancy (L’Annuaire théâtral : revue québécoise d’études théâtrales, 2016)
Ce texte revient sur le processus de création de trois spectacles chorégraphiques auxquels j’ai participé comme conceptrice sonore : Concerto grosso pour corps et surface métallique (1999), Duos pour corps et instruments (2003) et Là où je vis (2007). Ces parcours de recherche-création, traversés avec la chorégraphe Danièle Desnoyers (compagnie Le Carré des Lombes), permettent d’observer comment l’écriture sonore se développe in situ avec l’écriture chorégraphique. Les deux se forment ensemble en s’influençant l’une l’autre. Les trois spectacles choisis témoignent de différents modes de création de la matière sonore : amplification des danseurs, diffusion avec des haut-parleurs inusités, invention d’instruments et citation de musiques transformées. Les récits de collaborations qui suivent révèlent les manières dont la matière sonore a émergé de l’écriture chorégraphique et vice versa.

Changing openness and tolerance towards LGBTQ singer-songwriters - Williams, Katherine (The Cambridge Companion to the Singer-Songwriter, 2016)
Most often associated with modern artists such as Bob Dylan, Elton John, Don McLean, Neil Diamond, and Carole King, the singer-songwriter tradition in fact has a long and complex history dating back to the medieval troubadour and earlier. This Companion explains the historical contexts, musical analyses, and theoretical frameworks of the singer-songwriter tradition. Divided into five parts, the book explores the tradition in the context of issues including authenticity, gender, queer studies, musical analysis, and performance. The contributors reveal how the tradition has been expressed around the world and throughout its history to the present day. Essential reading for enthusiasts, practitioners, students, and scholars, this book features case studies of a wide range of both well and lesser-known singer-songwriters, from Thomas d'Urfey through to Carole King and Kanye West.

Rufus Wainwright - Williams, Katherine (Equinox Publishing, 2016)
Canadian-American singer-songwriter Rufus Wainwright is famous around the world for his multi-faceted musical style, shown through both his recorded output and his engaging live performances. Katherine Williams combines aspects of his life story with scholarly readings drawn from several methodologies.

La création des chansons chez les Innus : s’exprimer et manifester son existence - Audet, Véronique (Littoral, 2015)

La scène musicale populaire autochtone au Québec. Dynamiques relationnelles et identitaires - Audet, Véronique (Université de Montréal, 2015)

Rufus Wainwright sings "Grey Gardens": on Thomas Mann's "Death in Venice", Tadzio and his pop cultural "life" - Bałżewska, Katarzyna (Beyond Philology: An International Journal of Linguistics, Literary Studies and English Language Teaching, 2015)

Rising Sun: the True Story of Montreal's First International Jazz & Blues Festival - Boicel, Doudou (Doudou Boicel Éditeur, 2015)

A Study of Selected Representative Organ Pieces by Rachel Laurin - Cheng, S.S. (Université du Kansas, 2015)
Over the course of the last decade the organ works of Canadian composer Rachel Laurin (b. 1961) have gained critical acclaim among professional organists. Her organ music has captured the attention of American and Canadian organists, resulting in a series of commissions for new organ works. To date, there are over thirty-two compositions for organ solo. This document explores stylistic issues in Laurin's compositions for solo organ and for organ with other instruments. Pieces that have been selected for in-depth study include Chromatic Fantasietta, Scherzetto, Toccatarina (to Katarina) and Asian Legend from Twelve Short Pieces, Volume 3, op. 64, Étude Héroïque, Op.38, and the Sonata for Organ and Horn, Op.60, II. On a Painting by Thomson. At the outset of the document an overview of Canadian organ culture is provided, followed by an introduction to Laurin's life and works. Subsequently, a structural and harmonic analysis of Laurin's compositions is presented. As this analysis will reveal, the expressive dimensions of her works embrace elements of Romanticism and Impressionism.

Trajet de jeunesse d’une artiste de renommée mondiale. Maureen Forrester, fille de la rue Fabre - Cohalan, Kevin (Bulletin de la Société d’histoire et de généalogie du Plateau-Mont-Royal, 2015)

»Y’a que les très très vieux/ Qui ont encore l’espoir de mourir de vieillesse«. Alter und Apokalypse im französischen Chanson seit der Mitte des 20. Jahrhunderts [La vieillesse et l'apocalypse dans la chanson française depuis le milieu du XXe siècle] - Dietmar, Rieger (KulturPoetik, 2015)
After an introduction to the genre »chanson« and its fascination with real life, this article investigates the different ways in which French (and Franco-Canadian) chansons deal with ageing and old age. The study looks at the songs’ lyrics, which describe or represent old age in a manner between stereotype and intimate confession, and at the authentic or inauthentic performance of the chanson by its singer or singer-songwriter. The analyses are followed by an overview of chansons describing the end of the world. It can be shown that many of these songs focus on the feelings of lovers facing the apocalypse and that in more than one case chansons envisioning the last moments of the world contain a mixture of fear and parody.

La Bolduc. Parlure et accents de ses chansons - Duguay, Sylvie (Éditions Sylvie Duguay, 2015)

The Ethiopian and Eritrean Evangelical Diaspora of Montreal: Music, Identity and Ambivalence - Ferran, Hugo (African Diaspora, 2015)
The Ammanuel Montreal Evangelical Church (amec) is composed of over 150 members of Ethiopian and Eritrean origin. Through the examination of their musical practices, this article analyzes how music is involved in the construction and expression of religious identities in the context of migration. It appears that in borrowing worship music widespread in Ethiopia and in its diaspora, the faithful highlight the "Ethiopianness" of the group, at the expense of the minority Eritrean identity. The author then reveals that each musical parameter conveys different identity facets. If the universality of the Gospel message is expressed through dance and lyrics, the repertoire and its instrumentarium convey the "Ethiopianness" of the congregation, while the rhythms refer to a multi-ethnic Ethiopian imaginary. As for the local identity (Montreal) of the congregation, it is represented by the combination of several hymns borrowed from the stars of Ethiopian Gospel music. Finally, the paper highlights some musical ambivalences of the faithful who, in the context of migration, feel torn between several cultures.

La culture contemporaine du powwow chez les nations autochtones de l’est canadien - Giroux, Dalie (Géographie et cultures, 2015)
Le powwow compte parmi les pratiques culturelles les plus importantes de l’autochtonie nord-américaine, et constitue une pratique artistique en pleine expansion : alors que le powwow existe depuis le XIXe siècle dans le sud-ouest des États-Unis, de nombreuses communautés du sud-est canadien (essentiellement dans les provinces de l’Ontario et du Québec) ont investi cette forme culturelle dans les dernières décennies. L’étude présentée dans ce texte se penche sur ce phénomène des powwows du sud-est canadien, en s’attardant à la fois à la dimension de transferts culturels qui le définit, et à la dimension politique qui y est sous-jacente. Nous nous pencherons pour ce faire sur la définition et les influences autochtones aux origines du powwow contemporain, sur la géographie de ce que les praticiens qualifient de « retour des traditions, et sur la structuration géoculturelle des powwows du sud-est, parmi lesquels nous distinguerons le powwow ojibway (région ontarienne du nord des Grands Lacs), le powwow haudenosaune (péninsule de Niagara et vallée du Saint-Laurent), et le powwow est-algonquien (Outaouais, Haute Mauricie, Lac Saint-Jean).
Keywords: Amérique du Nord; North America; cultures autochtones; dance; danse; indigenous cultures; powwow; territoriality; territorialité

ECM+ Génération 2014 : regards sur les quatre compositeurs lauréats (1re partie) - Henry, Symon (Circuit, 2015)
Publisher: Les Presses de l’Université de Montréal

ECM+ Génération 2014 : regards sur les quatre compositeurs lauréats (2e partie) - Henry, Symon (Circuit, 2015)
Publisher: Les Presses de l’Université de Montréal

Sistema in the News: Exploring Media Coverage of Sistema-Inspired Programs in Montreal and Kahnawà:ke - Hopkins, Emily (Université de Montréal, 2015)

Leonard Cohen in the Global Village: Constructions of Identity and Desire in His Poetics - Icíar Álvarez Pérez, María (Université complutense de Madrid, 2015)

Elkahna Talbi : femme de paroles - Lalonde, Catherine (Jeu : revue de théâtre, 2015)
Publisher: Cahiers de théâtre Jeu inc.

L'esthétique rock queer : de C.R.A.Z.Y. à Xavier Dolan - Laverdière, Gabriel (Nouvelles vues. Revue sur les pratiques et les théories du cinéma au Québec, 2015)
L'analyse proposée des films C.R.A.Z.Y. (Jean-Marc Vallée, 2005), J'ai tué ma mère (Xavier Dolan, 2009), Les amours imaginaires (Dolan, 2010) et Laurence Anyways (Dolan, 2012) convoque trois perspectives : le rock, le camp et le queer. Dans ces films québécois, la musique rock semble orienter la narration et l'esthétique. Elle fait également le pont entre l'anticonformisme auquel renvoie le paradigme rock et l'identité marginale des personnages. L'esthétique de l'image se plie parfois à la bande sonore, qui encourage certains effets visuels. Cela dit, les films de Vallée et de Dolan se servent différemment de l'esthétique rock et du camp, ce qui s'accorde aux représentations distinctes qu'ils produisent eu égard à l'orientation ou à la diversité sexuelles et au genre. L'excès des films de Dolan, leur hyperréférentialité, leur jeu constant entre recherche d'émotions esthétiques et d'émois narratifs, leur fréquente suspension de la réalité contribuent à une écriture du différé dans laquelle les personnages queer jouissent d'une amplitude considérable, alors que dans C.R.A.Z.Y. la performance hyperbolique s'articule plutôt à une analytique de l'homophobie (sociétale et intériorisée) que le film s'efforce de dresser, sans pouvoir échapper à un certain malaise.

Le rap comme activité (s) sociale (s) : dynamiques discursives et genre à Montréal (approche sociolinguistique) - Lesacher, Claire (Université Rennes 2, 2015)
Cette recherche propose d’interroger l’activité rap montréalaise d’un point de vue sociodiscursif et à l’aune du genre, à travers le prisme des pratiques, des représentations, des expériences et des trajectoires de rappeuses à Montréal. Inscrite dans le champ de la sociolinguistique et arrimée aux, ancrages théoriques et épistémologiques qui envisagent le genre comme un rapport social coproduit et les subjectivités en tant que traversées des rapports sociaux, mais jamais Pleinement déterminées par ces derniers, cette étude se base sur une enquête de terrain réalisée en 2011 auprès de rappeuses à Montréal. Axée sur un corpus discursif et interprété selon une méthode qui croise analyse du discours et analyse de contenu thématique, elle engage une approche des phénomènes et des processus à l’œuvre en tant qu’ils sont territorialisés.Les pratiques, les expériences et les représentations des rappeuses seront envisagées dans un contexte marqué par leur « rareté ». Il sera constaté qu’outre une actualisation des rapports sociaux de sexe, les pratiques et les expériences des rappeuses sont aussi impactées par les enjeux sociolinguistiques de l’espace montréalais, ainsi que par ce qui relève du concept de québéquicité. Ainsi, les rappeuses composent leurs pratiques et leurs trajectoires en étant toujours situées à une place unique, dynamique et forcément ambivalente au sein de la matrice de la domination, et qui se façonne notamment par l’imbrication du genre, du langage, des représentations sur le rap, et des héritages d’une idéologie de la francophonie canadienne-française, que réactualise notamment le concept de québéquicité contemporain.

Willie Eckstein, Harry Thomas, Vera Guilaroff: Three Montreal Pianists from the Jazz Age - Litchfield, Jack (Autoédition, 2015)

Musiciens migrants d'origine arabe dans le contexte montréalais : le parcours de la reconnaissance - Marcoux-Gendron, Caroline (Université de Montréal, 2015)

Burgundy Jazz: Little Burgundy and the Story of Montreal Jazz - Marrelli, Nancy (Véhicule Press, 2015)
The area now called Little Burgundy was the birthplace of jazz in Montreal. Explore the textures of Montreal's jazz era through an array of rare jazz artifacts, including swizzle sticks and menus from renowned Montreal nightclubs, flapper dresses of the 1920s, porter uniforms, old LP vinyl records, cocktail shakers, and sheet music. Each object tells a fascinating story!

Mountain City Girls: The McGarrigle Family Album - McGarrigle, Anna; McGarrigle, Jane (Random House Canada, 2015)

Dans un grand champ nu. Des récits, des images, des chants - Miville-Deschênes, Monique (Éditions Trois-Pistoles, 2015)

Vivier reenacted: Singing beyond masculine - Novak, Jelena (New Sound: International Magazine for Music, 2015)
Vivier: A Night Report is a kind of poetical archive of musical details, protocols, experiences, concepts, memories, fears, desires and sorrows connected to Canadian composer Claude Vivier's (1948-1983) unusual destiny. All characters from Marko Nikodijević's opera originate from Vivier's life and works but they are re-indexed, or reenacted differently. The countertenor voice of Vivier is what primarily makes him different from all the rest of the characters. Even it could be claimed that the rest of the voices are dominated by Vivier's vocal presence on stage. Vivier stands as symbol for minority, queer, vulnerable. During his short life he was trying to get his own voice, voice as the personification of freedom and possibility to be heard. Finally he gets vivid, imaginative opera in which both his physical and personified voices are shining by creativity that his art emanate. He gets his singing voice, and he finally gets heard.

Vie musicale à l'église Saint-Viateur-d'Outremont. Victoria Cartier, première grande figure - Panneton, Hélène (Mémoire vivante, 2015)

Queering Discourses of Urban Decline: Representing Montréal's Post-World War II "Lower Main" - Podmore, Julie (Historical Geography, 2015)
In this paper, I examine how urban redevelopment and the regulation of public spaces in Montréal in the 1960s transformed the representations of the Lower Main, the city’s historic red-light and entertainment district. I argue that although the Lower Main had long been central to anti-urban discourses regarding heterosexual prostitution, by the 1960s the increased regulation of the city’s queer and trans populations changed its meaning as a representation of the inner city in decline. A central objective is to use this case study to queer discourses of urban decline by considering how heteronormativity was involved in the construction of the city’s sexual margins in the post-World War II period. A related objective is to call into question the narrative of “decline” itself by providing one example of the opportunities it created for queer place-making.

From Kitchen To Carnegie Hall: The Story of the Montreal Women's Symphony Orchestra - Rachwal, Maria Noriega (Second Story Press, 2015)
In the 1940s it was unheard of for women to be members of a professional orchestra, let alone play "masculine" instruments like the bass or trombone. Yet despite these formidable challenges, the Montreal Women's Symphony Orchestra (MWSO) became the only all-women orchestra in Canadian history. Formed in 1940, the MWSO became the first orchestra to represent Canada in New York City's Carnegie Hall and one of its members also became the first Canadian black woman to play in a symphony in Carnegie Hall. While the MWSO has paved the way for contemporary female musicians, the stories of these women are largely missing from historical records. From Kitchen to Carnegie Hall illuminates these revolutionary stories, including the life of the incredible Ethel Stark, the co-founder and conductor of the MWSO. Ethel's work opened doors of equal opportunity for marginalized groups and played an important role in breaking gender stereotypes in the Canadian music world.
Keywords: History / Canada / Post-Confederation (1867-); Music / History & Criticism; Music / Individual Composer & Musician

Pop Stars as Ambassadors of Sephardic Culture at the Festival Sefarad in Montreal - Roda, Jessica (Contemporary Jewry, 2015)
On their arrival in Montreal, Moroccan Jews established themselves as a community and created a festival in order to promote, gain recognition of, and institutionalize their culture and identity into the broader Jewish community of Montreal. In this article, I propose to analyse the festival as a “thing” (Kopytoff 1986), the biography of which will give us information about its transformation, in terms of representation, through time. From ethnography and historical analysis of the festival, as well as an examination of cultural policies in Canada, Quebec and Montreal during the last decades, we will discover that Sephardic musical heritage, which was initially used for community celebration, was progressively transformed into a marketable product embodied by international pop stars. The representation of Sephardic identity transitioned from a specific cultural reference to Morocco, to Judeo-Spanish and Judeo-Arabic songs, to a plethora of references promoted by Sephardic pop stars, mainly from France and Israel. More broadly, this study will illuminate issues surrounding strategies implemented by the community leaders to be part of these cultural policies and gain visibility in the public sphere.
Keywords: Festival; Montreal; Morocco; Representation; Sephardic; Stars

Les chemins de ma liberté - Simard, Nathalie (Éditions des Intouchables, 2015)

Java to Jazz: Eva Gauthier - Spiller, Henry (Javaphilia: American Love Affairs with Javanese Music and Dance, 2015)

Marketing, Merch, and Media: Nicole Lizée, in Conversation - Wiseman, Howard; Disman, Adriana (Canadian Theatre Review, 2015)
Nicole Lizée is an award-winning classical music composer and performer who composes for string quartet, electronic music, turntable, film, and other media. She has emerged as a major new voice in new classical composition, winning the coveted Canada Council for the Arts Jules Léger Prize (2013) for new Canadian chamber music with her work White Label Experiment. She has been commissioned by the Kronos Quartet among many other prestigious ensembles. This interview engages her relation to various aspects of her work, from marketing and promotion to inspiration and creation in the context of “avant garde” music. How can marketing continue to be part of the art itself? Does instinctively not fitting into a box allow for greater freedom to explore classical and chamber music in the broader context of film and other media? What other factors may be contributing to the inspired vitality of her work?
Keywords: Entretien

« Le train qui siffle ». Nostalgie et modernité dans la chanson country-western au Québec - Lefrançois, Catherine (Volume !, 2014)

Pour ne pas chanter idiote. Quand les Cultural Studies et la perspective féministe se marient - Boisclair, Isabelle (Françoise Stéréo, 2014)
Keywords: Pas de lien web

Women in Leonard Cohen's Work - Álvarez Pérez, Maria Icíar (Multidisciplinary Views on Popular Culture: Proceedings of the 5th International Selicup Conference, 2014)

Glimpses Into My Compositional Style and Techniques : Text and Musical Examples - Badian, Maya (Lucian Badian Editions, 2014)

La Bolduc en tournée : un patrimoine matériel unique - Boulay, Vicky (Magazine Gaspésie, 2014)
An article from Magazine Gaspésie, on Érudit.
Publisher: Musée de la Gaspésie

Shock, glam, punk - Desfossés, Félix B. (No Speed Limit (1964-1989). L’évolution du métal québécois, 2014)

Soprano Pierrette Alarie (1921-2011), tenor Léopold Simoneau (1916-2006). Part 1 - Duffie, Bruce (Opera Journal, 2014)
Keywords: Interviews; Music; Musical performances; Musicians & conductors; Singers

Soprano Pierrette Alarie (1921-2011), tenor Léopold Simoneau (1916-2006). Part 2 - Duffie, Bruce (Opera Journal, 2014)
Keywords: Accompanists; Composers; Librettists; Music; Musical performances; Musicians & conductors; Opera; Singers

Les Daraîche, la famille royale du country - Dumas, Carmel (Magazine Gaspésie, 2014)
Un article de la revue Magazine Gaspésie, diffusée par la plateforme Érudit.

Michel Louvain. Sans âge - Gignac, Benoît (Éditions Caractère, 2014)
Découvert au milieu des années 50, admiré et adulé, Michel Louvain fait encore battre les coeurs près de 60 ans après avoir amorcé sa carrière. Ce livre-coffret retrace le parcours irréprochable de cet artiste accompli, qui a remporté les honneurs autant pour ses performances sur disque, sur scène et à la télévision que pour son soutien à des causes sociales.

Claude Vivier: A Composer’s Life - Gilmore, Bob (University of Rochester Press, 2014)
Claude Vivier's haunting and expressive music has captivated audiences around the world. But the French-Canadian composer is remembered also because of the dramatic circumstances of his death: he was found murdered in his Paris apartment at the age of thirty-four. Given unrestricted access to Vivier's archives and interviews with Vivier's family, teachers, friends, and colleagues, musicologist and biographer Bob Gilmore tells here the full story of Vivier's fascinating life, from his abandonment as a child in a Montreal orphanage to his posthumous acclaim as one of the leading composers of his generation. Expelled from a religious school at seventeen for "lack of maturity," Vivier gave up his ambition to join the priesthood to study composition. Between 1978 and 1981 Vivier wrote the works on which his reputation rests, including 'Lonely Child', 'Bouchara', and the operas 'Kopernikus' and 'Marco Polo'. He went to Paris in 1982 to work on a new opera, the composition of which was interrupted by his murder. On his desk was the manuscript of his last work, uncannily entitled "Do You Believe in the Immortality of the Soul?" Vivier's is a tragic but life-affirming story, intimately connected to his passionate music. Bob Gilmore is a musicologist and performer and teaches at Brunel University in London. He is the author of 'Harry Partch: A Biography'.

Le Lunatique, « Le temps du changement » : Intimidation, ostracisme et homophobie dans le milieu hip-hop au Québec - Lamort, Kapois (Les boss du Québec. R.A.P. du fleur de lysée. Analyse socio-historique et sociologique du hip-hop dans la société québécoise, 2014)
Le tout premier livre monographique et scientifique axé sur la culture Hip-Hop au Québec, rédigé par Kapois Lamort, historien spécialiste diplômé de l’Université du Québec à Montréal ( UQAM); cet ouvrage retrace les 35 ans d’existence du H.I.P.H.O.P. à travers la société québécoise de 1979 à 2015

Mad Je Deviendrai : Les divas dans le hip-hop au Québec - Lamort, Kapois (Les boss du Québec. R.A.P. du fleur de lysée. Analyse socio-historique et sociologique du hip-hop dans la société québécoise, 2014)
Keywords: Italique avant les deux-points

Pétassetissité : Contenu explicite et lyrisme sexuel dans le hip-hop au Québec - Lamort, Kapois (Les boss du Québec. R.A.P. du fleur de lysée. Analyse socio-historique et sociologique du hip-hop dans la société québécoise, 2014)
Keywords: Italique avant les deux-points

Rap, langues, « québéquicité » et rapports sociaux de sexe : pratiques et expériences de rappeuses montréalaises d’origine haïtienne - Lesacher, Claire (Diversité urbaine, 2014)
In the stories recounting the early days of the rap scene in Montreal, actors of Haitian descent were particularly active on the rap scene: this is evident in rap texts, where frequent occurrences of Haitian Creole can be found. Considering this characteristic of Montreal rap, we propose a reflection on the issues around the visibility of Haitian migrants, and descendants of Haitian migrants, in Quebec public space by focusing on the practices and experiences of Montreal female rappers of Haitian descent. In this contribution, which aims at understanding the processes of hegemonization and minoritization at work in the Montreal and Quebec context, we will examine in particular how the vectors of differentiation involving language, “québéquicité” or gender, are manifested and reproduced in the media coverage of artistic productions.
Keywords: Haitian community; Rap; communauté haïtienne; gender; genre; languages; langues; « québéquicité »; “québéquicité”

Translanguaging in the Multilingual Montreal Hip-Hop Community: Everyday Poetics as Counter to the Myths of the Monolingual Classroom - Low, Bronwen; Sarkar, Mela (Heteroglossia as Practice and Pedagogy, 2014)
This chapter explores the possibilities multilingual hip-hop offers for language instruction within multiethnic classrooms in Montreal shaped by multiple discursive practices. The authors review current research on multilingualism and teaching and propose strategies for overcoming the French prescriptivist monolingual mindset in education in Quebec. They also turn to poetics, and in particular the literary theory of Edouard Glissant (Caribbean discourse, 1989; Poetics of relation, 1997) and the Martinican school of Créolité, offering possibilities for rethinking relationships between oral and written, vernacular and standard language forms and for igniting language teachers’ pedagogic imaginations.
Keywords: Creolization; Hip-hop; Oraliture; Popular culture

Le powwow contemporain dans l’est du Canada : une pratique du rassemblement - Mailhot, Amélie-Anne; Giroux, Dalie (Les arts performatifs et spectaculaires des Premières Nations de l’est du Canada, 2014)

In Search of a Different History: The Remains of Burlesque in Montreal - Mansbridge, Joanna (Canadian Theatre Review, 2014)
: Taking Elin Diamond’s and Rebecca Schneider’s recent work in drama and performance studies as a starting point, this essay looks at two eras of burlesque in Montreal—the 1940s-50s and 2012—tracing a shifting landscape of popular entertainment, politics, religion, and social attitudes toward female sexuality. There is a central question underlying this examination: Why burlesque? Why now (or, rather, again?). I argue that burlesque offers an archive that evokes a different, more glamorous history than the one passed down to women by second-wave feminism. Burlesque also provides an alternative to popular culture’s commodification of female sexuality, technology’s mediation of social life, and heteronormative culture’s privatization of sexuality, giving women—and men—a stage on which to make fun of our cultural fixation with sex and the female body. Both nostalgically looking back and eagerly reaching for the new, neo-burlesque repeats the past as it simultaneously reinvents it.
Publisher: University of Toronto Press

L'enjeu des communautés en sociomusicologie : Le cas du projet de recherche sur le développement des publics de la musique au Québec - Marcoux-Gendron, Caroline; Couture, Ariane; Gervasi, Flavia; Duchesneau, Michel (MUSICultures, 2014)

Nicole Lizée. Faisceaux imaginaires et cool media - McKinley, Maxime (La création musicale au Québec, 2014)

Interpreting Brazilianness: Reception and Representation in the Brazilian Music Scenes of Toronto and Montreal - Mercier, Catherine G. (Université de Toronto, 2014)
In Toronto and Montreal, Brazilian popular music performances constitute a context for intercultural encounter. Performances offer Brazilians the opportunity to present their culture of origin while emphasising their identification with it. The issue of representation is quite complex, however, due to the involvement of a majority of non-Brazilian musicians, audience members, artistic directors, producers, promoters, and journalists. This dissertation focuses on music reception and cultural representation and how these may influence each other after music has been decontextualised and recontextualised. I look closely at local non-Brazilian audiences possessing different degrees of familiarity with Brazilian music, and I demonstrate how cultural stereotypes influence their conceptions and expectations of Brazilian music, culture, and people. I argue that a desire for cultural difference and the exotic, encouraged by discourses of cultural diversity, influences the reception of performances. I suggest that, through the privileged gaze of non-Brazilian attendees, performances may be adjusted to correspond to audience fantasies of Brazil. Some non-Brazilians would like to become knowledgeable of, and even intimate with Brazilian culture, which would satisfy their desire to be cosmopolitan. However, pleasure frequently matters more to them than a nuanced understanding of Brazilian culture; this explains, I contend, why some Torontonians and Montrealers have become comfortable with essentialist and stereotypical representations. I examine how some non-Brazilian musicians, promoters, and band agents reinforce mythologies of Brazil to meet audience demands and sometimes to satisfy their own fantasies. I analyse the reproduction of similarly problematic discourses on Brazil in the presentations of Brazilian artists as both a form of autoexoticism and a particular type of tactical or strategic essentialism. Rather than to represent and understand Brazilian culture, I argue that, through local music performances, Brazilians and non-Brazilians in Toronto and Montreal interpret Brazilianness.

“We Paved the Way for Whatever Tolerance They Have in Their Lives”: An Interview with Michelle De Ville, “The First Door Bitch in Montreal” - Namaste, Viviane (Trans Activism in Canada: A Reader, 2014)
Centring the voices and experiences of trans identified people as experts on their own lives and agents of change, Trans Activism in Canada opens up a dialogue between scholars and community members in an effort to improve the lives of sex and gender variant people

Le voyage, la danse et la représentation des femmes dans la culture de grande consommation (1936-1947) - Savoie, Chantal (Les Cahiers de l'IREF, 2014)

Jazz, Diaspora and the History and Writing of Black Anglophone Montreal - Siemerling, Winfried (Critical Collaborations: Indigeneity, Diaspora, and Ecology in Canadian Literary Studies, 2014)

'The digital is everywhere': Negotiating the aesthetics of digital mediation in Montreal's electroacoustic and sound art scenes - Valiquet, Patrick Joseph (Université d'Oxford, 2014)
In this thesis I argue that the relationship between the increasing ubiquity of digital audio technologies and the transformation of aesthetic hierarchies in electroacoustic and sound art traditions is not deterministic, but negotiated by producers and policy-makers in specific historical and cultural contexts. Interviews, observations, and historical data were gathered during sixteen months of ethnographic fieldwork in the Canadian city of Montreal between 2011 and 2012. Research was conducted and analysed in collaboration with a transnational group of researchers on a programme of comparative research that tracked global changes to music and musical practice associated with digital technologies. The introduction presents Montreal as a rich ecology in which to track struggles for aesthetic authority, detailing its history as a key site of electroacoustic and sound art production, and its local positioning as a politically strategic 'hub' for the Canadian culture industry. Core chapters examine the specific role of digital mediation in the negotiation of electroacoustic and sound art aesthetics from multiple interlocking perspectives: the recursive relationship between technological affordances and theories of mediation; the mobilisation of digital technologies in the delineation of cultural, professional and generational territories; the political contestation of digital literacies and pedagogies; the articulation of the digital's opposition with analogue in the construction of instruments and recording formats; and the effects of the digital on the dynamics of genre and genre hierarchies. The concluding chapter offers a critique of the notion that digital mediation has shifted the balance between the normative and the generative dimensions of genrefication in the scenes in question, and closes by suggesting how a better understanding of this shift at an empirical level can inform an ongoing rethinking of the interaction between technology and aesthetics among scholars, policy makers, and musicians.

Native Classical: Musical Modernities, Indigenous Research Methodologies and a Kanienkéha (Mohawk) Concept of Non:wa (Now) - Witzleben, John Lawrence (Université du Maryland, 2014)
In this dissertation I explore how Indigenous methodologies that foreground cultural advocacy, revitalization, and education can be articulated using Indigenous language and cultural metaphor in research on North American Indian composers. Toward this end, I apply the Kanienkéha (Mohawk) concept of "non:wa" or "now" that also refers to three modes of perception–the now of the past, the present, and the future–toward understanding the intersection of innovation and tradition in classical Native music. This research joins the existing discourse that critiques binary oppositions separating Indigenous tradition (as past) and innovation (as present and future). Through interviews, fieldwork, and musical analysis, I illustrate Native values of interconnectedness, relationality, continuity, politics, and soundscapes in the processes of Native composition as well as the resultant works, I explore how these, in turn, may be understood through the application of Indigenous research techniques. In collaboration with a cohort of contemporary musicians, I look primarily at two Navajo composers–Raven Chacon and Juantio Becenti–and examine my own work as a composer, performer, and ethnomusicologist of Kanienkéha descent to explore the following questions: How can the topic of classical Native music best be served by using Indigenous methodologies in fieldwork, research, and representation and What is classical Native Music and is it different from other contemporary classical music styles? Drawing on the teachings of Indigenous dotahs (elders/teachers), the scholarship of ethnomusicologists, and examining oral and written tradition while using language and cosmology as cultural metaphors, I present a variety of possibilities for looking at Indigenous music through Indigenous eyes. Rather than offering a set of conclusions, I offer a set of tools for discussion and reflection: 1) how we might understand a definition of classical Native music; 2) how we are part

Layers of creativity in composition, rehearsal and performance: Nicole Lizée and the Kronos Quartet - Bayley, Amanda; Lizée, Nicole (2013)

Le son tactile ou la sensorialité excentrique dans les performances solos de Magali Babin - Abenavoli, Lorella (Circuit : musiques contemporaines, 2013)
How can the ephemeral touch of a caress become an aesthetic object? How can a fingernail scratching the mineral surface of a sheet of schist become music? How can intimate tactile experience become the scene of a collective artistic ritual? How does Magali Babin turn electronic sound into a medium for eccentric sensoriality? This article takes us into one region of Magali Babin’s artistic practice: the tactile world of sound that she uses in her solo performances. Author of a polymorphic sonic oeuvre, Magali Babin is a Quebec artist, performer, and composer whose artistic practice has incorporated sonic installations for the past two years. She is a key figure in Montreal’s alternative audio art, “edgy” improvisation, and experimental music scenes, moving freely among cutting-edge artistic categories.
Keywords: Magali Babin; art audio; art haptique; audio art; device; dispositif; eccentric sensoriality; electronic; haptic art; improvisation; performance sonore; sensorialité excentrique; sonic performance; électronique

Enjeux culturels et sociaux de la circulation de la chanson J’attendrai dans les années 1940 - Beaudet, Simon-Pierre; Savoie, Chantal (Mens. Revue d'histoire intellectuelle et culturelle, 2013)
Cette analyse aborde le cas singulier de la circulation de la chanson J’attendrai dans la culture des années 1940, dont l’analyse des variantes permet de cerner les rapports mouvants d’une chanson aux genres chansonniers et musicaux, aux goûts et aux pratiques du public, ainsi qu’à leur ancrage au sein des champs culturels nationaux. Elle permet même, parfois, de sonder les modalités de l’évolution des modèles des rapports sociaux entre les sexes présents dans différentes versions. Ce sont ainsi autant les enjeux artistiques, culturels, sociaux et intimes à l’oeuvre qui guident notre analyse de ce cas de transfert culturel, que le repérage de vecteurs permettant de formuler une équation de la circulation culturelle des chansons à succès. , This article deals with the singular case of the circulation of the song J’attendrai in the 1940s. The analysis of the different versions of the song allows us to reveal the changing relationship between these versions and musical genres, the tastes and practices of the public, and the way they fit into national cultures. This analysis also allows us, in places, to explore the evolution of social relationships between genders as presented in the different versions of the song. This way, our analysis of this case of cultural transfer is guided as much by the artistic, cultural, social and intimate aspects of the song, as by a search for the vectors explaining the cultural circulation of a successful song.
Keywords: chanson; féministe; musicologie

Providing the Taste of Learning: Nadia Boulanger’s Lasting Imprint on Canadian Music - Boivin, Jean (Intersections: Canadian Journal of Music / Intersections : revue canadienne de musique, 2013)
This article traces the rich Canadian legacy of the twentieth-century French musical legend Nadia Boulanger (1887–1979). Through teaching her more than seventy Canadian students, both French- and English-speaking, the renowned French pedagogue played a crucial role in the development of concert art music in this country from the 1920s, notably in Montreal and Toronto. Her numerous Canadian students went on to distinguish themselves as composers, teachers, performers, musicologists, theorists, administrators, and radio producers. Drawing on extensive archival and primary research, this study demonstrates the decisive impact Boulanger had on the development of musical styles and compositional practices in Canada in the last century.
Publisher: Canadian University Music Society / Société de musique des universités canadiennes

Du rôle de l'interprète-chercheur en création et re-création musicale : théories, modèles et réalisations d'après les cas de Kathinkas Gesang (1983-1984) de Karlheinz Stockhausen et de La Machi (2007-2011) d'Analía Llugdar - Breault, Marie-Hélène (Université de Montréal, 2013)
Cette thèse est basée sur une approche méthodologique hybride relevant de recherche-création en musique et de musicologie appliquée à l’interprétation. Elle s’intéresse à cette question centrale : « Quels rôles l’interprète-chercheur occupe-t-il dans un contexte de création ou de re-création (ou d’interprétation) musicale » ? Pour y répondre, l’auteure examine et rend compte du processus créateur et re-créateur de deux œuvres significatives dans son parcours en tant qu’interprète, soit Kathinkas Gesang als Luzifers Requiem (1983-1984) de Karlheinz Stockhausen et La Machi, rituel pour flûtes, électronique et regards (2007-2011) d’Analía Llugdar. Le travail de ces œuvres mixtes qui comportent toutes deux une dimension théâtrale tout en mettant en scène des personnages instrumentaux l’amène aussi à traiter des problématiques de l’appropriation de l’œuvre par l’interprète-chercheur et de la liberté de celui-ci face aux œuvres présentant un haut degré de déterminisme notationnel. La première partie situe les contextes disciplinaires et théoriques des recherches de l’auteure. Le premier chapitre permet de comprendre comment s’exerce la recherche de l’interprète en musique et de situer les différentes modalités dans lesquelles ce type de recherche s’effectue. Le deuxième chapitre explique les notions d’interprétation, d’improvisation et de composition et il situe l’interprète par rapport à ces trois champs d’activités. L’auteure y compare aussi les modes créatifs du théâtre à ceux de la musique tout en s’intéressant aux divers types d’authenticité inhérents au travail d’interprétation. Le troisième chapitre pose le principal angle d’investigation et d’analyse adopté dans cette thèse, soit celui du timbre instrumental. La deuxième partie porte sur Kathinkas Gesang de Stockhausen. Le quatrième chapitre présente une chronologie récapitulative des différentes grandes périodes d’appropriation de l’auteure. Le cinquième chapitre présente et met en contexte le symbolisme du cycle Licht, die sieben Tage der Woche (1977-2003), dans lequel Kathinkas Gesang s’insère. Le sixième chapitre est voué à une analyse du symbolisme attribué au timbre des principaux instruments que l’on retrouve dans Licht. Le septième chapitre évalue l’impact de la présence des interprètes dans le processus compositionnel chez Stockhausen tout en traitant de la question du casting dans Licht. Le huitième chapitre s’articule en un lexique timbral présentant une exégèse des techniques de jeu employées dans Kathinkas Gesang pour produire divers types de timbres. La troisième partie porte sur La Machi d’Analía Llugdar. Dans le neuvième chapitre, l’auteure présente la structure générale de l’œuvre et son synopsis et elle traite du rôle qu’elle a joué dans le processus de création de cette œuvre. Le dixième chapitre prend la forme d’un lexique timbral présentant une exégèse des différentes techniques de jeu employées dans l’œuvre pour produire divers types de timbres. Dans la conclusion, trois sphères d’action et six rôles-types de l’interprète-chercheur en création et en re-création musicale sont identifiés. De plus, des réponses aux problématiques de l’appropriation de l’œuvre et de la liberté de l’interprète sont apportées. L’auteure y suggère également des pistes de réflexion pour la recherche- création en musique et elle y présente les principales retombées de la thèse.
Accepted: 2014-01-16T17:36:59Z

Ginette Reno - Chanonat, Michelle (Éditions des Intouchables, 2013)
Ginette Reno est l'une des plus grandes chanteuses de toute l'histoire du Québec. C'est aussi la personnalité dont on a le plus parlé au cours des cinquante dernières années. Ses deux mille chansons, ses trente-huit albums et ses rôles au cinéma et à la télévision ont fait d'elle une véritable icône.

Parcours dans la programmation des concerts du Nouvel Ensemble Moderne - Couture, Ariane (Circuit : musiques contemporaines, 2013)
During its 25 years of activities, the nem has played 635 works by 374 composers at local concerts, public workshops or world tours. Collectively, these works cover most of the aesthetic tendencies of the music of the 20th century. However, it is possible to define the repertoire of the ensemble along two main axes: on one hand, works that have become “classics” of contemporary music, and, on the other hand, new works engaged in musical innovation. Thus, the policy for disseminating works through concerts established by Lorraine Vaillancourt introduces a new culture within the world of musical creation, based on the development of a repertoire of works from the 20th and 21st centuries.
Publisher: Les Presses de l’Université de Montréal
Keywords: Nouvel Ensemble Moderne; concert; musical programming; programmation musicale; repertoire; répertoire

La Bolduc : une pionnière de l’émancipation des femmes au Québec - Dupuis, Andréann (Magazine Gaspésie, 2013)
Un article de la revue Magazine Gaspésie, diffusée par la plateforme Érudit.
Publisher: Musée de la Gaspésie

« Donner le temps » : entretien avec Lorraine Vaillancourt - Goldman, Jonathan (Circuit : musiques contemporaines, 2013)
In an interview with Lorraine Vaillancourt, the founder and artistic director of the Nouvel Ensemble Moderne (nem) recounts her musical education in Quebec, Montreal and Paris, and goes on to describe the establishment and development of her ensemble, the choice of repertoire and her plans for the future.
Publisher: Les Presses de l’Université de Montréal
Keywords: Lorraine Vaillancourt; Nouvel Ensemble Moderne; contemporary music ensemble; direction musicale; ensemble de musique contemporaine; musical conducting

Auditeurs en exil : le cas des Chiliens à Montréal et leur rapport à deux chansons emblématiques - Gonzalez, Laura Francisca Jordán (Volume !. La revue des musiques populaires, 2013)
Cet article examine l’expérience des auditeurs chiliens exilés à Montréal, se concentrant spécifiquement sur leurs écoutes pendant la dictature militaire (1973-1989). Issus d’une méthodologie mixte qui combine l’histoire orale et l’analyse musicale, les résultats de cette recherche musicologique révèlent la place primordiale que l’audition musicale eut chez les exilés dans la reconstruction d’un lien avec leur pays d’origine, ainsi que dans le développement du mouvement de solidarité avec le peuple chilien. L’article explique, d’abord, le déploiement des goûts musicaux et identifie les répertoires canoniques qui demeurent au centre des écoutes. Ensuite, il aborde le rôle de l’usage des enregistrements en vinyle et cassette, et de la radio dans la diffusion des musiques. Enfin, les deux dernières sections explorent les significations associées aux pièces musicales ‘Gracias a la Vida’ et ‘Vuelvo’, mettant en relief la complexité de la réception en ce qui concerne la construction des identités culturelles, le récit des histoires personnelles et communautaires.
ISBN: 9782913169340 Number: 10 : 1 Publisher: Éditions Mélanie Seteun
Keywords: bootleg / piratage / contrefaçon; cassette / bande magnétique; communautés / minorités; migration / diaspora / exil; réception; écoute / auditeur

«Vous êtes tous des gagnants». “Étoile des aînés” et le vieillissement réussi au Québec - Grenier, Line; Valois-Nadeau, Fannie (Recherches sociologiques et anthropologiques, 2013)
Cet article s’intéresse à “Étoile des aînés”, un concours de musique réservé aux citoyens canadiens de 65 ans. Organisé et commandité par Chartwell, le plus gros réseau de résidences pour personnes âgées au Canada, ce concours vise à « célébrer le talent des retraités ». Fruit d’un projet pilote réalisé sous le mode d’une ethnographie multi-sites, l’étude explore comment “Étoile des aînés”, en tant qu’événement sis à l’intersection de la musique, des médias et du marché en pleine expansion de l’habitation pour aînés, met en évidence des articulations particulières du “bien vieillir” au Québec. Nous proposons qu’ “Étoile des aînés” agit comme une médiation du “vieillissement réussi”, comme une forme distincte du “bien vieillir”, en insistant sur les enjeux que pose la mise à l’épreuve publique du vieillissement. Nous y examinons deux modalités qui confèrent au vieillissement réussi un caractère collectif : l’expérience publique et l’engagement partagé. Ce concours-spectacle est un terrain privilégié pour comprendre les manières dont le vieillissement actif se déploie hors des domaines de la santé et de la sécurité.
ISBN: 9782930207735 Number: 1 Publisher: Université catholique de Louvain (Unité d’anthropologie et de sociologie)
Keywords: concours musical; culture populaire; engagement partagé; résidences pour aînés; vieillissement actif; vieillissement réussi; visibilité; Étoile des aînés

La construction sociodiscursive de l'image médiatique de la drag-queen Mado Lamotte. Les frontières de la transgression sociale - Laberge, François (Université Laval, 2013)
Selon la perspective interactionniste de la communication développée par Goffman (1973a, 1973b), l’image qu’un individu a de lui-même et qu’il tente de projeter sur les autres se construit au cours de l’interaction en fonction de représentations socialement partagées. Adoptant cette approche théorique, ma recherche vise à identifier, dans les interventions médiatiques de la drag-queen Mado Lamotte, les procédés discursifs qui participent à la construction de son image publique. L’analyse portera sur les actes de parole potentiellement menaçants (Brown et Levinson, 1987) et à leur amplification (Kerbrat-Orecchioni, 1990). Le corpus est constitué de 29 apparitions télévisées principalement extraites d’émissions de divertissement. La méthode d’analyse du discours (Charaudeau et Maingueneau, 2002) a permis de dégager les différents actes de parole menaçants (Venderveken, 1988) ainsi que les types de procédés par amplification (Vincent, Laforest et Turbide, 2008). L’analyse révèle trois dimensions de transgression sociale dans le modèle de construction de l’image de la drag queen : les normes interactionnelles, la frontière entre les domaines public et privé et l’identité de genre.
Accepted: 2018-04-19T21:50:05Z

Construire le corps, construire la star : une agentivité à l'œuvre dans deux clips de Marie-Mai - Labrosse, Claudia; Melançon, Johanne (Chanson et performance. Mise en scène du corps dans la chanson française et francophone, 2013)
La moustache de Georges Brassens, la robe noire d’Edith Piaf, les paillettes de Claude François, les cheveux de Dalida… Les chanteurs ont un corps indissociable de leurs chansons, et ce livre s’intéresse précisément à la présence physique de la musique populaire, à sa performance sur scène et sur disque. Si le dualisme historique entre le corps et l’esprit a eu tendance, en France, à inluencer la réception de la chanson en attribuant plus de prestige à la modestie d’un Brassens qu’à la séduction démonstrative d’un chanteur de ‘variétés’, cet ouvrage est l’occasion de revenir sur cette opposition et de la nuancer, en identiiant les artistes qui ont su l’ignorer ou la contester. En légitimant l’étude de la performance (au sens de mise en scène du corps), cette étude met sur un pied d’égalité des genres aussi différents que la chanson ‘à textes’, le rock, le disco, le zouk ou le cabaret, et recadre les études sur la chanson loin de l’analyse de paroles. Il démontre, notamment, qu’en tant que véhicule de la chanson, le corps du chanteur reflète des a priori sociaux sur les rapports entre physique et séduction, genre et sexualité, apparence ethnique et identité, artiice et authenticité. Cet ouvrage est le fruit d’une collaboration entre chercheurs de GrandeBretagne, des États-Unis, du Canada, de Nouvelle-Zélande et de France, et dont la qualité commune est une fraîcheur d’analyse pluridisciplinaire inspirée des études culturelles. Observant les corps de chanteurs et chanteuses en France, aux Antilles et au Québec, ce livre offre une rélexion comparatiste sur les codes esthétiques en vigueur dans chaque contexte national, et observe les tensions sociales, sexuelles et identitaires qui sous-tendent la performance musicale.

Cross-dressing to Backbeats: An Exploration of the Practices, Wo/men Producers, and History of Electroclash - Madden, David (Université Concordia, 2013)
This research-creation dissertation focuses on the emergence of electroclash as a dominant form of electronic dance music in the late 1990s and early 2000s. Electroclash combines the extended pulsing sections of techno, house and other dance musics with the trashier energy of rock and new wave. The genre signals an attempt to reinvigorate dance music with a sense of sexuality, personality and irony. Electroclash also emphasizes, rather than hides, the European, trashy elements of electronic dance music. This project addresses the following questions: what is distinct about the genre and its related practices, both in and out of the studio? Why do rock and electro come together at this point and in this way? Why is electroclash affectively powerful for musicians, audiences and listeners? And, what does the genre portend in terms of our understandings of the politics of electronic music? The coming together of rock and electro is examined vis-à-vis the ongoing changing sociality of music production/distribution and the changing role of the producer. Numerous women, whether as solo producers or in the context of collaborative groups, significantly contributed to shaping the aesthetics and production practices of electroclash, an anomaly in the history of popular music and electronic music where the role of the producer has typically been associated with men. These changes are discussed in relation to the way key electroclash producers often used a hybrid approach to production involving the integration of new(er) technologies, such as laptops containing various audio production software with older, inexpensive keyboards, microphones, samplers and drum machines to achieve the ironic backbeat laden hybrid electro-rock sound.

In and out of the studio - McCartney, Andra (Université Concordia, 2013)
In and out of the studio was a collaborative multimedia project which aimed to examine and document the working methods of several female sound producers, from a variety of media (such as radio, film sound, television, hypermedia, performance art) and in different institutional contexts. The website, which is compiled in this document, was one element in an effort to establish a greater sense of community among women sound producers who are separated by geographic space, occupation or disciplinary boundaries.

Faisceaux imaginaires et cool medias : This Will Not Be Televised de Nicole Lizée - McKinley, Maxime (Circuit : musiques contemporaines, 2013)
The imagination of composer Nicole Lizée brings together disparate elements, largely drawn from cinema, philosophy, visual arts, and so-called popular music, with a pronounced penchant for the period from 1960-1980 and the ghostly effect thus conveyed. This article illustrates Lizée’s creative process through one of her characteristic works, This Will Not Be Televised (2005-2007), scored for DJ and seven instruments. Our analysis illustrates how the composer’s “beams of imagination” take form through a unique musical language, based here on a meticulously notated DJ part and extended through the instrumental ensemble, and which draws on cultural references, repetitive effects, and montages of juxtapositions and superpositions, and whose continuous form achieves cohesion through the use of repeats. In this way, the composer focuses on the connections that are generated in the memory and subjectivity of the hearer – the tabula rasa characteristic of McLuhan’s “cool” media.
Keywords: Nicole Lizée; This Will Not Be Televised; analyse; analysis; cool medias; tables tournantes; turntable; “cool” media

Notre Clémence. D'amour et d'humour - Pedneault, Hélène (Éditions de l'Homme, 2013)
Humoriste, poète, monologuiste, comédienne: Clémence DesRochers s'est constamment réinventée au cours de sa prolifique carrière. Prenant la parole au nom des gens d'ici, elle a tour à tour exprimé avec justesse les joies et les peines des ouvriers, des femmes, des laissés-pour-compte et des homosexuels. Chaque fois, ses mots nous ont touchés droit au cœur, nous faisant à la fois sourire et réfléchir. Ce livre rend hommage au parcours exceptionnel d'une auteure profondément humaine, accessible et chaleureuse qu'un prénom suffit à désigner. Redécouvrez Clémence, la femme, l'artiste, la peintre du quotidien qui n'a jamais cessé d'esquisser notre portrait.

„A Moncton“ von Marie-Jo Thério. Chiac in Literatur und Alltag [« À Moncton » de Marie-Jo Thério. Le chiac dans la littérature et la vie quotidienne] - Reinsberg, Franziska (Grin Verlag, 2013)
„C'est boring à soir“ - Vielfältiger und vermischter zeigt sich eine Sprache nur selten. Doch was ist das, was dort zu lesen ist? Das Ziel dieser Arbeit ist die Untersuchung der sprachlichen Strukturen dieser besonderen hybriden Sprachvarietät - dem Chiac, eine Varietät des akadischen Französisch, das im Osten Kanadas gesprochen wird.

Inégalités et minorisation des identités chez les femmes artistes dans la francophonie canadienne - Robineau, Anne (Nouvelles perspectives en sciences sociales : revue internationale de systémique complexe et d'études relationnelles, 2013)
Even if women artists are wishing for recognition of their work, independently from their gender, language and belonging to a cultural group, their practices conditions are sometimes linked to these statuses. Through a sociodemographic study of French Canadian artists, we will analyze more specifically the data on women artists. We will show that, even if they have a higher education than man, women artists usually are considerably less paid for their services. We will also try to understand if minorization processes of women from professional artistic francophone communities can explain some gender inequalities and how the production of identity discourses (women, francophonie, linguistic minority) reinforce tensions between art and the identity perspective.
Publisher: Prise de parole
Keywords: Artiste; Artists; Canadian Francophonie; femmes; francophonie canadienne; inequalities; inégalités; minorisation; minorization; women

La chanson à succès dans les années 1940. Une modernité culturelle par acclamation ? - Savoie, Chantal (Globe, 2013)
Dans le contexte de travaux plus larges portant sur l’histoire de la chanson à succès par l’analyse des préférences musicales des lectrices du Bulletin des agriculteurs dans les années 1940, nous nous intéressons ici aux éléments qui permettent de comprendre les modalités par lesquelles les goûts musicaux témoignent de l’émergence d’une modernité culturelle au Québec dans les années 1940. Deux postulats orientent notre perspective. Le premier consiste à supposer l’existence d’une modernité culturelle « populaire » qui transite par la forme, les supports et la technologie. Le second sonde la façon dont les thèmes intimes et la focalisation sur l’expression du sentiment amoureux marquent une transformation des valeurs et, surtout, explore les marques formelles et discursives qui portent ces valeurs dans la chanson à succès. , As part of a larger research project on the history of popular song, which analyzes the musical preferences of the female readers of the Bulletin des agriculteurs in the 1940s, this article focuses on those elements that allow for an understanding of the modalities by which these women’s musical tastes reflected the emergence of a cultural modernity in Quebec during that decade. Two basic premises orient my perspective on the subject. The first presupposes the existence of a “popular” cultural modernity based on form, equipment, and technology. The second explores both the way in which intimate themes and the importance given to expressions of love reflected a shift in values, as well as the formal and discursive markers that transmitted these values in popular song.

Feminism, Media Technologies, and Studio XX: An Interview with Kim Sawchuk - Sawchuk, Kim; Tripp, Stephanie (Media-N: Journal of the New Media Caucus., 2013)
Kim Sawchuk is a feminist media studies scholar and a founding member of Studio XX, a feminist-run new media arts collective based in Montreal. A professor in the Department of Communication Studies at Concordia University, she is the former editor of the Canadian Journal of Communication and co-editor of wi: journal of mobile media. Sawchuk’s work encompasses the roles of women in science and technology, as well as issues surrounding media technology access and use by women, elders, and immigrant communities. Her more recent research involves the use of mobile devices by older adults. During a Skype interview with guest editor Stephanie Tripp on March 22, 2013, Sawchuk discussed her collaboration in Studio XX, her research on women and technology, her work on mobile communications technologies, and her outlook on issues facing women working in new media today.

"The Cult of the Diva" – Rufus Wainwright as Opera Queen - Smith, Oliver C. E. (Transposition. Musique et Sciences Sociales, 2013)
The music of Rufus Wainwright has been afforded much critical acclaim thanks to the singer-songwriter’s understanding of Queer cultural history, and the candor with which he explores (homo)sexuality in his music. This case study seeks to examine his use of opera in particular, and how Wainwright uses the historical trope of the opera queen to incorporate his own queerness into music, thus asserting an authority of difference and challenging the dominant (hetero)norm constructions of masculinity in popular music. Wainwright disregards any cultural framework imposed by heternormativism, and reclaims the Orphic figure of operatic authority as one of queer power through this absence. By drawing on his own relationship with opera, Wainwright exploits the right this gives him by reinterpreting cultural history, and revising the pejorative stereotype that is an opera queen.
Number: 3 Publisher: Association Transpositon. Musique et Sciences Sociales
Keywords: Eurydice; Hallelujah; Jeff Buckley; Memphis Skyline; Rufus Wainwright; Waiting For A Dream; Want Two; diva; gay; heteronormativism; identity; masculinity; opera; queer; stereotype

Diane Dufresne - Villeneuve, Anne-Marie (Paroles de femmes, 2013)
Croyez-vous que chaque individu a le devoir de trouver sa vocation ? Vous trouvez-vous douée pour le bonheur ? Peut-on se préparer à la souffrance ? Avez-vous déjà regretté d'être née femme ? Y a-t-il des choses qui vous révoltent actuellement dans notre société ? Voilà un aperçu du type de questions qui ont été posées à nos cinq personnalités publiques. Des questions qui demandent temps et réflexion, mais ô combien nécessaires pour faire le point sur le chemin parcouru et pour porter un regard philosophique sur l'avenir.

The Fiddlers of James Bay: Transatlantic Flows and Musical Indigenization among the James Bay Cree - Wilkins, Frances (MUSICultures, 2013)
Fiddle music and dancing have formed a major component of the social lives of the Algonquian First Nations Cree population living in the James Bay region of Ontario and Québec since the instrument and its associated repertoire were introduced to the region by British (and most notably Scottish) employees of the Hudson’s Bay Company who travelled across the Atlantic on ships from the late 17th to the 20th century. Based on archival research and ongoing fieldwork in the region since 2011, this article aims to explore this transatlantic musical migration from the British Isles to James Bay and the reshaping of Scottish fiddle music and dance through indigenization and incorporation into the Cree cultural milieu. By examining this area of cultural flow, the article seeks to engage with current themes in ethnomusicology on the subject and add to the growing body of knowledge surrounding them.

Innu nikamu - L’Innu chante. Pouvoir des chants, identité et guérison chez les Innus - Audet, Véronique (Presses de l'Université Laval, 2012)
Le présent ouvrage porte sur l’expression musicale populaire contemporaine des Innus du Québec et du Labrador (Canada). Les chants et musiques innus sont abordés dans une perspective d’affirmation identitaire et de guérison sociale liées aux processus de décolonisation et de revalorisation de la culture. L’ouvrage concerne plus précisément les Innus des communautés de Uashat mak Mani-utenam et d’Ekuanitshit situées sur la côte nord du golfe du Saint-Laurent. La création et la diffusion de chansons populaires en langue innu-aimun sont devenues depuis peu un phénomène très important dans la plupart des communautés innues. Ces chansons s’inspirent à la fois des modes traditionnels de relation au son et au monde, de la tradition de chants chrétiens en langue innu-aimun ainsi que des musiques de violoneux, country, folk, rock et des divers courants actuels. Malgré ces multiples influences, elles révèlent une attitude musicale propre aux Innus, en continuité avec un mode d’être ancestral, où le chant confère du pouvoir sur soi-même et dans le monde environnant. Ancrées dans l’expérience contemporaine, ces musiques sont des agents de transformation qui prennent aussi part au processus de guérison de l’être innu.

Why do the Innu Sing Popular Music? Reflections on Cultural Assertion and Identity Movements in Music - Audet, Véronique (Aboriginal Music in Contemporary Canada: Echoes and Exchanges, 2012)

Maryvonne Kendergi (1915-2011) : hommage et mémoire - Bail, Louise (Circuit, 2012)
Publisher: Les Presses de l’Université de Montréal

L'extase figurative : incarnation du Verbe dans l'espace scriptural (une analyse du Cantique d'actions de grâce ou Chant d'amour de Dina Bélanger) - Bergeron, Carlos (Université du Québec à Chicoutimi, 2012)
En 1924, les supérieures de la communauté des Jésus-Marie, à Sillery (Québec), demandent à Dîna Bélanger (1897-1929), Mère Marie Sainte-Cécile de Rome alors supposément aux portes de la mort, d'écrire son autobiographie qu'elle intitula Cantique d'actions de grâces ou Chant d'amour. C'est ce texte mystique écrit par obéissance, inachevé et dans lequel une énonciatrice multiplie les procédés rhétoriques pour faire valoir son droit à la sainteté, sainteté qu'elle lie à une écriture missionnaire ayant l'étonnant pouvoir de sauver des âmes, qui constitue l'objet de la présente thèse. L'originalité du texte analysé réside surtout dans la combinaison qu'il propose : autant la volonté d'inscrire une Parole de Dieu que l'étude des paramètres énonciatifs par lesquels l'énonciatrice en vient à en proposer un équivalent langagier, dans un cadre scriptural clamant son appartenance à l'autobiographie, sont des éléments nous assurant des assises pertinentes. Les notions théoriques créées pour rendre compte du fonctionnement d'une écriture prenant le pari de figurer l'indicible sont relatives à la « transcendance » comme principe actif présidant à l'encodage comme au décodage du texte mystique: «l'extase figurative », c'est-à-dire la prise en charge d'une insurmontable absence entre le langage et ce à quoi il réfère dans un cadre discursif où il s'agit souvent de donner des mots à la Parole de Dieu (l'indicible), et « l'indice trans », fonction imputée à une figure obligeant une interprétation de son énonciation au détriment de son contenu qui semble irrécupérable, nous conduisent précisément à théoriser une lecture originale du Cantique de Dina Bélanger. Ainsi, la rhétorique comme champ disciplinaire nous permet de rendre compte du mode de fonctionnement du texte analysé que nous avons divisé en trois phases complémentaires. La première phase est constituée d'une introduction (« Loués soient à jamais Jésus et Marie ») dans laquelle, d'une part, la narratrice explique la genèse de son acte scriptural : il s'agit de répondre à la volonté divine; d'autre part, elle cible les principaux objectifs de ce travail qu'elle s'apprête à accomplir. La seconde phase, soit les chapitre I à XIX (pp. 41-192), construit le portrait d'une sainte qui est supposément digne d'être le messager d'une « voix » entendue intérieurement; ce portrait est organisé par la narration de certains faits biographiques auxquels Dina accorde un traitement qui souscrit, grâce à l'alternance de deux isotopies principales (terrestre et spirituelle), à l'établissement d'une polysémie inductrice des premiers balbutiements d'un effet de « transcendance », d'où une possible diffusion de la « Parole », mais dans l'optique où l'énonciatrice, piégée par sa « tiédeur » humaine (son manque de foi), ne fait ici que « donner la parole à la Parole » afin de sanctionner sa propre prédestination. La troisième phase est constituée de deux parties complémentaires que nous avons intitulées «Abandon», débutant le 15 août 1924 pour se terminer le 25 janvier 1925 (essentiellement les chapitres XX et XXI, pp. 193-208) et «Message», ce journal spirituel resté inachevé (les chapitres XXII à XLVI, pp. 209-391), qui illustre l'entrée graduelle de l'énonciatrice dans ce qu'elle nomme la « Trinité », c'est-à-dire un espace « fabuleux » (relatif à la fable) où le Verbe est incarné dans l'espace scriptural par une sainte organisant effectivement son discours pour un lectorat composé de religieux tièdes qui doivent être persuadés de cette sainteté, puisque il en va du salut de toutes les âmes (la reconnaissance de la sainteté de Dina, sans preuve, supposant le passage de la tiédeur à la ferveur). La narratrice, substituée, donne alors la Parole au lecteur. Cette troisième phase du Cantique, dans laquelle l'alternance des isotopies cède sa place à la substitution de l'une par l'autre, impose la dominance du thème spirituel et, dans le contexte, la poétisation de l'écrit qui lui est indissociable. Cette étape ultime, qui est néanmoins représentative de tout cheminement mystique « canonique », crée le sentiment que la narratrice s'est libérée de tous ses liens terrestres et que son écriture est Union en acte. La transition de la « Parole » au « Verbe », produit d'un renversement nous faisant passer d'un univers plutôt factuel (seconde phase) à un monde généralement fabuleux (troisième phase), nous amène à analyser l'évolution suivante : de simples faits biographiques acquièrent rétrospectivement la possibilité de prendre une envergure poétique de par cette capacité qu'a une figure de « contaminer » l'énoncé dont elle fait partie. Finalement, les lecteurs idéals du Cantique, ces religieux plutôt tièdes par rapport à la narratrice, font à leur tour un acte de foi en prenant la parole (Parole) dans le paratexte afin de faire valoir le droit à la sainteté de l'énonciatrice. Leurs commentaires sont en grande partie relatifs au texte qu'ils jugent souvent comme un élément de preuve de cette sainteté que, comme Dieu, ils souhaitent pour Dina. Ils seraient prêts à la soutenir devant le Pape qu'une convention fait le représentant de Dieu sur Terre.

The Vocal Music of Ana Sokolović: Love Songs for the Twenty-First Century - Bernstein, Tamara (Circuit, 2012)
Enchanted by the vocal music of Serbian-born Canadian composer Ana Sokolović, Tamara Bernstein visited the composer at her home in Montreal. Sokolović’s music draws on several sources, including the theatrical world and the culture of the Balkans. The extended vocal techniques in Sokolović’s music are rooted not in the avant-garde music of the twentieth century, but in the oral traditions and poetic voice of Serbia. It seems that the more the composer returns to her cultural roots, the more she embraces the universality of the human soul.
Publisher: Les Presses de l’Université de Montréal

Life notations of Daisy Sweeney: reflections of othermothering, musicianship and Montreal - Campbell, Arlene (Université York, 2012)
The life story of Mrs. Daisy Sweeney, an African Canadian native of Montreal, Quebec, helps fill a void in the historical documentation of Montreal Blacks (especially female elders). Of particular significance is her prominence as a music educator and othermother during her life. The current literature on African Canadian othermothering experiences is not synonymous with both White or African American females and inclusion of their voices in academic, as well as mainstream spaces, is virtually non-existent. This dissertation asks: What did it mean to be a first generation 'Negro' working class bilingual female in a largely hostile White francophone Quebec metropolis in the early 20th Century? How can her narratives help shape and inform life history and African Canadian othermothering research? My sojourn with Mrs. Daisy Sweeney referenced African centered epistemology in my conceptual understanding of herself and community mothering. Capturing her conversations meant engaging with multiple methodologies articulated through African oral traditions, life history, archival canons and interdisciplinary inquiries. It is striking to note that there were not only certain tensions associated with memory loss and physical limitations (prompted by the aging process) that destabilized and enriched our 'interactive' communication, but also revealed a rupture and reversal of the participant/researcher dynamic. In spite of blatant racial discrimination that plagued Montreal's Black communities during that time, Daisy Sweeney fulfilled a life-long dream and taught hundreds of children the canon of classical piano for over 50 years. She lived her voice through her music, finding ways to validate her own identity and empowering others in the process. She used the musical stage as her platform to draw invaluable connections between race, gender, language and social class. Daisy Sweeney's generation of othermothers is dying out and, as the carriers of culture, the urgency to tell their stories must be emphasized. The account respects, reclaims and reflects those voices. It is time to write in African Canadian female elders and diversify the exclusionary genre of life history and archival research.

The Role of Music in the Quebec Sephardic Community - Cohen, Judith R. (Contemporary Sephardic Identity in the Americas: An Interdisciplinary Approach, 2012)

De l’ombre à la lumière : fragments pour une analyse des trois premiers albums d’Ariane Moffatt - Doyon, Noémie (Canadian Folk Music, 2012)

Femme-acrobate, femme-automate : Le Fil de Camille et Le Cœur dans la tête d'Ariane Moffatt - Doyon, Noémie (Chanson et performance. Mise en scène du corps dans la chanson française et francophone, 2012)
La moustache de Brassens, la robe noire d'Edith Piaf, les paillettes de Claude François, les cheveux de Dalida ... Les chanteurs ont un corps indissociable de leurs chansons. Ce livre s'intéresse à la présence physique de la musique populaire, à sa performance sur scène et sur le disque. Voici observées les tensions sociales, sexuelles et identitaires qui sous-tendent la performance musicale

La famille Daraîche. Une page du country au Québec - Dumas, Carmel (Éditions Pratiko, 2012)
Lorsque la barmaid du Rocher Percé que fréquente la diaspora à Montréal se met à chanter avec les portiers pour secouer la nostalgie des clients, commence à s'écrire une page de la petite histoire du Québec et de sa populaire chanson country. Les trois disques d'or enregistrés au début des années 70 par les Gaspésiens Julie Daraîche, Bernard et Fernand Duguay ont donné au répertoire des chansons immortelles et c'est sur cette base solide que s'est bâtie la légende de la Famille Daraîche, ralliant sur quatre décennies et deux générations l'authenticité de Julie, la musicalité de Paul, l'énergie de Dani et la douceur de Katia. Leur histoire en est une d'audace, de solidarité et d'appartenance qui rejoint et inspire depuis plus de 45 ans les artistes et le public qui retrouvent en eux leurs propres racines.

Forestier selon Louise. Pas d'choker pas d'collier - Forestier, Louise (Éditions La Presse, 2012)
De Louise Belhumeur, née à Shawinigan, élevée à Montréal et étudiante à l'École nationale de théâtre elle est devenue Louise Forestier, grande artiste ayant louvoyé toute sa vie entre chanson, théâtre, cinéma, radio et télévision. Dans son autobiographie qu'elle qualifie d'autoportrait, Louise Forestier se raconte avec générosité et franchise. Ses rencontres, ses triomphes et ses défaites ainsi que les moments déterminants de la vie d'une femme sensible et d'une artiste passionnée. Celle qui a connu le succès avec entre autres l'Osstidcho, Demain matin, Montréal m'attend, Starmania, IXE-13, Les Ordres et son rôle dans Le Négociateur a su toujours se renouveler avec audace, humour, créativité et authenticité. Nous la suivons de son enfance, au sein d'une famille pas toujours facile, à ses amours tumultueuses, à son état de mère absente, de femme déterminée à vaincre la dépression, à celle qui a vécu des heures de gloire professionnelle nombreuses. Un voyage au centre des événements culturels qui ont marqué le Québec et notre histoire collective et qui incluent des gens comme Robert Charlebois, Yvon Deschamps, Mouffe, Ginette Reno, Les Cyniques, Isabelle Boulay et Zachary Richard. Un récit touchant, dans lequel la femme artiste laisse libre cours à ses pensées, à ses souvenirs et à sa passion.

Introduction : la voix d’Ana Sokolović - Goldman, Jonathan (Circuit, 2012)
Publisher: Les Presses de l’Université de Montréal

Musical Robots and the Serbian Kolo: A Narrative Analysis of Ana Sokolović’s Géométrie sentimentale (1997) - Harman, Brian (Circuit, 2012)
Composer Ana Sokolović divided her instrumental work Géométrie sentimentale into large sections inspired by pure geometric shapes — Triangle, Cercle and Carré — describing these sections as three contrasting perspectives of the same musical materials. This article uses a narrative analytical approach as a lens through which to understand these distinct sections and the materials populating them. Inspired by Sokolović’s employment of musical objects in her compositions and by the extra-musical concepts inspiring many of her works, this analysis uses a collection of colourful robot toys as metaphors for the work’s materials. Three unique perspectives of these toys are described: in Triangle, the robots interact as characters on a dramatic stage; in Cercle, they peacefully coexist in slow motion; and in Carré new combinations of robot elements are abruptly juxtaposed against each other. The characteristics and interactions between these toys, as well as the various harmonic ‘masks’ that the composer has them wear, are helpful in understanding Sokolović’s harmonic structure, variation/transformation techniques, formal organization and rhythmic characteristics. The Serbian kolo is also shown as influential on the work, relating directly to the physicality and kinetics of the metaphorical robots.
Publisher: Les Presses de l’Université de Montréal

El cancionero judeoespañol en transición: Un estudio de dos compilaciones de mujeres sefarditas del siglo XX [Le répertoire de chansons judéo-espagnoles en transition : étude de deux compilations de femmes sépharades du XXe siècle] - Havassy, Rivka (Ladinar, 2012)

Different Folk: The Discreet Charm of Kate and Anna McGarrigle - Jelly-Schapiro, Joshua (American Quarterly, 2012)
Publisher: Johns Hopkins University Press

Diane Dufresne : muse en scènes - Lebrun, Barbara (Chanson et performance. Mise en scène du corps dans la chanson française et francophone, 2012)
La moustache de Georges Brassens, la robe noire d’Edith Piaf, les paillettes de Claude François, les cheveux de Dalida… Les chanteurs ont un corps indissociable de leurs chansons, et ce livre s’intéresse précisément à la présence physique de la musique populaire, à sa performance sur scène et sur disque. Si le dualisme historique entre le corps et l’esprit a eu tendance, en France, à inluencer la réception de la chanson en attribuant plus de prestige à la modestie d’un Brassens qu’à la séduction démonstrative d’un chanteur de ‘variétés’, cet ouvrage est l’occasion de revenir sur cette opposition et de la nuancer, en identiiant les artistes qui ont su l’ignorer ou la contester. En légitimant l’étude de la performance (au sens de mise en scène du corps), cette étude met sur un pied d’égalité des genres aussi différents que la chanson ‘à textes’, le rock, le disco, le zouk ou le cabaret, et recadre les études sur la chanson loin de l’analyse de paroles. Il démontre, notamment, qu’en tant que véhicule de la chanson, le corps du chanteur reflète des a priori sociaux sur les rapports entre physique et séduction, genre et sexualité, apparence ethnique et identité, artiice et authenticité. Cet ouvrage est le fruit d’une collaboration entre chercheurs de GrandeBretagne, des États-Unis, du Canada, de Nouvelle-Zélande et de France, et dont la qualité commune est une fraîcheur d’analyse pluridisciplinaire inspirée des études culturelles. Observant les corps de chanteurs et chanteuses en France, aux Antilles et au Québec, ce livre offre une rélexion comparatiste sur les codes esthétiques en vigueur dans chaque contexte national, et observe les tensions sociales, sexuelles et identitaires qui sous-tendent la performance musicale.
OCLC: ocn829707227
Keywords: France; Music; Popular music; Social aspects

Quand le rap dit la ville : perceptions sociolinguistiques des rappeuses de Montréal - Lesacher, Claire (Dynamiques sociolangagières de l’espace algérois. Discours et représentations, 2012)

Musique, immigration et intégration au Québec - Leyssieux, Florence (Université de Montréal, 2012)

Le plurilinguisme dans les cultures populaires, un terrain inexploré? L’étude du langage mixte du rap montréalais en guise d’exemple - Low, Bronwen (Kinephanos, 2012)

De la cuisine au studio - Lupien, Anna (Éditions du remue-ménage, 2012)
De la cuisine au studio explore les parcours de douze artistes issues de trois générations différentes : femmes signataires du manifeste Refus global en 1948, premières cinéastes qui ont œuvré à l’ONF dans les années 1970 et artistes médiatiques impliquées au Studio XX. À partir d’entrevues avec les artistes, Anna Lupien pose un regard sociologique sur l’expérience de créatrices qui ont investi l’art en tant qu’espace d’expression dans la sphère publique. De quelle façon ont-elles élaboré des stratégies créatives et par le fait même donné corps à des transformations sociales engendrées par le mouvement féministe, notamment en ce qui a trait à la conciliation travail-famille ? Comment ont-elles intégré des milieux artistiques qui ne leur étaient pas ouverts d’emblée ? Comment se sont-elles engagées pour le bien commun à travers leur parcours artistique ? Les histoires de ces artistes – Madeleine Arbour, Christine Brault, Mireille Dansereau, Dorothy Todd Hénaut, Stéphanie Lagueux, Bérengère Marin-Dubuard, Helena Martin Franco, Terre Nash, Anne-Claire Poirier, Françoise Riopelle, Bonnie Sherr Klein et Françoise Sullivan – témoignent des luttes inachevées du mouvement féministe et des brèches qu’elles ont pratiquées dans l’ordre des choses, suscitant des rencontres originales entre l’art et le politiqu

Crossdressing to Backbeats: The Status of the Electroclash Producer and the Politics of Electronic Music - Madden, David (Dancecult, 2012)
Addressing the international emergence of electroclash at the turn of the millenium, this article investigates the distinct character of the genre and its related production practices, both in and out of the studio. Electroclash combines the extended pulsing sections of techno, house and other dance musics with the trashier energy of rock and new wave. The genre signals an attempt to reinvigorate dance music with a sense of sexuality, personality and irony. Electroclash also emphasizes, rather than hides, the European, trashy elements of electronic dance music. The coming together of rock and electro is examined vis-à-vis the ongoing changing sociality of music production/distribution and the changing role of the producer. Numerous women, whether as solo producers, or in the context of collaborative groups, significantly contributed to shaping the aesthetics and production practices of electroclash, an anomaly in the history of popular music and electronic music, where the role of the producer has typically been associated with men. These changes are discussed in relation to the way electroclash producers Peaches, Le Tigre, Chicks on Speed, and Miss Kittin and the Hacker often used a hybrid approach to production that involves the integration of new(er) technologies, such as laptops containing various audio production softwares with older, inexpensive keyboards, microphones, samplers and drum machines to achieve the ironic backbeat laden hybrid electro-rock sound.

Choral, Public and Private Listener Responses to Hildegard Westerkamp's École - McCartney, Andra; McCarthy, Marta (Music and Arts in Action, 2012)
Hildegard Westerkamp's (1990) composition École Polytechnique is an artistic response to one of Canada's most profoundly disturbing mass murders, the 1989 slaying of fourteen women in Montreal, Quebec. Using the theoretical model, derived from Haraway, of the cyborg body, and analyzing the import of the mixed media (voices, instruments and electroacoustic tape) incorporated in the music, the authors examine the impact this work has had on some of those who have heard it and performed it, based on the responses of choristers and listeners in several studies. The authors explored how those who engaged significantly with the music, (including those who had no personal association with the actual events of the 1989 massacre), were able to make relevant connections between their own experience and the composition itself, embrace these connections and their disturbing resonances, and thereby experience meaningful emotional growth.
Accepted: 2012-11-14T10:25:30Z Publisher: University of Exeter

Cartographie de l’apprentie - Messier, Anne (Circuit, 2012)
La compositrice québécoise Ana Sokolović est d’origine serbe et plusieurs de ses oeuvres font référence à son pays d’origine, que ce soit par l’utilisation de mélodies et de rythmes traditionnels ou par des références culturelles. Pour approfondir son héritage serbe, l’auteure s’est entretenue avec la compositrice en mars 2012. L’article relate les paysages de son enfance et de son adolescence, l’environnement musical, culturel et politique de ses années d’apprentissage. Le portrait de sa vie familiale et de son quotidien nous permet de saisir des éléments constituants de sa personnalité d’artiste en devenir. Sa décision de s’établir à Montréal est explorée et elle raconte comment elle a pris conscience de son héritage slave.
Publisher: Les Presses de l’Université de Montréal

« J’aime quand on explose de joie ! » : entretien avec Ana Sokolović - Panneton, Isabelle (Circuit, 2012)
Lors d’un entretien réalisé par la compositrice Isabelle Panneton, Ana Sokolović discute de ses inspirations, de ses méthodes et de son rapport avec les interprètes de sa musique.
Publisher: Les Presses de l’Université de Montréal

Par les mains pour les yeux : les représentations de l'identité sourde au sein de performances artistiques de la scène montréalaise - Paradis Vigneault, Marie-Claude (Université Laval, 2012)
Ce mémoire s’appuie sur une recherche ethnographique réalisée principalement au sein de la communauté sourde de Montréal et tente de déceler les représentations de l’identité sourde au sein de performances artistiques de la scène montréalaise. Le but de cette recherche est d’inscrire la culture sourde dans les réflexions sociales et scientifiques portant sur l’expression identitaire de minorités culturelles par les arts. Afin de démontrer les liens à la fois théoriques et pratiques entre l’identité sourde et celles de minorités socio- politiques, telles que les Noirs, les gays, les femmes ou les Queers, cette étude s’appuie sur les concepts de performativité (Judith Butler), de performance (Clifford Geertz et Victor Turner) et de représentations (Stuart Hall et Serge Moscovici). Y seront également démontrées les relations entre ces notions, le vécu des sujets, leur agency et leur expression artistique.

Le pouvoir créateur d’Alfred et de Clémence - Roy, Julie; Fortier, Hélène (Revue de Bibliothèque et Archives nationales du Québec, 2012)

Sociologie et vecteurs de la popularité : l'mpact de la réception féminine sur la chanson québécoise des années 1940 - Savoie, Chantal (25 ans de sociologie française de la musique en France. Réflexivité, écoutes, goûts, 2012)

L'intuition de/dans l'œuvre de la compositrice québécoise Isabelle Panneton: un défi à la bipartition du genre - Stévance, Sophie (Le genre à l'œuvre, 2012)

La réalité socioprofessionnelle des musiciennes au Québec : un engagement vers l’écriture du féminin - Stévance, Sophie (Loin des yeux près du corps. Entre théorie et création,, 2012)

Polyrhythmic Dance Currents: Race Multiculturalism and the Montreal Dance Community - Templeton, Melissa (Université de Californie à Riverside, 2012)

Violet Archer's "The Twenty-Third Psalm" (1952): An Analytical Study of Text and Music Relations Through Fibonacci Numbers, Melodic Contour, Motives, and Piano Accompaniment - Wan, Jessica Jane (Université d'Ottawa, 2012)
This study explores text and music relations in Canadian composer Violet Archer's “The Twenty-Third Psalm” by analysing the text of Psalm 23, Fibonacci numbers, melodic contours, motives, and the role of the accompaniment. The text focuses on David's faith in God and his acceptance of God as his shepherd on earth. The four other approaches allow us to examine the work on three different structural levels: background through Fibonacci numbers, middleground through melodic contour analysis, and foreground through motivic analysis and the role of the accompaniment. The measure numbers that align with Fibonacci numbers overlap with some of the melodic contour phrases, which are demarcated by rests, as well as with the most important moments at the surface level, such as the emphasis on the word “death” through recurring and symbolic motives. The piano accompaniment further supports these moments in the text.
ISBN: 9780494866368
Keywords: Archer; Canadian music; Communication and the arts; Fibonacci numbers; Melodic contour; Motivic analysis; Music analysis; Psalm 23; Text and music relations; The Twenty-Third Psalm (1952); Theory; Violet

Wendat Song and Carnival Noise in the Jesuit Relations - Bloechl, Olivia (Native Acts: Indian Performance, 1603–1832, 2011)

'No So Komo Las De Agora' (I'm not like those modern girls): Judeo-Spanish Songs Meet the Twenty-First Century - Cohen, Judith R. (European Judaism, 2011)
The Judeo-Spanish song tradition has experienced many changes in recent years as it enters the 'world music' scene. Change, however, can be seen as a constant feature of the many aspects of Judeo-Spanish song and performance practice. Here, various genres are examined, together with some of the changes they have undergone in repertoire, style and context, and a selection of reactions to changes on the part of Sephardi Jews interviewed over several years. To a large extent, the repertoire has moved from the home to public representation, and is performed more by professional artists with no Sephardi background than by people from Sephardi communities, raising questions of appropriation and representation.

Selanikli Humour in Montreal: the Repertoire of Bouena Sarfatty Garfinkle (1916-1977) - Cohen, Judith R. (Judeo Espaniol: Textos satíricos judeoespañoles: de salonicenses o sobre salonicenses/Satirical Texts in Judeo-Spanish by and about the Jews of Thessaloniki, 2011)

Swinging in Paradise: The Story of Jazz in Montreal - Gilmore, John (Ellipse Editions, 2011)

National Affection: Céline Dion - Hurley, Erin (National Performance: Representing Quebec from Expo 67 to Celine Dion, 2011)
In National Performance, Erin Hurley examines the complex relationship between performance and national identity. How do theatrical performances represent the nation in which they were created? How is Quebecois performance used to define Quebec as a nation and to cultivate a sense of 'Quebec-ness' for audiences both within and outside the province? In exploring Expo 67, the critical response to Michel Tremblay's Les Belles Soeurs, Carbone 14's image-theatre, Marco Micone's writing practices, Cľine Dion's popular music, and feminist performance of the 1970s and 80s, Hurley reveals the ways in which certain performances come to be understood as 'national' while others are relegated to sub-national or outsider status. Each chapter focuses on a particular historical moment in Quebec's modern history and a genre of performance emblematic of the moment, and uses these to elaborate the nature of the national performances. Winner of the Northeast Modern Language Association's Book Prize, National Performance is sophisticated yet accessible, seeking to enlarge the parameters of what counts as 'Quebecois' performance, while providing a thorough introduction to changing discourses of nation-ness in Quebec

La musique des Chiliens exilés à Montréal pendant la dictature (1973-1989) : la création de musiques de la résistance politique et la réception des auditeurs dans l’exil - Jordan Gonzalez, Laura Francisca (Université de Montréal, 2011)
Cette étude musicologique aborde la musique pratiquée et écoutée par les Chiliens exilés à Montréal pendant la dictature (1973-1989), se concentrant sur l’histoire de la musique du point de vue des auditeurs. Quelles musiques participent à l’expérience d’exil et quel rôle accomplissent-elles? Comment les musiques accompagnent-elles le processus d’adaptation au pays d’accueil et comment aident-elles à construire un lien avec le pays d’origine? Ce sont quelques unes des questions qui ont guidé le développement de la recherche, dont la méthodologie est mixte et se concentre sur l’entrevue. Trois dimensions de l’histoire musicale y sont examinées. Premièrement, la contribution de la pratique musicale au mouvement de solidarité envers le peuple du Chili, notamment à travers la formation d’ensembles musicaux et l’organisation des peñas et des concerts. Deuxièmement, le rôle des musiques dans la construction d’une communauté culturelle chilienne, où différents discours sur l’identité nationale et politique sont négociés. Troisièmement, la présence des musiques dans les expériences individuelles d’exil, de déracinement et d’adaptation. Les genres de musique populaire les plus présents, soit la Nueva Canción Chilena et la Proyección Folclórica, ainsi que leurs enjeux des significations identitaires et politiques, font partie de la problématique du présent texte. La cueca, considérée la danse nationale, occupe aussi une place privilégiée de la discussion, due à la place importante qu'elle occupe dans la communauté chilienne de Montréal.

The role of folk, popular and improvisatory music in the lives of marginalised youth: rethinking music education for Canadian Inuit - Lane, David (2011)

Vers une approche interculturelle de l'enseignement de l'orchestre à cordes de la première secondaire - Laurin, Chantal (Université du Québec à Montréal, 2011)

Entretien avec Isabelle Panneton - Lefebvre, Marie-Thérèse (Les Cahiers de la Société québécoise de recherche en musique, 2011)
Sous forme d’entrevue, la compositrice se remémore les moments importants des cours d’analyse de Gilles Tremblay, plus particulièrement sa manière d’aborder le rapport de la poésie et de la musique, ainsi que son souci du traitement vocal, une approche qui se démarque par son caractère instinctif et sa vision organique des oeuvres. La compositrice parle également de sa propre approche de la poésie et présente quelques-uns de ses projets.
Publisher: Société québécoise de recherche en musique

La chanson country-western, 1942-1957 un faisceau de la modernité culturelle au Québec - Lefrançois, Catherine (Université Laval, 2011)
Cette thèse explore les liens entre le country-western produit au Québec entre 1942 et 1957 et la modernité populaire. À l’aide de l’analyse musicale et de l’histoire, ce travail de recherche tente de cerner la signification culturelle du genre au moment de son émergence. L’histoire du country-western débute au Québec avec le soldat Roland Lebrun, qui amorce en 1942 sa carrière sur disque. Il sera suivi de Paul Brunelle, de Marcel Martel et de Willie Lamothe, qui enregistrent chez l’une ou l’autre des deux compagnies généralistes établies à Montréal pendant les années 1940, Compo et RCA Victor. À mesure que le genre se structure, notamment grâce à la fondation de compagnies de disques spécialisées à partir de 1958, un discours sur l’authenticité du country-western se développe chez les artistes et leurs observateurs. Fondée sur une valorisation a posteriori des conditions qui caractérisent la période d’émergence du genre, qui s’étend de 1942 à 1957, l’authenticité insiste sur la continuité et la tradition. Ce discours, présent dès le milieu des années 1960, masque les aspects les plus modernes d’un genre qui, au moment où il émerge, n’est pas explicitement porteur de valeurs traditionnelles ou conservatrices. La voix country-western constitue un premier indice de modernité. La chanson country-western québécoise des années 1940 et 1950 structure dans un cadre musical des modificateurs paralinguistiques dont les deux plus caractéristiques, d’un point de vue générique, sont la nasalisation et le second mode de phonation. Véhicules de l’expressivité vocale, ces deux modificateurs du timbre sont coordonnés avec les paroles des chansons et avec la variation de paramètres musicaux, technologiques et phonétiques. Ils contribuent à la construction d’èthos spécifiques comme la tristesse, la solitude, la plainte et l’exubérance, et conservent dans le contexte discursif constitué par les enregistrements la signification expressive qu’on leur attribue dans la parole spontanée. C’est donc la voix parlée, quotidienne et ordinaire, qui fournit à l’auditeur le code culturel lui permettant d’en interpréter la signification. En ce sens, la chanson country-western incarne une certaine modernité populaire, redevable au code de la langue vulgaire partagée par le plus grand nombre. La modernité du country-western est aussi apparente dans sa popularité, qui se réalise à la fois dans son succès comme objet de consommation et dans sa proximité avec le public qui en détermine en partie le développement. Son recours particulier à la technologie, qui contribue à la création d’effets de spatialisation mais surtout à la mise en scène de l’intimité, le rattache aussi à la modernité. Enfin, le country-western témoigne d’une américanité certaine, assumée, et s’inscrit dans le déplacement du centre de gravité culturel, de l’Europe vers les États-Unis, qui marque la modernité. L’américanité du country-western, liée à ses origines mêmes, se renouvelle à la fin des années 1950 alors que le genre intègre le rock and roll.

De la cuisine au studio : le rapport public/privé interrogé au fil des parcours d'artistes québécoises de trois générations - Lupien, Anna (Université du Québec à Montréal, 2011)

Ethel Bruneau: Montreal’s Rhythm Tap Legend - Lys, Stevens (Dance Collection Danse, 2011)

Entre stabilité et mouvement : l'oscillation spatiale dans le diptyque "Want" de Rufus Wainwright - Mathieu-Lessard, Jeanne (Université Laval, 2011)
Ce mémoire propose l’analyse de chansons extraites du diptyque Want (formé des albums Want One et Want Two), de l’auteur-compositeur-interprète Rufus Wainwright, en regard des relations entre l’énonciateur et l’espace. La notion d’oscillation spatiale, définie en introduction, est au cœur de la situation de l’énonciateur et se déploie sous de multiples formes dans les cinq chansons à l’étude. « Oh What a World » et « I Don’t Know What It Is » sur Want One, « Hometown Waltz », « Memphis Skyline » et « Old Whore’s Diet » sur Want Two, ont été choisies pour la façon dont la relation à l’espace y agit de même que pour leur emplacement dans l’ensemble. La position de l’énonciateur mise en évidence dans chaque analyse s’inscrit au sein d’un parcours, que l’étude préliminaire du paratexte des albums aura d’ailleurs mis en évidence.

Performing ‘Judy’: The Creation and Function of Cover Personae in Popular Music in Rufus Wainwright's Judy Garland Concerts - O'Connell, Sam (Contemporary Theatre Review, 2011)

Lara Fabian. Toutes les femmes en elle - Patinier, Jérémy (Lulu Press, 2011)
Peu de chanteuses sont aussi multiples : auteur, compositeur, comédienne et bien sûr chanteuse, Lara Fabian est une artiste, au sens plein du terme : extrêmement sensible, vibrant pour son art, elle ne laisse pas de marbre ! Soit on l’aime, follement, comme les milliers de fans qui la suivent, soit on l'attaque, avec acharnement… Belgo-sicilienne de naissance et québécoise de cœur, elle est devenue en 25 ans de carrière (en 2011, soit plus de 12 millions de disques vendus) une star dans ses deux pays, puis en France et aussi en Russie et au Brésil… Retour sur un parcours en chansons, en portraits, tout en émotion, dans l’intimité de l’artiste et de son travail, de son entourage jusqu'à ses fans, mais aussi sur les zones d’ombre... Anecdotes, révélations.

La poétesse de l'ombre [entretien avec l'artiste sonore Nancy Tobin] - Siaud, Florent (Théâtre/Public, 2011)

"Give Me Aladdin's Lamp”: A Possible Perspective of Modernism - Ştefan, Angi (Musicology Papers, 2011)
Defining the differentiated semantics of new and novelty, reversing the dictum non nova sed nove into non nove sed nova, the author of the chamber cantata „Give me Aladdin’s lamp” is based on the rich experience of leading myriad of mid-century modernism. The investigation of the paradigms of new relationships between vocal and instrumental in creation of Dora Cojocaru, is directed in present at the chamber cantata for mezzo-soprano, brass quintet and percussion on lyrics by Emil & Dan Botta, Georg Trakl, Rainer Maria Rilke and Ady Endre (1998). The relations text - melody by their phenomenological reduction to fruitful combinations between poetic word - musical sound in Dora Cojocaru’s cantatas represent a stylistic-rhetorical subsumption of autochthonous and foreign experiences in promoting new compositional and interpretive skills meant for adaptation of appropriate musical expression in portraying contemporary aesthetic message. They are designed on the wide range of contemporary aesthetic values from the grotesque in nascendi to the absurd in morendi. As long as the Cantata Galgenlieder in der Nacht with lyrics by Christian Morgenstern (1995) is conceived at the grotesquely pole on the axis of the field of contemporary aesthetics, the Cantata Give me Aladdin’s lamp is designed in the sphere of the tragic. In the composer’s vocal and instrumental creation (and not only in them) the experiences of today’s musical composition and interpretation are rethought creatively, suggesting in perspective the permanence of modern horizons.

Give Me Aladdin’s Lamp”: A Possible Perspective of Modernism - Stefan, Angi (Musicology Papers, 2011)
Defining the differentiated semantics of new and novelty, reversing the dictum non nova sed nove into non nove sed nova, the author of the chamber cantata „Give me Aladdin’s lamp” is based on the rich experience of leading myriad of mid-century modernism. The investigation of the paradigms of new relationships between vocal and instrumental in creation of Dora Cojocaru, is directed in present at the chamber cantata for mezzo-soprano, brass quintet and percussion on lyrics by Emil & Dan Botta, Georg Trakl, Rainer Maria Rilke and Ady Endre (1998). The relations text - melody by their phenomenological reduction to fruitful combinations between poetic word - musical sound in Dora Cojocaru’s cantatas represent a stylistic-rhetorical subsumption of autochthonous and foreign experiences in promoting new compositional and interpretive skills meant for adaptation of appropriate musical expression in portraying contemporary aesthetic message. They are designed on the wide range of contemporary aesthetic values from the grotesque in nascendi to the absurd in morendi. As long as the Cantata Galgenlieder in der Nacht with lyrics by Christian Morgenstern (1995) is conceived at the grotesquely pole on the axis of the field of contemporary aesthetics, the Cantata Give me Aladdin’s lamp is designed in the sphere of the tragic. In the composer’s vocal and instrumental creation (and not only in them) the experiences of today’s musical composition and interpretation are rethought creatively, suggesting in perspective the permanence of modern horizons.

Le 'principe de contrainte stimulante' dans l'œuvre de la compositrice Isabelle Panneton - Stévance, Sophie (Médecine des arts, 2011)

Survivre aux naufrages - Thalie, Lynda (Éditions La Semaine, 2011)
Elle en a fait du chemin, la petite Lynda qui a débarqué au Québec après avoir quitté une Algérie à feu et à sang! De l'intégrisme religieux à la liberté d'être, nous découvrons le parcours de la jeune fille affranchie, la naissance de l'artiste, de la conférencière, de la femme et de la mère qu'elle est aujourd'hui.

La fille du Saint-Laurent - Thibeault, Fabienne (Éditions du Moment, 2011)
Fabienne Thibeault retrace les péripéties de sa légende familiale, aux sources de son ascendance canadienne française, dans le Charlevoix de son enfance. Fille de maçon, petite-fille de cultivateurs, fille de la ville, petite-fille de la campagne, elle relate le destin de ses grands-parents, oncles et tantes, nombreux cousins et cousines, tous incarnant avec force un peuple qui s'est forgé à travers une vie âpre, une foi simple et l'amour de la musique.Autour de la figure très aimée de son père, la chanteuse ressuscite le Québec d'autrefois, terre de pionniers, de mariniers et de bûcherons. Une ode à la nature et à des figures inoubliables. Plus tard ses parents s'installent dans les quartiers ouvriers de Montréal, où elle grandit. Dans les années 1970, la jeune fille, qui se destine à la pédagogie, chante aussi avec sa bande, sa «gang de chums». Découverte par Luc Plamondon, elle est choisie pour l'un des premiers rôles de Starmania, qui se monte à Paris. Choc des cultures, rencontre avec des stars, Michel Berger et France Gall notamment, elle dévoile les coulisses de cet opéra-rock devenu un spectacle-culte.Tragique, drôle, tendre, corrosif, ce récit foisonnant dessine aussi le portrait d'une femme entière, originale, que la France a adoptée et à qui le public est fidèle depuis trente ans.

Kanadisches Französisch im Unterricht - Lynda Lemay: Les maudits Français [Le français canadien en classe - Lynda Lemay : « Les maudits Français »] - Thiele, Sylvia (Varietäten im Französischunterricht. 1. Französische Fachdidaktiktagung [Les variétés dans l'enseignement du français. 1er colloque de didactique du français], 2011)

Notes from the Field: The Cree Fiddlers of James Bay - Wilkins, Frances (Canadian Folk Music / Musique folklorique canadienne, 2011)

Violet Archer: A Canadian woman in composition - Banfield, Emma (Université Northwestern, 2010)

L'enseignement de la musique en milieu autochtone canadien - Côté, Gérald (Les faces cachées de l'interculturel. De la rencontre des porteurs de culture, 2010)

La création musicale : scène d'un dialogue interculturel à la croisée des imaginaires - Gauthier Mercier, Catherine (Interfaces Brasil/Canadá, 2010)

One Day in the Life of Rufus Wainwright - Hailand, Tim (Hailand Books, 2010)
One Day in the Life of Rufus Wainwright follows the singer-songwriter from New York City to Boston for his performance at the Boston Opera House, which featured his sister Martha Wainwright as a special guest. With an intro by NYC nightlife legend Cherry Vanilla and text from Rufus himself.

"Si mosós no las vamos a recoger...": The Songbooks of Emily Sene and Bouena Sarfatty-Garfinkle - Havassy, Rivka (Los sefardíes ante los retos del mundo contemporáneo. Identidad y mentalidades [Les sépharades face aux défis du monde contemporain. Identité et mentalités], 2010)

Jeunesse, musique et rituels chez les Atikamekw (Haute-Mauricie, Québec) : ethnographie d'un processus d'affirmations identitaire et culturelle en milieu autochtone - Jérôme, Laurent (Université Laval, 2010)

There Will Be Rainbows: A Biography of Rufus Wainwright - Lake, Kirk (Itbooks, 2010)
"No contemporary pop performer's work mixes innovation and tradition like Rufus Wainwright's. He is the son of singer, songwriter, actor Loudon Wainwright III and legendary Canadian folk singer Kate McGarrigle whose story is one of towering highs and rock bottom lows in which family influences, sexual experimentation, and a crystal meth addiction in the early 2000s have greatly contributed."

The Montreal Sailors' Institute and the Homosexual Sailor: A Model for Moral Reform in the Nineteenth and Twentieth Centuries - Renwick, Claire (Montreal as Palimpsest, 2010)

Diane Dufresne, sentiments partagés. Hommages de personnalités et de fans - Rousseau, Denis (Les Éditions Québec-Livres, 2010)
À la fois superstar et femme secrète, Diane Dufresne est une des rares artistes à susciter autant de passion au Québec, en France et dans toute la francophonie. Depuis quatre décennies, ses admirateurs sont légion des deux côtés de l'Atlantique et le milieu artistique reconnaît unanimement son audace et son immense talent de créatrice

“Oh What a World”: Queer Masculinities, the Musical Construction of a Reparative Cultural Historiography, and the Music of Rufus Wainwright - Schwandt, Kevin C. (Université du Minnesota, 2010)
Throughout his ascendancy in fame and cultural visibility, singer/songwriter and gay pop icon Rufus Wainwright's output has been consistently related, by scholars and critics alike, to camp aesthetics, modes of artistic expression typically understood as emerging from queer communities, particularly certain gay male populations, but ones whose political potential is highly contested. Traditional conceptions of camp, as most famously articulated by Susan Sontag in the 1960s, emphasize style over content, necessarily rendering it politically-disengaged. However, scholars have vehemently challenged conceptions like Sontag's, in order to reclaim camp as a potent means to facilitate queer world-making and a powerful resistance to heteronormativity. I examine Wainwright's image and music in order to theorize a new queer interpretive listening position. Specifically, I draw upon the literary perspective of “reparative reading,” articulated by Eve Kosofsky Sedgwick in opposition to what she describes as “paranoid reading,” to propose a uniquely queer approach to musical and cultural historiography, exemplified by Wainwright's music. Much of the current queer musicology focuses on lost histories, systematic marginalization, and the commoditization of queer identities. While such approaches have produced important insights, thorough examination of the relationships between queer cultural products and their queer reception has proven elusive. This project suggests a unique approach to understanding the musical construction of a specific kind of queer masculinity, one which combines authorial creation with reparative conceptions of reception, in order to theorize a uniquely gay male interpretive position. When viewed through a theoretical lens combining politically-potent conceptions of camp performativity with a reparative reading position, Wainwright's music strikingly enacts Philip Brett's call to claim, not historical evidence, but the right of interpretation, emerging as an act of resistance via the reclamation and consolidation of a queer interpretive authority. In this way, Wainwright articulates both a rupture in the history of queer masculinity and a powerful means of resistance to the often-exclusionary relationships between literary, musical, and artistic objects and the heteronormative cultural systems in which they are created.
Keywords: Communication and the arts; Gay history; Gay rights; Historiography; Masculinities; Popular culture; Queer; Reparative reading; Rufus; Social sciences; Wainwright

Être compositeur aujourd'hui : entretien de Sophie Stévance avec Isabelle Panneton - Stévance, Sophie (Composer au XXIe siècle. Pratiques, philosophies, langages et analyses, 2010)

Quelle place pour les femmes dans la création musicale au XXIe siècle ? - Stévance, Sophie (Composer au XXIe siècle. Pratiques, philosophies, langages et analyses, 2010)

Reprise et intertextualité musicale. L’hommage à La Bolduc par des compositrices engagées vers l’avant - Stévance, Sophie (Volume ! La revue des musiques populaires, 2010)
Cet article étudie la notion de reprise sous l’angle de l’Hommage à La Bolduc rendu par sept compositrices à Mary Travers (alias La Bolduc), icône de la musique populaire au Québec dans les années 1930, à l’occasion du Festival SuperMicMac. Par des allusions, des références précises et explicites ou par de simples emprunts et citations, ces hommages sont autant de lectures que de relectures des chansons sélectionnées en abordant différents modes de jeux d’« intertextualité musicale ». Celle-ci se situe à deux niveaux : le pôle de la production, qui montre que les chansons engagées de La Bolduc sont elles-mêmes le témoignage d’une époque ; le pôle de la réception, pour exposer les résonances de ces chansons à partir de références autres et communes à la fois, comme la place des femmes dans la création musicale. Cette étude envisage ainsi la reprise à partir des aspects, des significations et des enjeux musicaux posés par l’intertextualité musicale, ici abordée sous l’angle de l’hommage alors conçu comme « réactivateur » de sens.
Keywords: concert / live / festival; féminité / masculinité / genre; intertextualité (musicale); politique / militantisme; reprise / pastiche / parodie; réception

Hip-hop autochtone au Québec. Oralités contemporaines au gré des ondes politiques et médiatiques - Audet, Véronique (Inter : art actuel, 2009)
An article from Inter, on Érudit.
Publisher: Les Éditions Intervention

Modèles identitaires sexués et rapports amoureux chez Daniel Bélanger - Boisclair, Isabelle; Tellier, Carolyne (Écouter la chanson, 2009)

Chansons fleuve suivi de Les lieux de l'intime dans "Arbre à fruits, arbre à fruits" de Marie-Jo Thério. Analyse narratologique et paralinguistique - Boucher, Mélanie (Université Laval, 2009)
Ce mémoire de création littéraire se divise en deux parties. La première propose une série de chansons intitulée Chansons Fleuve. Ce sont huit pièces créées autour de l'idée de l'intime, dont j'ai composé les paroles et la musique1. Elles ont été enregistrées sur un support audio qui accompagne la copie papier de ce mémoire. La seconde partie consiste en une analyse des rapports qu'entretiennent le texte et la musique d'"Arbre à fruits, arbre à fruits" de Marie-Jo Thério, avec l'intime. À travers les paroles de la pièce, les marques de l'intime sont présentes comme contenu (l'essence de l'intime, les thématiques) et comme forme (les relations, les situations, le temps, l'espace). Dans l'enregistrement de la voix et l'interprétation, sont véhiculées plusieurs émotions qui installent un climat d'intimité, appuient le texte et contribuent à rapprocher le public de l'artiste.

Chansons de travail, chansons de chômage : une lecture du monde ouvrier pendant la crise à travers l’œuvre de La Bolduc - Charest, Marie-Josée (Études littéraires, 2009)
In the 1930s, Mary Travers wrote folk songs dealing with the thorny issue of the working poor during hard times. A self-styled “woman at the service of the community”, she focused on those who lost their jobs as a result of the economic crisis. Heeding tradition, she lauded the work of famers whom she perceived as the mythical representatives of an idealised “old era”. How did she reconcile her songs praising tradition with an increasingly industrial labour market ? How did she react to women entering the workforce ? What did she think of government actions in the face of dwindling employment and pressing poverty ? Did she consider herself to be a career woman, what with hers being the first successful recordings of Quebec folk songs ? Confronting or buttressing established taboos such as those about women in the workforce, she wrote songs reflecting those societal issues prevalent at the time. Yet, she set herself apart both through her trade as a songwriter and her depiction of it. The economic situation in the province of Quebec influenced how labour was perceived, and her writings, favouring the standpoint of a working woman from the lower classes where employment is a matter of both survival and pride, echoed this perception with originality. A sociological and critical analysis of her songs illustrates the societal discourse on labour that prevailed during hard times.
Publisher: Département des littératures de l'Université Laval

Canadian Women Composers in Modernist Terrain: Violet Archer, Jean Coulthard and Barbara Pentland - Danielson, Janet (Circuit, 2009)
The successful compositional careers of Jean Coulthard, Barbara Pentland, and Violet Archer spanned all but the first three decades of the twentieth century. Entering a compositional career at this time had many challenges: as Western Canadians, these composers had to establish their credibility with a public that could not be counted on to recognize the worth of their work due to sexist bias and a prevailing critical stance: public approval was evidence of a lack of true creativity. This was especially problematic for women, who had to keep to the center of progressive composition, away from the experimental and conservative margins, in order to gain recognition. Following World War II, the pressure of modernism increased, due at least in part to initiatives by the U. S. Government in occupied Germany, countering the stereotype of the unsophisticated American with a new narrative of American experimental tradition.
Publisher: Les Presses de l'Université de Montréal

La représentation de la masculinité dans les vidéoclips de musique populaire : le code visuel et l’expression de la vulnérabilité masculine - Demers, Véronique (Université de Montréal, 2009)
Ce mémoire propose d'étudier les représentations de la masculinité dans les vidéoclips de musique populaire. Il consiste plus précisément en une analyse textuelle de vidéoclips suivant l'approche sémiologique. La représentation y est entendue comme un processus d'attribution de sens, agissant dans la construction sociale de la masculinité. Selon une méthode qualitative, il est premièrement question de cerner et, ultérieurement, explorer les principaux schémas de la masculinité dans un corpus de 29 vidéoclips sélectionné auprès de la chaîne québécoise Musique Plus. L'observation des codes visuels est centrale à cette entreprise, l'articulation de ces derniers permettant la prolifération d'expressions du genre masculin. Partant du point de vue que des attributs, notamment la force et l'invulnérabilité, apparaissent comme typiquement masculins au sein de certaines représentations, il sera question de confronter cette idée aux trois scénarios majeurs ayant émané du corpus ; l'homme-enfant, l'introspectif et le meneur, indiquant tous trois la récente montée des représentations d'une masculinité vulnérable en musique populaire. Les constats qui résulteront de cette exploration seront finalement recadrés dans l'actuel cadre social, où le masculin et le féminin sont de moins en moins enclos dans les moules traditionnels et tendent à se redéfinir sur une nouvelle matrice

Mots de tête - Dufresne, Diane (Éditions Michel Lafon, 2009)
J'écris c'qui m'chante , dit-elle. Et elle a bien raison ! Au lieu d'une biographie pompeuse, Diane Dufresne nous livre avec bonheur une vie en éclats. Écrivain, peintre, chanteuse : nous la retrouvons sous ses multiples facettes – l'existentialiste, la rockeuse, l'amoureuse impudique (sur scène) et la femme secrète, inattendue. Nous nous retrouvons aussi nous-mêmes, à travers les émotions que Diane exprime. Des pages magnifiques sur l'amitié, l'amour, la solitude... D'intimes confidences où resurgissent nos peurs : peur de l'inconnu, de la mort, du destin de la Terre et du nôtre. Et parmi toutes ces craintes un oubli capital : celui de savourer la vie. Pourquoi sentons-nous toujours qu'on a quelque chose à faire au lieu de quelque chose à vivre ? Avec ses splendeurs d'écriture, sa fantaisie, son humanité, son humilité, cette diseuse de belle aventure nous enchante et nous fait du bien.

Facing the Music: Rituals of Belonging and Recognition in Contemporary Western Art Music - El-Ghadban, Yara (American Ethnologist, 2009)
In this article, I examine the tense relationship between belonging and recognition that occurs as two young composers try to situate their musical identities between the urge to contest the hegemony of Western art music and the desire to be part of and recognized within this musical tradition. I draw on their participation as finalists in an international composition competition to examine how issues of identity, postcoloniality, and belonging, on the one hand, and of musical authorship, subjectivity, and agency, on the other hand, are woven into the highly ritualized processes of evaluation and recognition in contemporary Western art music.
Publisher: [Wiley, American Anthropological Association]

The Piano Sonatas of Violet Archer: The Creative Influences of Bartók and Hindemith - Friesen, Darryl Shane (Université de l'Illinois à Urbana-Champaign, 2009)

Une histoire du jazz à Montréal - Gilmore, John (Lux Éditeur, 2009)
Pendant près d’un demi-siècle (1920–1970), Montréal a été un centre névralgique du jazz en Amérique du Nord. Le légendaire nightlife de la ville et l’abondance de travail qu’il offrait attiraient des musiciens de tout le continent. Dans ce livre, John Gilmore décrit l’effervescence culturelle de cette époque. Il nous transporte à Montréal, après la tombée de la nuit, dans les lieux mythiques aujourd’hui presque tous disparus où ont vécu et joué les Myron Sutton, Johnny Holmes, Oscar Peterson, Louis Metcalf, Steep Wade, Maury Kaye et René Thomas. Dans cette contribution fondamentale à l’histoire du jazz, on découvre que les Noirs américains venus s’établir à Montréal au début du XXe siècle ont largement contribué à la culture populaire nord-américaine. Gilmore souligne qu’au-delà des réalisations individuelles des musiciens, la production du jazz a été profondément influencée par des facteurs politiques, sociaux et économiques : la prohibition et la ségrégation raciale aux États-Unis, l’essor économique – notamment du secteur ferroviaire – de Montréal puis la Grande Dépression des années 1930, la Seconde Guerre mondiale, le « nettoyage » de la ville et la renaissance de la « moralité civique » des années 1950 et, enfin, l’émergence de l’indépendantisme québécois.
Keywords: Art / General; History / Canada / Post-Confederation (1867-); Music / Genres & Styles / Jazz; Political Science / General

Introduction : Compositrices sur la scène contemporaine - Goldman, Jonathan (Circuit: Musiques contemporaines, 2009)

Diane Dufresne : toute l'émotion du monde - Havard, Constance (Écouter la chanson, 2009)

Les voix du tambour. Traditions et innovations musicales chez de jeunes Atikamekw Nehirowisiwok, Québec - Jérôme, Laurent (Jeunesses autochtones. Affirmation, innovation et résistance dans les mondes contemporains, 2009)

"A Whole Hundred Years of Questionable Behavior": Wainwright/Garland/Jolson and Performance as Palimpsest - Kerr, Darin (The Theatre Annual, 2009)
Keywords: Audiences; Cultural heritage; Culture; Empowerment; History; Musical performances; Performance art; Prostheses; Theater

Tusarnituuq! Nagano In The Land Of The Inuit - Lajeunesse, Félix (Filmoption International, 2009)
In September 2008 Canada’s most prestigious orchestra, the acclaimed Orchestre symphonique de Montreal (OSM), embarked on its first ever tour of the Canadian Arctic. Lead by internationally celebrated conductor Kent Nagano, the OSM's program featured a concert of music from the classical repertoire, including Stravinksy’s Histoire du soldat narrated in Inuktitut, the language of the Inuit people, and a new work inspired by Inuit throatsinging from Canadian composer Alexina Louie. Offering viewers intimate access to Maestro Nagano, the artists, and the remote Inuit communities they visit, this stunning documentary captures an extraordinary meeting of two worlds through music.

‘People Didn’t Call It Klezmer’: Klezmer Music in Jewish Montreal 1924-1970 - Lam, Emily (Student Journal of Canadian Jewish Studies, 2009)

Micheline Coulombe Saint-Marcoux et Marcelle Deschênes : pionnières dans le sentier de la création électroacoustique - Lefebvre, Marie-Thérèse (Circuit : musiques contemporaines, 2009)
A review of “masculine” and “feminine” attitudes towards music composition of the past fifty years highlights the contributions of Micheline Coulombe Saint-Marcoux and Marcelle Deschênes to the development of Québécois electroacoustic music. The author re-creates the historical context for the composers’ childhoods, adolescences, and periods of training in Montreal and Paris, and follows this with a discussion of how they negotiated the dominant trends of the 1970s. She then turns to the composers’ roles as pioneers: in their wish to depart from well-trodden paths, Coulombe Saint-Marcoux and Deschênes turned to new technological tools that would allow them to express a new artistic sensibility. From this perspective, they should be considered the “sherpas” of Québécois electroacoustic music.
Publisher: Les Presses de l'Université de Montréal

‘Ch'us mon propre Bescherelle’: Challenges from the Hip-Hop nation to the Quebec nation - Low, Bronwen; Sarkar, Mela; Winer, Lise (Journal of Sociolinguistics, 2009)
We examine the uses of and attitudes towards language of members of the Montreal Hip-Hop community in relation to Quebec language-in-education policies. These policies, implemented in the 1970s, have ensured that French has become the common public language of an ethnically diverse young adult population in Montreal. We argue, using Blommaert's (2005) model of orders of indexicality, that the dominant language hierarchy orders established by government policy have been both flattened and reordered by members of the Montreal Hip-Hop community, whose multilingual lyrics insist: (1) that while French is the lingua franca, it is a much more inclusive category which includes ‘Bad French,’ regional and class dialects, and European French; and (2) that all languages spoken by community members are valuable as linguistic resources for creativity and communication with multiple audiences. We draw from a database which includes interviews with and lyrics from rappers of Haitian, Latin-American, African-American and Québécois origin.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/j.1467-9841.2008.00393.x
Keywords: Order of indexicalities; Quebec language policy; multilingual code-switching; normative tradition (French); rap lyrics; urban youth culture

‘Small Has No Inside, Big Has No Outside’: Montreal’s Chinese Diaspora Breaks Out/In Music - Morris, Kim Chow (MUSICultures, 2009)
Through ethnographic fieldwork undertaken from 2003 to 2010, discussion with local musicians, and analysis of concert programs, recordings, live performances, rehearsals, press reviews, musicians’ websites and textual sources, the author examines the means by which the Chinese diasporic community in Montreal negotiates its cultural identity and exerts its agency through musical performance. The author also explores how the tangled relationships of regionally- diverse Chinese immigrants to their birthplaces and their chosen homeland are unravelled, reflecting simultaneous positions as “insiders” and “outsiders.”

Diane Dufresne, la diva de la chanson québécoise - Oberhuber, Andrea (BAT – Das Bulletin des Archivs für Textmusikforschung, 2009)

Hildegarde von Bingen et Lorraine Vaillancourt : deux femmes rebelles dans leur siècle... - Peillon, Catherine (La pensée de midi, 2009)
Bibliographie_available: 0 Cairndomain: www.cairn.info Cite Par_available: 0 Publisher: Actes sud

Des pratiques d’artistes et de chercheuses en écologie sonore - Piché, Claire (Recherches féministes, 2009)
This article is an incursion into the domain of sound ecology based on interdisciplinary research about artists and researchers. We expose the fundamental principles of sound ecology, a discipline that emerged during the seventies, and discuss the best practices of women in sound ecology, demonstrating how this constitutes a relevant research area for women’s studies. The link between feminism and sound ecology being established, we summarize three sociopolitically relevant research projects whose methods resemble feminist action research. We conclude by reflecting on the best means to foster interdisciplinary collaboration.
Publisher: Revue Recherches féministes

De la musique de geste à la musique du son, de SuperMémé à I8U - Prévost, Hélène (Circuit, 2009)
La musique actuelle née au tournant des années 1970-1980 a connu ses heures de gloire pendant de nombreuses années. Trois femmes font partie de la lancée et demeurent à ce jour des musiciennes actives et des administratrices hors pair. Mais d’autres, artistes sonores plutôt qu’instrumentistes, émergent, au moment du tournant technologique et plus particulièrement au milieu des années 1990. Un nombre important de ces femmes développent des pratiques non instrumentales d’art audio, de musique bruitiste, de musiques mixtes, électroniques expérimentales, d’installation et de multimédia. Elles sont mal connues, méconnues des grands médias et de la plupart des lieux d’enseignement de la musique, bien que plusieurs d’entre elles les aient fréquentés. Ce moment de rencontre avec certaines d’entre elles souhaite les faire apparaître, en plein jour.
Publisher: Les Presses de l'Université de Montréal

Les femmes et la chanson au Québec : jalons d'une histoire et esquisses de perspectives - Savoie, Chantal (Écouter la chanson, 2009)

Nicole Lizée – Surrealist Collagist. A Music of New Contexts - Simas, Richard (Musicworks, 2009)

Du teueikan au hip-hop, des harangues à l’art action - Sioui Durand, Guy (Inter : art actuel, 2009)

Interpreting success and failure: the eclectic careers of Eva and Juliette Gauthier - Slominska, Anita (Université McGill, 2009)
My dissertation explores the eclectic singing careers of sisters Eva and Juliette Gauthier. Born in Ottawa, Eva and Juliettte were aided in their musical aspirations by the patronage of Prime Minister Wilfred Laurier and his wife Lady Zoë. They both received classical vocal training in Europe. Eva spent four years in Java. She studied the local music, which later became incorporated into her concert repertoire in North America. She went on to become a leading interpreter of modern art song. Juliette became a performer of Canadian folk music in Canada, the United States and Europe, aiming to reproduce folk music “realistically” in a concert setting. My dissertation is the result of examining archival materials pertaining to their careers, combined with research into the various social and cultural worlds they traversed. Eva and Juliette’s careers are revealing of a period of transition in the arts and in social experience more generally. These transitions are related to the exploitation of non-Western people, uses of the “folk,” and the emergence of a cultural marketplace that was defined by a mixture of highbrow institutions and mass culture industries. My methodology draws from the sociology of art and cultural history, transposing Eva and Juliette Gauthier against the backdrop of the social, cultural and economic conditions that shaped their career trajectories and made them possible.

Tunes That Bind: Paul J. Seelig, Eva Gauthier, Charles T. Griffes, and the Javanese Other - Spiller, Henry (Journal of the Society for American Music, 2009)
The powerful concept of orientalism has undergone considerable refinement since Edward Said popularized the term with his eponymous book in 1978. Orientalism typically is presented as a totalizing process that creates polar oppositions between a dominating West and a subordinate East. U.S. orientalisms, however, reflect uniquely North American approaches to identity formation that include assimilating characteristics usually associated with the Other. This article explores the complex relationship among three individuals—U.S. composer Charles T. Griffes, Canadian singer Eva Gauthier, and German-trained Dutch East Indies composer Paul J. Seelig—and how they exploited the same Javanese songs to lend legitimacy to their individual artistic projects. A comparison of Griffes's and Seelig's settings of a West Javanese tune (“Kinanti”) provides an especially clear example of how contrasting approaches manifest different orientalisms. Whereas Griffes accompanied the melody with stock orientalist gestures to express his own fascination with the exotic, Seelig used chromatic harmonies and a chorale-like texture to ground the melody in the familiar, translating rather than representing its Otherness. The tunes that bind Griffes, Gauthier, and Seelig are only the raw materials from which they created their own unique orientalisms, each with its own sense of self and its own Javanese others.
Publisher: Cambridge University Press

La composition musicale et la marque du genre : l’examen conscient de l’« écriture féminine » - Stévance, Sophie (Circuit, 2009)
Si les spéculations idéologiques concernant les différences biologiques entre les sexes persistent dans le domaine de la création, elles ont été mises en valeur dès 1970 par des écrivaines et plasticiennes pour oeuvrer en fonction de mythes spécifiques touchant à leur féminité, au corps de la femme chargé de stigmates, afin qu’émerge un « art féminin ». D’une certaine manière, des compositrices vont emprunter cette voie en affirmant entretenir un rapport différent de celui des hommes à l’écriture musicale. Selon elles, leur sensibilité spécifique et leur situation d’être au monde les poussent à travailler autrement, à partir de thématiques « existentielles » inspirées de leur condition sociale et culturelle. De telles circonstances ont provoqué cette quête identitaire par l’invention d’un style artistique particulier qui, paradoxalement, use de ce qui était considéré par un féminisme radical comme les pièges de la féminité. Cet article tente de montrer que ces spécificités, du moins ces constantes relevées par les créatrices expliquant leur démarche, sont le résultat de recherches esthétiques pour caractériser une création universelle au féminin, et non le produit de diktats biologiques.
Publisher: Les Presses de l'Université de Montréal

Les femmes dans la création musicale improvisée: l'exemple des collectifs de la musique actuelle au Québec - Stévance, Sophie (L'Éducation musicale, 2009)

Réactiver le sens de l’hommage : L’exemple du Festival SuperMicMac au Canada - Stévance, Sophie (Itamar, 2009)
Cet article étudie la notion d’hommage à partir du Festival SuperMicMac organisé en 2000 par sept compositrices à la mémoire de Mary Travers (alias La Bolduc), icône de la musique populaire au Québec dans les années 1930. Par des allusions, des références précises et explicites ou par de simples emprunts et citations, ces hommages sont autant de lectures que de relectures des chansons sélectionnées en abordant différents modes de jeux d’« intertextualité musicale ». Celle-ci se situe à deux niveaux : le pôle de la production, qui montre que les chansons engagées de La Bolduc sont ellesmêmes le témoignage d’une époque ; le pôle de la réception, pour exposer les résonances de ces chansons à partir de références autres et communes à la fois, comme la place des femmes dans la création musicale. Cette étude envisage ainsi l’hommage à partir des aspects, des significations et des enjeux musicaux posés par l’intertextualité musicale. L’hommage est ainsi conçu comme un « réactivateur » de sens.

Ces voix oubliées un choeur qui déjoue les préjugés - Barrette, Blaise (Office national du film du Canada, 2008)

Isabelle Boulay - Bescos, Pierre-Alexandre (K&B, 2008)
La petite fille qui chantait debout sur un juke-box en Gaspésie pour divertir les clients du restaurant de ses parents a parcouru bien du chemin... De starmania à la country, en passant par la variété et la chanson réaliste, la carrière d'Isabelle Boulay est un fascinant mélange de styles et d'émotions. Sa voix, entre brisure et éclat, lui a assuré l'admiration et la collaboration des plus grands, de Francis Cabrel à Johnny Hallyday, en passant par Serge Lama, Julien Clerc ou Patrick Bruel. Entre le Canada et la France, cette artiste sincère et humble n'a jamais dévié de sa ligne directrice : trouver sa vérité profonde. Son nouvel album Nos lendemains, dépouillé et céleste, prouve une fois de plus l'immense talent d'Isabelle Boulay, qui demeure, au-delà des océans, une référence incontournable de la chanson. Cet Instant-Mag2 propose un entretien fleuve avec l'artiste, une biographie complète et détaillée, ainsi que des interviews de ses proches et/ou collaborateurs. Le tout illustré par de superbes photos en grand format. Un collector indispensable.

L’histoire du Rising Sun et ses légendes jazz et blues - Boicel, Roue-Doudou (Éditions Michel Brûlé, 2008)

La chanson, une technologie du genre: Éric Lapointe et l'exaltation d'une virilité rebelle - Boisclair, Isabelle (Quebec Studies, 2008)
Publisher: American Council for Quebec Studies

Colette Boky. Le chant d'une femme - Boky, Colette; Barrière, Mireille (Éditions Triptyque, 2008)
La présente biographie relate une carrière riche, autant à l'opéra qu'au concert et en récital. Le lecteur pénètre dans les coulisses parfois mystérieuses des maisons d'opéra. Colette Boky nous entretient de ses relations avec ses collègues, de sa conception des principaux rôles qu'elle a incarnés, de ses prestations devant maints personnages célèbres. Mais, plus encore, ces pages tracent le portrait d'une femme résolue, fonceuse, au franc parler, qui ne craint pas de mettre sa réputation au service de causes qui lui tiennent à coeur.

Francine-Brunel-Reeves : portrait d’une chercheuse atypique ou quand la pratique appelle la recherche... - Bolduc, Marc (Rabaska : revue d'ethnologie de l'Amérique française, 2008)
This article offers a portrait of Francine Brunel-Reeves, an independent researcher who has followed an exceptional course throughout her active life. It begins with a short biography of this artist, perfomer, educator and independant researcher who has split her life between France, Québec and the United States of America. The second section describes the current state of her work and the theoretical approaches that have delineated her research not only in the field of ethnology, but also in anthropology, musicology and mythology.
Publisher: Société québécoise d’ethnologie

Nanette Workman. Rock'n romance - Bolduc, Mario (Éditions Libre Expression, 2008)
Issue d'une famille de musiciens, Nanette Workman chante sur scène - devant 300 personnes ! - dès l'âge de quatre ans. Le lieu : Jackson, dans le Mississippi. Suivront de nombreuses performances dans des pièces scolaires et des spectacles pour amateurs. Tout naturellement, Nanette s'inscrit en musique à l'Université de Southern Mississippi.Soudain, son univers bascule…En 1964, Nanette se retrouve sur Broadway dans une comédie musicale qui fera le tour des États-Unis. Elle rencontre alors Tony Roman, qui l'invite à partager la scène avec lui à l'occasion d'une tournée au Québec. Pour Tony, la jeune femme a le talent et les capacités pour entreprendre une carrière internationale. La chanteuse ne parle pas français, mais les Québécois l'adorent et l'adoptent ! Son séjour se prolonge… Nanette devient une vedette. S'installe entre elle et le public québécois une fidélité qui dure encore aujourd'hui.Mais la jeune Américaine a la bougeotte. On la retrouve en Grande-Bretagne, où elle travaille avec les Rolling Stones, Peter Frampton, John Lennon et plusieurs autres figures incontournables du rock britannique. Ensuite, elle part en France, où elle chante avec Johnny Hallyday et l'accompagne dans une tournée mondiale. Elle revient au Québec juste à temps pour enregistrer Lady Marmelade. D'autres succès s'ajouteront à cette liste…Tout au long de sa carrière, Nanette Workman a été le témoin privilégié de l'évolution de la musique populaire et l'une de ses dignes représentantes, ici et à l'étranger. Dans cette biographie, Nanette se livre sans retenue, avec chaleur et émotion, mais aussi avec beaucoup d'humour : ses échecs, ses succès, ses amours tumultueuses - avec Johnny Hallyday notamment -, sa descente dans l'enfer de la drogue, ses liens avec le crime organisé, la violence dont elle a été victime dans ses relations avec les hommes, sa fascination pour les armes à feu et le… bouddhisme, sans oublier l'accident tragique qui a failli lui coûter la vie.Au final, ce livre relate le parcours inusité mais palpitant d'une femme exceptionnelle, qui n'hésite pas à tout dévoiler…

Lhasa. La route chante - De Sela, Lhasa (Éditions Textuel, 2008)
La chanteuse mexicano-américaine Lhasa de Sela, également passionnée par la peinture, le dessin, la photographie et l'écriture, retrace son parcours et dévoile les lectures, les artistes et les pensées qui la nourrissent (Jung, Hugo, Géricault, Cat Stevens, etc). En 1998, la chanson la Llorona la fait connaître en Europe et au Québec.

Errance, appartenance, reconnaissance dans la musique savante occidentale - El-Ghadban, Yara (Université de Montréal, 2008)

"Eskimo chicks and word warriors": the creative cultural spaces of Elisapie Isaac and Taqralik Partridge - Foot, Johanna Maria (Université Carleton, 2008)

Les femmes et la vie culturelle à Québec avant la Révolution tranquille - Harvey, Fernand (Cap-aux-Diamants : la revue d'histoire du Québec, 2008)

Dykes on Mykes: Podcasting and the Activist Archive - Hogan, Mel (TOPIA: Canadian Journal of Cultural Studies, 2008)

All these poses, such beautiful Poses: articulations of queer masculinity in the music of Rufus Wainwright - Jones, Matthew J. (Université de Géorgie, 2008)
Singer-composer Rufus Wainwright uses specific musical gestures to reference historical archetypes of urban, gay masculinity on his 2002 album Poses. The cumulative result of his penchant for pastiche, eschewal of traditional musical boundaries, and self-described hedonism, Poses represents Wainwright’s direct engagement with the politics of identity and challenges dominant constructions of (homo)sexuality and masculinity in popular music. Drawing from a vast lexicon of musical styles, he assembles an idiosyncratic persona, ignoring several decades of pop with an “utter lack of machismo [and] a freedom that comes to outsiders disinterested in meeting the requirements of the dreary status quo.”1 Though analysis of musical and lyrical characteristics of Poses, I establish a dialectic between Wainwright’s musical persona and four historical modes of urban gay masculinity: the 19th Century English Dandy, the French flaneur, the 20th Century gay bohemian, and the “Clone.” In doing so, I introduce Wainwright as a reinvigorating force, resuscitating the subversive potential of radical gay sexuality as a 21st Century model for imagining gay male subjectivity.

Sobre meninos e homens Por uma leitura edipiana: Rufus Wainwright e a canção Dinner at Eight [Des garçons et des hommes: Rufus Wainwright et la chanson "Dinner at Eight"] - Júnio, José Mariano Tavares (Cadernos do LINCC, 2008)
O artigo reflete sobre a obra do compositor novaiorquino Rufus Wainwright iconsiderando as suas influências no sentido de explicar, ao menos em parte, a originalidade melódica e harmônica presente na arquitetura de suas canções, a grandiloqüência dramática dos arranjos, e a complexidade de sua persona artística, opondo, a uma forte teatralidade camp, a melancolia trágica, cortante, do solitário e outsider.

Les représentations de la femme dans l'œuvre scénique de Diane Dufresne, 1975-1984 - Lafrenière, Marilyne (Université du Québec à Trois-Rivières, 2008)
Ce mémoire de maitrise vise a identifier les representations de la femme proposees par la chanteuse Diane Dufresne entre 1975 et 1984, afin de mettre en lumiere la contribution d'une artiste individuelle et officiellement non-engagée au discours public du Quebec de ces annees. Les deux dimensions de la communication - remission et la reception - y sont traitees et comparees. Une analyse thematique des paroles des chansons de Diane Dufresne, mise en relation avec differents aspects de ses mises en scene, nous ont permis de cerner l'univers de Partiste ainsi que les modeles feminins qu'elle propose. II s'agit de femmes solitaires, instables, sexuelles, sensuelles, parfois agressives et generalement apeurees face au monde dans lequel elles evoluent. Ainsi, les diverses origines du malaise existentiel des heroines - le quotidien lassant, la vitesse, le stress, les normes sociales, la vieillesse et la dictature de 1'image - sont autant d'entraves ressenties dans leur quete de liberte et de critiques adressees au monde contemporain. Leurs attaches sont d'ordre familial et professionnel. Les heroines embrassent egalement deux causes: la protection de Penvironnement et la liberte d'expression. Cette derniere - par la creativite qu'elle implique — est presentee comme un exutoire efficace au mal de vivre. Les heroines incarnees par Diane Dufresne s'inscrivent en marge des modeles generalement diffuses dans la chanson des decennies 1970 et 1980. L'etude de la presse culturelle quebecoise et des entrevues avec des fans de Partiste nous renseignent sur la reception de Diane Dufresne et de son oeuvre dans la societe ou elles sont diffusees. Etonnamment, les journalistes et les fans ne se sont pas averes etre des recepteurs si distincts. En effet, s'ils commentent parfois aprement la vie personnelle de Diane Dufresne, son comportement hors de la scene ou ses prises de position face a l'industrie, l'apparente fascination des journalistes en regard de l'art de Diane Dufresne les situe plus pres d'un public d'admirateurs que de la critique. C'est avec complaisance, sauf quelques rares exceptions, que les journalistes ont relaye 1'image que Diane Dufresne voulait donner d'elle-meme. Cette image est neanmoins incomplete puisque la douceur et la conscience sociale de Partiste y sont amenuisees par rapport aux autres dimensions de sa persona. Les journalistes culturels ont aussi contribue a creer une autre dimension au personnage public qu'est Diane Dufresne qu'ils associent a P emancipation feministe, alors qu'elle-meme refusait clairement cette etiquette. Alors que Paspect feministe est evacue du discours des fans, la force de Paffirmation de Diane Dufresne, voire son emancipation individuelle persiste et constitue un des piliers de leur attachement fidele et constant à l'artiste. Leur identification profonde a Diane Dufresne, la specificite qu'elle reconnait a chaque spectateur et Pinvitation qu'elle lance a chacun d'assumer sa difference lors de ses spectacles scelle le lien entre l'artiste et son public.

Une œuvre purement musicale ? Analyse de la spiritualité des Sœurs des Saints Noms de Jésus et de Marie à partir de l’exemple de l’École de musique Vincent-d’Indy - Laperle, Dominique (Études d'histoire religieuse, 2008)
L’École de musique Vincent-d’Indy des Soeurs des Saints Noms de Jésus et de Marie (connue avant 1951 sous le nom d’École supérieure de musique d’Outremont) fut considérée comme l’une des meilleures du genre dans la province de Québec. Cette réputation ne peut passer sous silence le fait qu’il s’agisse d’une institution catholique. Dans la vie scolaire quotidienne, quelle place occupait réellement la spiritualité ? En étudiant les Constitutions, le Coutumier, les programmes musicaux, les lettres circulaires et différents imprimés des religieuses, nous pouvons mieux identifier la spiritualité à laquelle se rattache cette communauté et comprendre comment elle l’a vécue et partagée.

L'identité culturelle dans « Montréal », d'Ariane Moffatt : une analyse musicale sémiologique - Laurier-Cromp, Mélanie (Université McGill, 2008)
La chanson « Montréal », d'Ariane Moffatt, a remporté un vif succès durant l'été 2006. Ce mémoire examine les causes de cette popularité. Après une revue des diverses méthodes existantes en recherche en musique populaire, trois types d'analyse se succèdent. En premier lieu, l'étude présentée ici décrit la chanson de manière théorique; on y observe le fonctionnement de la voix, de la mélodie, de la métrique, de la basse, des phrases, de la tonalité, des accords et des instruments utilises, images par une transcription précise de l'enregistrement de la chanson. Puis, le présent travail étudie les codes musicaux qui se retrouvent dans «Montréal». Dans cette deuxième section, le message musical du morceau est analysé, en tenant compte du contexte socioculturel de l'été 2006, de l'histoire nationale et musicale qui a précédé la sortie de cette pièce et des paroles de la chanson. Finalement, cette étude investigue la composante identitaire de «Montréal» en examinant les croyances nationalistes des Québécois, la place de la chanson dans l'imaginaire collectif de ce peuple, et la tradition musicale populaire de la province.

La chanson country-western au Québec: État de la question et pistes musicologiques - Lefrançois, Catherine (Quebec Studies, 2008)

La faim Artaud. Le corps musical éclaté : à la recherche d'un langage musical inspiré d'Artaud - Llugdar, Analia (Université de Montréal, 2008)
Ce travail s'inscrit dans une rechcerche interdisciplinaire tendant à faire le point sur l'actualité de la pensée d'Antonin Artaud à travaers l'analyse du texte radiophonique Pour en finir avec le jugement de dieu. Ce texte conçu peu avant sa mort réunit tous les éléments propres à la pensée d'Artanud tant au niveau philosophique qu'au niveau formel: le corps sans organes, le concept de jugement, l'idée de dieu mais aussi les «sonorisations», les cris et les «glossolalies» à travers une étude profonde des différents textes d'Artaud ainsi que de ses dessins, de sa voix enregistrée, de ses mises en scènes et des différents aspects de son langage, j'ai élaboré une écriture musicale qui m'a permis de composer une oeuvre qui s'inscrit dans le domaine du théatre musical et qui se veut une lecture personnelle d'Artaud. Ainsi, les éléments de ce nouveau langage ont été incorporés aux oeuvres que j'ai composé postérieurement. Nous aborderons dans le chapitre 1 les sourecs nombreuses et hétéroclites du langage d'Artaud; la lecture de ses différentes manières d'expression artistique sont indispensables à la compréhension et à l'interprétation de sa pensée. Le chapitre 2 présente une analyse approfondie de la pièce résultat de ces recherche: La Faim d'Artaud, oeuvre de théatre musical pour sept instrumentistes, mezzo-soprano, baryton, un comédien et une bande pré-enregistrée. Cette analyse montre différents aspects du langage artaudien, présents dans la musique et dans les choix de mise en scène. Le dernier chapitre est une exemplification de l'influence qu'a exercée le langage développé à travers la composition de La Faim d'Artaud dans d'Autres oeuvres de mon répertoire. Pour démontrer cette influence, j'ai réalisé une analyse sommaire de la pièce Todos los recuerdos presentes envolvìan ese sonido y algo me miró pour orchestre de chambre de quinze instrumentistes.

The conservation of a gender fantasy: women and Top 40 radio in Montreal - Maki, Christine (Université McGill, 2008)
This work examines today's Anglophone Top 40 radio in Montreal in terms of gender. Looking at the history of commercial radio, and the historical relationship between radio and women, it argues that these radio stations have always programmed based on an imagined rather than actual understanding of their target audience. Programmers today continue to hold a conservative understanding of their female audience and their interests, and to program using a stereotypical understanding of gender.

Listening to/at/with Marilyn Lerner’s "They’re All in Families" - McNeilly, Kevin (Critical Studies in Improvisation / Études critiques en improvisation, 2008)
Marilyn Lerner’s audio-art composition “They’re All in Families” (1998) re-works a sound clip from a virulently homophobic message left on an answering machine, turning hate-speech back on itself to expose the rhythms and textures of verbal violence.

Le sacre du spectacle : Robert Charlebois et Diane Dufresne, deux cas de figure spectaculaires de la chanson québécoise - Oberhuber, Andrea (Quebec Studies, 2008)

« Un studio à soi ». Entrevue avec Bérengère Marin Dubuard, du Studio XX - Parent, Sylvie (ETC, 2008)
Un article de la revue ETC, diffusée par la plateforme Érudit.
Publisher: Revue d'art contemporain ETC inc.

L'émergence des chanteurs immigrants sur la scène de la musique populaire au Québec : l'exemple de Corneille et de Lynda Thalie - Proulx, Robert (Quebec Studies, 2008)
A l'instar des ecrivains de la litterature migrante, des chanteurs et des chanteuses venus de divers pays ont fait du Quebec leur port d'attache et le foyer de leur carriere artistique. Ce phenomene assez recent a fait qu'au cours des dix dernieres annees on a vu debarquer au Quebec des artistes d'Hai'ti, du Bresil, du Mexique, du Maroc, du Rwanda, du Tchad, de l'Algerie, et du Venezuela, chacun avec sa musique, sa couleur, et sa sensibilite propre. Dans cette nouvelle branche de la chanson quebecoise on trouve les themes de predilection de la litterature migrante tels que l'exil, la nostalgie, le sentiment de perte, l'adaptation a un nouveau pays, l'integration, le racisme, la xenophobie, et l'hospitalite. La chanson quebecoise s'enrichit de ces differents apports; car ces artistes apportent avec eux non seulement des voix, des sons et des styles musicaux nouveaux, mais aussi des themes inedits et des trames narratives originales qui refletent leur culture d'origine, leur passe, et leurs valeurs de meme que leurs emotions liees a leurs defis actueis et a leurs reves pour l'avenir. (1) Dans cet article, nous examinerons en detail l'ceuvre de deux d'entre eux: Lynda Thalie qui, selon Monique Giroux, l'experte en chanson francophone de Radio-Canada, "est, parmi les artistes neo-quebecois, celle qui a pris le plus de place et est la plus susceptible de conquerir un large public" (cite par Vignaux) et Corneille, celui qui a jusqu'a ce jour remporte le plus grand succes aussi bien commercial que d'estime. II a vendu plus d'un million et demi de ses deux premiers disques, et a lance son premier disque en anglais, "The Birth of Cornelius," au Japon en mai 2007. (2) Lynda Thalie: l'exilee d'Algerie

«Ousqu’on chill à soir?» Pratiques multilingues comme stratégies identitaires dans la communauté hip-hop montréalaise - Sarkar, Mela (Diversité urbaine, 2008)

"Still Reppin' Por Mi Gente": The Transformative Power of Language Mixing in Quebec Hip Hop - Sarkar, Mela (Global Linguistics: Hip Hop Cultures, Youth Identities, and the Politics of Language, 2008)

Influence de la culture hip-hop québécoise sur les adolescents montréalais d'origine haïtienne - Tessier, Karine (Université du Québec à Montréal, 2008)

Masculinités variables en temps de crise : deux auteurs-compositeurs-interprètes [Dumas, Fixer le temps; Stefie Shock, Les vendredis] - Boisclair, Isabelle (Spirale, 2007)

Rufus Wainwright [entrevista]: Geni i figura - Broc, David (Benzina: Revista d'excepcions culturals, 2007)

Lire Mary Travers (La Bolduc). Chansons et représentations sociales dans le Québec des années 1930 - Charest, Marie-Josée (Université de Montréal, 2007)
Ce mémoire de maîtrise intitulé Lire Mary Travers (La Bolduc). Chansons et représentations sociales dans le Québec des années 1930 a pour objet les dimensions sociales, historiques et idéologiques que les textes de La Bolduc prennent en écharpe et transforment. S'intéressant à la totalité des chansons écrites par Mary Travers entre 1927 et 1939, l'étude offre une analyse détaillée de la représentation de la société québécoise de l'entre-deux-guerres portée par son œuvre. C'est par le bais de l'analyse littéraire, de la cantologie et de la sociocritique que ces chansons humoristiques racontant la vie quotidienne et la misère des petites gens sont interprétées. Une attention particulière est portée au genre « chanson », à la narrativité, au registre linguistique, à l'humour, à la représentation des femmes et aux dérives idéologiques observées dans son répertoire. Par l'étude des chansons énumératives, des dialogues chantés et des autres ballades créées par Mary Travers, le mémoire rend compte de la mesure de l'inscription sociale de l'écriture de cette chansonnière et folkloriste populaire.

Three Canadian Sephardic Women and their Transplanted Repertories: From Salonica, Larache and Sarajevo to Montreal and Kahanawá:ke - Cohen, Judith R. (Folk Music, Traditional Music, Ethnomusicology: Canadian Perspectives Past and Present, 2007)

Culture, État et responsabilités : entretien avec Ana Sokolovic - Gendreau, Philippe (Liberté, 2007)
Publisher: Collectif Liberté

Circulation, valorisation et localisation de la musique pop planétaire : le cas Céline Dion - Grenier, Line (Musiques. Une encyclopédie pour le XXIe siècle : L'unité de la musique, 2007)
Posant un regard comparatiste sur la diversité des musiques à travers le monde, sur leurs brassages, mais aussi leurs traits communs, le volume V cherche à répondre à la question : la musique est-elle un langage universel ? Et quels en seraient les universaux ?

Keeping Time with Lesbians on Ecstasy - Halberstam, J[ack] (Women and Music: A Journal of Gender and Culture, 2007)
Publisher: University of Nebraska Press

Itinéraire de quatre pionnières de la vie culturelle à Québec après 1945 - Harvey, Fernand (Les cahiers des dix, 2007)
À Québec comme partout ailleurs, la place des femmes dans la sphère publique est relativement récente. L’idée qu’une femme puisse poursuivre des études universitaires, travailler à l’extérieur de la maison ou entreprendre une carrière après le mariage a commencé à se généraliser peu avant les années 1960. Dans ce long cheminement, certaines femmes ont joué un rôle pionnier. Cet article examine le parcours de vie de quatre de ces femmes qui ont réussi à faire leur marque dans le milieu culturel et médiatique de la ville de Québec au cours des années qui ont suivi la seconde guerre mondiale : Francoise Larochelle-Roy, Simone Bussières, Georgette Lacroix et Monique Duval. L’itinéraire biographique de ces pionnières permet de mieux comprendre les singularités de leur insertion dans le milieu culturel et professionnel, en même temps que les points communs qui les relient toutes quatre au contexte d’une époque. On les suivra donc depuis l’enfance jusqu’à la vie adulte où elles évolueront dans l’enseignement, le journalisme, l’animation radiophonique, ainsi que dans le monde des lettres.
Number: 61

The Ladino Song in the 20th Century: A Study of the Collections of Emily Sene and Bouena Sarfatty-Garfinkle - Havassy, Rivka (Université Bar-Ilan, 2007)
Hébreu
Keywords: Pas de lien web

Identifications, relations et circulation des savoirs chez les Atikmakekw de la Haute-Mauricie. Un regard ethnographique sur le tewehigan - Jérôme, Laurent (La nature des esprits dans les cosmologies autochtones, 2007)

Kate and Anna McGarrigle: Songs and Stories - Lanken, Dane (Penumbra Press, 2007)

Les jeunes et la marginalisation à Montréal : la culture hip-hop francophone et les enjeux de l’intégration - LeBlanc, Marie Nathalie; Boudreault-Fournier, Alexandrine; Djerrahian, Gabriella (Diversité urbaine, 2007)
La culture hip-hop est apparue au Québec dans les années 1980. À Montréal en particulier, différents groupes ethniques et culturels se sont approprié le rap et l’emploient comme un mode d’expression de leurs réalités quotidiennes, le transformant ainsi en un référent identitaire. Nous proposons que la culture hip-hop offre un espace d’intégration et d’adaptation à des jeunes de diverses origines ethniques et culturelles, souvent marginalisés au sein de la culture québécoise dominante. Loin d’être un instrument de résistance et de contestation mondialisé, adapté et manipulé sur le plan local, le rap québécois nous apparaît comme une stratégie d’intégration mise en place par de jeunes artistes qui visent ainsi à rendre leur culture davantage visible au sein de la société majoritaire, tant au niveau public que médiatique.
Keywords: culture populaire; hip hop; hip-hop; integration; intégration; jeunes; media; média; popular culture; youth

La rencontre des musiques du Moyen-Orient et de l'Occident : esthétisme, composition et analyse - Makdissi-Warren, Katia (Université de Montréal, 2007)
The object of this dissertation is the meeting of Middle-Eastern and Western music. The dissertation includes an essay and seven original compositions (scores and recordings). The text begins with the exposition of the basics of Middle-Eastern music required to understand my artistic approach. The 'taqasim', a major musical form in the Middle-East and a source of inspiration for my work is presented in more detail. The second chapter deals with the philosophy of aesthetics involved in the intermixing of musical cultures. Concerns about the coherence of commingled languages are exposed. The concepts of intermixing, cultural identity and coherence of a work are submitted for discussion. For a given work, does the notion of coherence retain its essence from one person to the next according to culture and social context? This questioning is directly linked to the creation and generation of the processes of development for the musical material in my compositions. Throughout the chapter, I position my approach in relation to the thinking of authors such as Adorno, but also relative to personal experiences. In chapter 3 I describe the writing processes I have developped in order to create a sound fabric wherein Middle-Eastern music meets that of the West. My work defines processes for treating parameters in order to draw together elements of both Eastern and Western musical expressions into a distinctive language <f> <fr><nu>.</nu><de>7</de></fr></f> the key to this is grasping how one musical element influences another. Using analysis as a starting point for the comparison of musical parameters in each of the languages, I have elaborated new commingling (intermixing) techniques. This chapter is therefore devoted to the cross-relational writing techniques that have been evolved to adequately support my artistic approach. The final chapters of this dissertation feature the detailed analyses of three of my compositions: 'Jet Stream, Algorythme and PLB'. Each piece's form, sections and sub-sections are presented followed by the analysis of its basic musical material and development.

Récit d’une Beauceronne en Irlande ou la découverte de ‘l’irlandicité’ des Québécois - Matte, Isabelle (Cap-aux-Diamants, 2007)

A Queer Protocol of Homage: Chambres de Ténèbres/Tombeau de Claude Vivier By Marko Nikodijević - Novak, Jelena (International Journal of Music New Sound, 2007)
The music of Canadian composer Claude Vivier (1948-1983) was used as a fractalized material for the creation of the composition Chambres de ténèbres/tombeau de Claude Vivier (2005) by Marko Nikodijević. Vivier’s opus and his marginal queer acting were the pillars of Nikodijević’s meticulous reading/deconstructing of Vivier’s world through his own artistic dilemmas.

Jeanne Maubourg (1875-1953) : l’apprentissage de la modernité théâtrale - Robert, Lucie (Jeu. Revue de théâtre, 2007)
Un article de la revue Jeu, diffusée par la plateforme Érudit.

Hybrid Identities in Quebec Hip-Hop: Language, Territory, and Ethnicity in the Mix - Sarkar, Mela; Allen, Dawn (Journal of Language, Identity & Education, 2007)
Montreal is the metropolitan hub of the province of Quebec, a French-speaking island in officially bilingual, but de facto majority English-speaking, Canada. The current youth generation represents a variety of ethnolinguistic backgrounds—French and English Canadian, but also many different immigrant-origin groups, including large Haitian and Hispanophone populations. Young adults and adolescents share French as a common language through schooling. In Quebec, hip-hop, a privileged literary–artistic and political medium for this generation, not only reflects its multilingual, multiethnic base, but also constitutes an active and dynamic site for the development of an oppositional community that encourages the formation of new, hybrid identities for youth. The authors draw on interviews with rappers of Haitian, Dominican, and African origin, and analysis of lyrics by these MCs, to highlight ways in which the discourses of “conscious” Quebec hip-hop promotes particular ideologies and identities in a context of migration/resettlement and globalization of youth culture.
Publisher: Routledge _eprint: https://doi.org/10.1080/15348450701341253
Keywords: Quebec; hip-hop; identity; multilingual; rap; youth culture

Les voix des auteures-compositeures et interprètes populaires : une toile arc-en-ciel posée entre elles et nous - Tremblay, Danielle (Québec français, 2007)
Un article de la revue Québec français, diffusée par la plateforme Érudit.
Publisher: Les Publications Québec français

Essential Song: Three Decades of Northern Cree Music - Whidden, Lynn (Wilfrid Laurier University Press, 2007)
A pack that contains a book and a CD. The book presents an outline of Cree musical history and a contribution to ethnomusicology, social history, and Aboriginal studies. The CD contains over 80 Cree hunting songs.

Rufus Wainwright. Interview by Paul Zollo - Zollo, Paul (Song: the World’s Best Songwriters on Creating the Music that Moves Us, 2007)
Song is an enthralling compilation of songwriting wisdom from 100 of the biggest names in music. From country to rock to folk to alternative, this genre-spanning collection of interviews captures the anecdotes, history, and wisdom of the best songwriters around - in their words. An entertaining read as well as an indispensable guide to the art and craft of songwriting, Song is a must-have resource for the aspiring, amateur, or professional musician. Inside, you'll find entertaining and enlightening interviews from great songwriters such as Smokey Robinson, Willie Nelson, Jewel, Kenny Chesney, Cat Stevens, Jack Johnson, Sheryl Crow, John Legend, John Mellencamp, Ray Charles, Clint Black, Rob Thomas, Dolly Parton, Rufus Wainwright, Bob McDill, Lyle Lovett, Keith Urban, Beck, M. Ward, Lou Reed, Roger Miller, Grant-Lee Phillips, and John Denver.

Erika Mann et Pauline Julien : voix parallèles dans l'exil et l'engagement - Augustin, Myriam (Université McGill, 2006)

Musiques d’ici et d’ailleurs ; Montréal au « son » du monde - Beauvais, Annick (Université de Montréal, 2006)

Espace musical, espace érotique - Chamberland, Roger (Groove. Enquête sur les phénomènes musicaux contemporains, 2006)

L’opéra pour enfants ou la quête d’identité : commentaire critique sur L’arche, d’Isabelle Panneton et Anne Hébert - Champagne, Éric (Circuit : musiques contemporaines, 2006)
Avant de rendre compte de l’opéra pour enfants L’arche (musique d’Isabelle Panneton, livret d’Anne Hébert), créé le 25 novembre 2004 par le Nouvel Ensemble Moderne et l’Atelier lyrique de l’Opéra de Montréal, cet article replace l’oeuvre dans un contexte plus large en esquissant un portrait de l’opéra pour enfants au XXe siècle. À travers diverses incarnations (parmi lesquelles l’opéra interprété par et pour des enfants), le genre est caractérisé par une durée limitée à moins d’une heure et un sujet spécifiquement destiné aux enfants, rendu aussi compréhensible que possible par un livret écrit dans la langue de son auditoire et porté par une musique claire et simple. Si ces caractéristiques ne vont pas sans soulever quelques questions, l’auteur estime qu’ils trouvent dans L’arche une illustration tout à fait réussie.
Publisher: Les Presses de l'Université de Montréal

Un entretien avec Diane Labrosse - Cornell, Andrea-Jane (Intersections: Canadian Journal of Music / Intersections : revue canadienne de musique, 2006)
This interview with Diane Labrosse was conducted in December 2004 in the offices of Production SuperMusique within the framework of Dr. Andra McCartney's In and Out Of the Sound Studio project. Andrea Jane Cornell asked Labrosse about the experiences that brought her to choose sound as a medium for her artistic expression, and the methods that she employs to create sound.

Marc-Antoine Charpentier chez les Abénaquis ou la petite histoire d’une Chanson des Bergers au Nouveau-Monde - Dubois, Paul-André (Études d'histoire religieuse, 2006)

L'écho du féminisme dans les chansons de Jean-Pierre Ferland et de Jim Corcoran - Dubois, Vicky (Université de Montréal, 2006)

Thérèse Dion. La vie est un beau voyage - Germain, Georges-Hébert (Éditions Libre Expression, 2006)

Mais il n'a rien compris à ce que j'ai dit, celui-là! La chanson L'incompétence de Lynda Lemay - Gouvernec, Ludovic (FSU Frz, 2006)
La chanson « L'incompétence » de Lynda Lemay aborde avec humour les situations de communication gênantes du quotidien dans lesquelles on peut se retrouver, par exemple en faisant ses courses ou en allant au restaurant. Il est donc adapté - dans les cours de français à partir de la quatrième année - pour travailler des thèmes tels que les relations interpersonnelles, les différents registres de langue et la politesse. De plus, des aspects régionaux peuvent être abordés, l'accent étant mis sur les particularités géographiques et culturelles du Québec ainsi que sur les particularités dialectales du français qui y est parlé en raison des origines du chanteur. Après un examen détaillé du contenu de la chanson, divers exercices tels que l'invention d'un dialogue, un jeu de rôle et l'écriture d'un couplet de chanson sont proposés. Il y a des feuilles de travail et (à la page 95 du livret) le texte de la chanson, qui est également disponible sous forme de texte audio sur un CD qui peut être acheté avec le livret.
Keywords: Pas de lien web

Le son généreux [pour une hyper-écoute] - Laplante, Chantale (Intersections: Canadian Journal of Music / Intersections : revue canadienne de musique, 2006)
L’article que l’artiste propose au lecteur relate le processus de transformation de sa pratique artistique durant une période particulière. L’artiste nous entretient de la transformation dans sa manière de composer la musique et de travailler avec le son. Elle développe sa réflexion autour de deux notions principales : l’hyper écoute qui favorise une approche intuitive, le son devenant la source première d’information à être transmué par la sensibilité de l’artiste, et l’espace-surface issu d’un temps musical non linéaire inscrit dans la durée. Tout au long de l’article, le lecteur prendra connaissance d’un contexte de travail précis qui a favorisé l’émergence d’un questionnement sur le processus de composition musicale et la relation avec le matériau en jeu, le son.

Alanis Obomsawin: The Vision of a Native Filmmaker - Lewis, Randolph (University of Nebraska Press, 2006)
In more than twenty powerful films, Abenaki filmmaker Alanis Obomsawin has waged a brilliant battle against the ignorance and stereotypes that Native Americans have long endured in cinema and television. In this book, the first devoted to any Native filmmaker, Obomsawin receives her due as the central figure in the development of indigenous media in North America.

The Importance of Community-Based Media for Building and Sustaining Lesbian Subcultures: The Role of Montréal’s Dykes on Mykes Radio Show - MacPhee, Marie-Claire; Hogan, Mél (Global Media Journal, 2006)
This paper was originally written for and presented at the Lesbian Lives XIII: Historicizing the Lesbian Conference in Dublin, Ireland in February 2006. The essay considers the history of Dykes on Mykes, a groundbreaking, lesbian and queer community-based radio program in Montréal, Canada. The authors, who are the show’s current hosts and technicians, collected data by examining the show’s archives and conducting individual and focus group interviews with Dykes on Mykes’ past and present hosts. These data reveal that changes in Dykes on Mykes’ programming and foci correlate closely with contemporary cultural and social developments among lesbian communities in Montréal.

The Role of Montréal’s Dykes on Mykes Radio Show - MacPhee, Marie-Claire; Hogan, Mél (Canadian Woman Studies, 2006)
Les auteures examinent le rôle historique, socio-politique de la programmation radiophonique montréalaise des années ‘20 alors que Dykes on Mykes, une émission qui a forgé et soutenu la sous-culture des lesbiennes et queers de la communauté anglophone de Montréal. Elles assurent que l’émission Dykes on Mykes a initié un courant alternatif à l’ordre établi en travaillant directement avec la communauté lesbienne et queer de Montréal et en contribuant à leur représentation positive dans les médias.

Gender, Genre and Electroacoustic Soundmaking Practices - McCartney, Andra (Intersections: Canadian Journal of Music / Intersections : revue canadienne de musique, 2006)
This article is an exploration of how genres and practices of electroacoustic soundmaking are gendered, examining processes of gendering in language used in the early dichotomous categorization between musique concrète and elektronische Musik, then thinking about related arguments concerning abstraction, context, and compositional control in the writings of electroacoustic soundmakers including Pierre Schaeffer, Pierre Boulez, Daphne Oram, Pauline Oliveros, and several participants of the In and Out of the Sound Studio project. Analysis of their practices and ideas suggests different ways of conceptualising electroacoustic genres, their related practices, and roles of contemporary electroacoustic soundmakers (composers, artists, producers, mixers, audiences...), by examining the potentials of the concepts of empathetic knowledge and ecological thinking advanced by feminist epistemologist Lorraine Code.

In and Out of the Sound Studio: Introduction - McCartney, Andra; Waterman, Ellen (Intersections: Canadian Journal of Music / Intersections : revue canadienne de musique, 2006)
Dans l’introduction à ce numéro spécial d’Intersections, Andra McCartney et Ellen Waterman présentent les Dedans et Dehors du Studio, un projet de recherche ethnographique inter-universitaire soutenu financièrement par le CRSH du Canada de 2001 à 2005. L’équipe de recherche a étudié les idées et pratiques des artisans sonores canadiens, se penchant particulièrement sur le sujet de la relative invisibilité et inaudibilité des femmes, réfléchissant aux différentes manières dont les technologies et pratiques sonores peuvent être orientées sexuellement. Dans leurs essais, les auteures discutent des relations trouvées entre les termes genre, son et technologie, du point de vue aussi bien terminologique, qu’esthétique, du mentorat, ou encore méthodologique et théorique. Les contributions de McCartney, Diamond, Laplante, Labrosse, Marsh et Bosma sont ici discutées.

Snobs and quétaines: Prestige and Boundaries in Popular Music in Quebec - Ollivier, Michèle (Popular Music, 2006)
This paper is a study of prestige and boundaries in Quebec French-language popular music. Based on interviews with artists, producers and critics conducted in the early 1990s, I argue that popular music in Quebec at that time remained divided along a symbolic boundary established in the 1960s between a highly prestigious group of songwriters/rock artists, who wrote and sang their own material, and a less prestigious group of interpreters/artistes populaires, who sang light pop songs or songs written by others. As predicted by Bourdieu, I show that artists in the most prestigious category were associated with privileged social groups and gained material and symbolic advantages from their prestige. They are more likely to receive honorific awards, to be invited to perform at special cultural events, to see their work recognised as 'important', and to persist over time. In opposition to Bourdieu, however, I argue that in the context of emerging nationalism, their songs were also perceived as providing collective benefits over and beyond class and gender divisions.

Les représentations de la féminité et de la masculinité à travers le thème des rapports amoureux dans la chanson populaire francophone consommée au Québec, 1960-1990 - Ouellette, Myrthô (Université de Sherbrooke, 2006)

Portrait d’Ana Sokolovic - Picard, Isabelle (Circuit : musiques contemporaines, 2006)
An article from Circuit, on Érudit.
Publisher: Les Presses de l'Université de Montréal

Œuvres principales d’Ana Sokolovic - Picard, Isabelle (Circuit : musiques contemporaines, 2006)
An article from Circuit, on Érudit.
Publisher: Les Presses de l'Université de Montréal

Au delà du sexe et de la technologie : les tendances du genre - Piché, Claire (eContact!, 2006)

“La vraie langue française [n'] existe plus”: français parlé et pratiques multilingues comme stratégies identitaires dans le rap montréalais - Sarkar, Mela (Grenzgänge, 2006)

"Pour connecter avec le peeps": Québéquicité and the Quebec Hip-Hop Community - Sarkar, Mela; Low, Bronwen; Winer, Lise (Identity and Second Language Learning: Culture, Inquiry, and Dialogic Activity in Educational Contexts, 2006)

Multilingual Codeswitching in Quebec Rap: Poetry, Pragmatics and Performativity - Sarkar, Mela; Winer, Lise (International Journal of Multilingualism, 2006)

Les préférences musicales des lectrices du Bulletin des agriculteurs, 1939-1955 - Savoie, Chantal (Communication. Information médias théories pratiques, 2006)
Au cours des vingt dernières années, plusieurs travaux s’intéressant à la chanson québécoise dans ses dimensions historiques ont contribué à renouveler notre perception du passé musical populaire québécois. Des ouvrages de référence, comme le Dictionnaire de la musique populaire au Québec (Thérien et D’Amours, 1992) et la numérisation de l’Encyclopédie de la musique au Canada (Kalmann, Potvin et Winters, 1993), sont venus baliser le domaine des études sur la chanson en rendant accessibles de ...
ISBN: 9782895182542 Number: Vol. 25/1 Publisher: Editions Nota bene
Keywords: chanson; femmes; goût musicaux; magazine

Michel Louvain : héritage, circonstances et convergences - Savoie, Chantal (Groove. Enquête sur les phénomènes musicaux contemporains, 2006)
En juin 2003 décédait tragiquement Roger Chamberland. Professeur titulaire à l’Université Laval, directeur du Département des littératures, cet homme du présent multipliait compétences et engagements dans une urgence aussi fervente que généreuse. Ses intérêts de recherche portaient sur des objets à la croisée des mouvements littéraires, artistiques et technologiques de son temps : formes variées de la culture populaire, expressions musicales contemporaines, esthétiques nouvelles étaient pour lui autant de champs d’investigation dignes de l’attention du chercheur d’aujourd’hui. Codirigé par Patrick Roy et Serge Lacasse, le présent ouvrage porte trace de cette enquête sur notre post-modernité. Il rend hommage au professeur, au chercheur qu’était Roger Chamberland. Ceux qui ont côtoyé cet homme d’exception, ses étudiants, ses collègues, ses amis, savent qu’il était infiniment plus que cela.

La alegría de hacer música contemporánea: entrevista con Lorraine Vaillancourt [La joie de faire de la musique contemporaine : entretien avec Lorraine Vaillancourt] - Stan, Luana (Doce notas preliminares, 2006)
Publisher: Doce notas Section: Doce notas preliminares: revista de música y arte

Texte et musique dans le Journal d'Henriette Dessaulles, une disposition en abîme de type fractal - Vadean, Mirella (Université Concordia, 2006)
This master thesis aims to demonstrate that the personal diary, as a structure where several systems of signs can converge and seen from the point of view of evocation, can contribute to the structuring of a new hermeneutic figuration. For the purpose of this thesis, we analyze the limit of the literary fragment using the philosophical point of view of the Whole as a possible dynamic of restitution. Beyond this limit, we explore the emptiness that lays ahead, in the hope of, once again, recreating the Whole. References made to music (opera) throughout the diary, will be studied as a never ending "mise en abîme". We will use Lucien Dällenbach's methodology to detect and decode excerpts of Giuseppe Verdi's Trouvere and Richard Wagner's Rienzi within the diary. Throughout this thesis, we will suggest that textual and musical resonance between the word, the utterance and the code, allow for the creation of a system whose components are perpetually moving. For a better description of this system and in order to make the mechanism of sequences and resonance more clearly visible, we propose to consider this system as a fractal. This will enable us to constitute a system based on Henriette Dessaulles' diary (a "Dessaullien System"), a system erected using the science of fractals. The parameter of this system is the literary fragment, the unknown factor is the music and the interface is philosophy

Entretien avec Joane Hétu - Arroyas, Frédérique (Critical Studies in Improvisation / Études critiques en improvisation, 2005)

Innu Nikamu : expression musicale populaire, affirmation identitaire et guérison sociale en milieu innu contemporain - Audet, Véronique (Université Laval, 2005)

Les chansons et musiques populaires innues : contexte, signification et pouvoir dans les expériences sociales de jeunes Innus - Audet, Véronique (Recherches amérindiennes au Québec, 2005)
This article presents popular Innu musical expressions as voices that serve to reaffirm Innu identity and revitalize Innu society and culture. These songs in the Innu language are inspired by various musical trends such as country, rock, folk and pop, as well as Innu, Pan-Indian, Christian and Quebecois traditions. They have been created, practiced and renewed since the second half of the twentieth century, accompanying the often radical events, movements and transformations that have marked Innu social and cultural life. Contemporary Innu youth, like their predecessors, are the primary conveyers of this expressive movement which they use to participate in the daily life of their communities, and reaffirm their identity, their experiences and their preoccupations, thus contributing to the revitalization of their world and the Innu “way of being”. We present some of the singers, groups and songs that are representative of contemporary Innu musical expression and who have had a significant impact within their society. This provides a sensitive understanding of the context, the significance and the power of these expressions.
Publisher: Recherches amérindiennes au Québec

Y a-t-il des créatrices en musique au Québec ? - Carignan, Nicole; Leblanc (FAMEQ à la une, 2005)

Rufus Wainwright - De Curtis, Anthony (In Other Words: Artists Talk About Life and Work, 2005)

Small Heroes: Rap Music and Selective Belongings of Young Haitian Immigrants in Montreal - Drotbohm, Heike (Childhood and Migration: From Experience to Agency, 2005)

Constructions of Identity in the Life Stories of Emma Albani and Glenn Gould - Elliott, Robin (Journal of Canadian Studies, 2005)
Biographical accounts of musicians have enjoyed widespread popularity since the late-Victorian era. Literary theory has recently held biography to be a literary construct, rather than a factual enterprise. Biographies and music are both governed by narrative structures and help to create a sense of individual and collective/national identity. Biographical accounts of two Canadian musicians—Emma Albani and Glenn Gould—are examined. Both musicians are Canadian national icons, but there are several problematic issues in their life stories: Albani’s elitism, class consciousness, and ambiguous relationship to Canada, and Gould’s eccentricity and uncertain sexual identity. The article examines how these issues have been handled in various auto/biographical accounts of the two musicians.
Publisher: University of Toronto Press

Chantal Dumas: a passion for listening and for studio art - Fenner, Victoria (Musicworks, 2005)

The Loudspeaker as Instrument: the soundworks of Nancy Tobin - Friz, Ann (Musicworks, 2005)

Présences musicales cubaines au Québec : analyse ethnomusicologique d’approches individuelle - Gauthier Mercier, Catherine (Université de Montréal, 2005)

Violet Balestreri Archer (1913-2000) - Hartig, Linda (Music Reference Services Quarterly, 2005)
Violet Archer, one of Canada's well-known composers, passed away in 2000. This article is meant to add biographical information not previously available and to bring closure to her works list. Selected bibliographical citations are also included.
Keywords: Canadian composers; Violet Balestreri Archer

Radical Queers: A Pop Culture Assessment of Montréal's Anti-Capitalist Ass Pirates, the Panthères roses, and Lesbians on Ecstasy - Hogan, Mélanie (Canadian Woman Studies, 2005)
Cet article nous explique comment des artistes montréalaises queer radicales, Anti-Capitalists Ass Pirates, les Panthères roses et Lesbians on Ecstasy, ont transformé la sphère publique en intégrant politique et célébrations dans leurs importants messages à la population.

Musique, tradition et parcours identitaire de jeunes Atikamekw. La pratique du tewehikan dans un processus de convocation culturelle - Jérôme, Laurent (Recherches amérindiennes au Québec, 2005)
À travers l’expérience d’un groupe de joueurs de tambour de la communauté atikamekw de Wemotaci, cet article montre comment de jeunes autochtones négocient le changement dans un con- texte social et culturel en pleine mutation. La pratique contemporaine du tambour est révélatrice de transformations et de persistances culturelles véhiculées par la jeunesse : valorisé dans de nombreuses communautés, le tambour s’inscrit dans un processus plus large de convocation culturelle qui a pris naissance dans la communauté de Wemotaci dans les années 80. À côté de la responsabilité culturelle que cette pratique implique, les membres du groupe revendiquent aujourd’hui une responsabilité professionnelle intervenant tout autant dans leur expérience et dans leur représentation de ce que signifie être jeune et atikamekw aujourd’hui. Les dispositions musicales, les lois du marché, le respect des contrats, les négociations et les conciliations liées à la professionnalisation se positionnent donc aux côtés des savoirs locaux persistant dans le contexte contemporain.
Publisher: Recherches amérindiennes au Québec

La mémoire historique de la communauté noire dans la société québécoise : l'expérience d'un atelier de musique organisé à Québec en 2004 - Lanthier, Pierre (Université Laval, 2005)

Répertoire musiques du monde à Montréal - Laurent, Sophie; Bélanger, Thomas (Conseil des arts de Montréal, 2005)

La contribution des femmes à l’histoire musicale et les compositrices d’aujourd’hui au Québec - Lefebvre, Marie-Thérèse (L'accès des femmes à l'expression musicale. Apprentissage, création, interprétation. Les musiciennes dans la société contemporaine, 2005)

C'était du spectacle! L'histoire des artistes transsexuelles à Montréal, 1955-1985 - Namaste, Viviane (McGill-Queen's University Press, 2005)
Le quartier chaud de Montréal a fait couler beaucoup d'encre, mais sa culture de cabaret n'a jamais été examinée dans la perspective des artistes transsexuelles et travesties qui l'ont rendu si populaire. Par le biais des récits provenant des danseuses elles-mêmes, Viviane Namaste peint un portrait honnête de quatorze transsexuelles - danseuses, chanteuses, magiciennes ou effeuilleuses - et jette un regard dans les coulisses du monde dans lequel vivent et travaillent ces hommes devenus femmes. Les années soixante et soixante-dix ont été des décennies de changement social au Québec. C'était du spectacle! raconte l'histoire de la première génération de transsexuelles ayant subi une chirurgie d'inversion de sexe. Namaste examine les conditions de travail dans les cabarets, la prostitution, les abus de pouvoir des policiers à l'égard des transsexuelles, le rôle du crime organisé dans la vie nocturne de la ville et l'accès aux soins de la santé. C'était du spectacle! offre un rare survol de la culture urbaine de Montréal, présenté dans ses propres mots par l'une de ses plus importantes communautés artistiques.

L’art de chanter… au féminin : de la prise de paroles au jeu de références postmodernes - Oberhuber, Andrea (L’accès des femmes à l’expression musicale. Apprentissage, création, interprétation : les musiciennes dans la cité, 2005)

L'instrument de musique amérindien dans l'Est de l'Amérique du Nord : facture, usages et changements, des contacts à 1800 - Plante, Jean-François (Material Culture Review, 2005)
The problematic issue of the relations between Europeans and North American Aboriginal peoples has been widely studied during the twentieth century, but the European influence on native musical practices has not yet been explored as a general rule, nor in particular with regard to how their instruments were created and used. The voice, that manifestation of object-body-person, and its musical usage in song is without doubt the best documented musical fact in the narratives of the voyages of the civil and military officers of the New World. The historical ethnological study presented here is an initial analysis of ancient texts written between 1524 and 1800, whose purpose is to identify the changes that may have appeared in the instrumental and vocal cultures, which were closely linked to the musical art of the various Native peoples. A comparison of the collected data reveals a variety of trends in the development of native practices. In addition to these results, the work on native musical issues conducted by researchers since the end of the nineteenth century provides confirmation that in some cases acculturation and its symptoms became evident only in the nineteenth and twentieth centuries. Résumé La problématique des relations entre les Européens et les peuples autochtones d’Amérique du Nord a fait l’objet de nombreuses études au XXe siècle, mais l’influence des Européens sur les pratiques musicales amérindiennes n’a pas encore été mesurée de façon générale ni particulièrement en ce qui a trait à la fabrication et l’usage des instruments. La voix, manifestation de l’objet-corps humain, et son utilisation musicale, le chant, constituent sans doute la portion du fait musical la mieux documentée dans les récits de voyages et la corres pondance des officiers civils et militaires du Nouveau Monde. L’étude d’ethnologie historique présentée ici jette un premier regard sur des textes anciens écrits entre 1524 et 1800, afin de cerner les changements qui ont pu apparaître au sein des cultures instrumentale et vocale, très liées dans l’art musical des différents peuples autochtones. La confrontation des données recueillies permet de dégager des tendances dans l’évolution des pratiques. À ces résultats s’ajoutent les travaux sur les questions musicales amérindiennes menés par des chercheurs depuis la fin du XIX e siècle, qui viennent confirmer dans certains cas que l’inculturation et ses symptômes se sont manifestés seulement aux XIXe et XXe siècles.

Multilingual code-switching in Montreal Hip-Hop: Mayhem meets method, or, ‘Tout moune qui talk trash kiss mon black ass du nord’ - Sarkar, Mela; Winer, Lise; Sarkar, Kobir (ISB4: Proceedings of the 4th International Symposium on Bilingualism, 2005)

La réception féminine de la chanson sentimentale populaire - Savoie, Chantal (Le féminin, le masculin et la musique populaire d'aujourd'hui. Actes de la journée du 4 mars 2003., 2005)

Briser le silence. Nathalie - Vastel, Michel (Éditions Libre Expression, 2005)
Un livre attendu, celui de Nathalie Simard, une jeune femme courageuse qui est devenue le symbole de toutes les femmes abusées, dont Michel Vastel signera l’histoire. Un témoignage touchant écrit par un journaliste d’envergure qui racontera l’histoire d’une femme, mais aussi celle de sa famille et de son entourage tout au long des années où elle a travaillé dans le monde du spectacle. Il y sera question de son enfance, son adolescence, jusqu’au dénouement médiatique de son histoire qui a éclaté dans les journaux en 2004 et en 2005.

Le destin des pratiques vocales autochtones entre protoethnographie, modernité et antimodernité - de Surmont, Jean-Nicolas (MUSICultures, 2004)

La singulière pluralité de Marilyn Lerner - Denis, Dominique (Liaison, 2004)
Publisher: Les Éditions l'Interligne

Chant et mission en Nouvelle-France. Espace de rencontre des cultures - Dubois, Paul-André (Université Laval, 2004)

Diane Leboeuf: from mixing boards to museums - Gasior, Lisa; McCartney, Andra (Musicworks, 2004)

The bilingual ethnic media production: in the case of a Korean English radio program, VOKO - Hong, Sung-Nam (Université du Québec à Montréal, 2004)

Les Noirs et le jazz au Québec - Lelièvre, Denys (Cap-aux-Diamants : la revue d'histoire du Québec, 2004)
An article from Cap-aux-Diamants, on Érudit.
Publisher: Les Éditions Cap-aux-Diamants inc.

The Memoirs of a Partisan from Salonika - Melammed, Renee Levine (Nashim: A Journal of Jewish Women's Studies & Gender Issues, 2004)

Geneviève Gilardeau : le violon baroque et Jean-Marie Leclair - Melançon, Johanne (Liaison, 2004)
Publisher: Les Éditions l'Interligne

Beyond Leisure Studies: A Labour History of Male to Female Transsexual and Transvestite Artists in Montréal, 1955-1985 - Namaste, Viviane (Atlantis, 2004)

Étude sociologique de la musique actuelle du Québec : le cas des Productions Supermusique et du Festival International de Musique Actuelle de Victoriaville - Robineau, Anne (Université de Montréal, 2004)
Cette thèse a pour but l’étude sociologique de la musique actuelle au Québec. La musique actuelle est une pratique de création créée en dehors des institutions académiques et des centres de recherche. La professionnalisation de ce milieu artistique est décrite et analysée dans une perspective sociologique en prenant les cas des Productions Supermusique et du label DAME ainsi que du festival International de Musique Actuelle de Victoriaville. L’objectif de cette thèse est d’acquérir une connaissance sur la façon dont s’est développé ce milieu musical des années 70 à aujourd’hui.

Musique, femme et création musicale - Robineau, Anne (Dire, 2004)

De la comédie musicale au rapprochement interculturel : l'exemple d'une école secondaire de Montréal - Talmon, Suzanne (Médiations et francophonie interculturelle, 2004)

Signé Louise - Forestier, Louise (Éditions du Boréal, 2003)

Les Amérindiens, les missionnaires et la musique européenne - Gallat-Morin, Élizabeth; Pinson, Jean-Pierre (La vie musicale en Nouvelle-France, 2003)

Les communautés féminines - Gallat-Morin, Élizabeth; Pinson, Jean-Pierre (La vie musicale en Nouvelle-France, 2003)

Analyse sociopoétique de la réception mitigée de deux œuvres de Clémence Desrochers : Le monde aime mieux... et Mon dernier show - Gauthier, Mélissa (Université Laval, 2003)

Violet Archer: Eine sozio-kulturelle Einordnung der Musik der kanadischen Komponistin unter besonderer Ber cksichtigung der Orchesterwerke [Violet Archer : une classification socioculturelle de la musique de la compositrice canadienne, avec une attention particulière à ses œuvres orchestrales] - Glathe, Kerstin (Université de la Ruhr à Bochum, 2003)
Keywords: Pas de lien web

Oralité et culture vocale inuit - Le Goff, Philippe (Revue DEMéter, 2003)

Creating and Contributing: The Expansive Spirit of Marcelle Deschênes - Mountain, Rosemary (Musicworks, 2003)

Maya Badian: Her Life and Her Music, A Privilege to Soar - Popovici, Fred (Editura Muzicalǎ, 2003)

"Gnaah" and the Trout Song - Whidden, Lynn (Proceedings of Eighth Workshop on the Structure and Constituency of Languages of America, 2003)

Maryvonne Kendergi. La musique en partage - Bail, Louise (Éditions Hurtubise, 2002)

Les pratiques musicales autochtones : une confluence de perspectives - Beaudry, Nicole (Traité de la culture, 2002)

The Sound System: Contributions to Jamaican Music and the Montreal Dancehall Scene - Constantinides, John (Université de Montréal, 2002)

Native American Contemporary Music: The Women - Diamond, Beverley (The World of Music, 2002)
This article explores issues raised in interviews with traditional and contemporary Native American musicians and recording artists of the 1990s. It exemplifies how they view their roles vis à vis traditional gender structures and community obligations, how they draw upon different media to communicate their messages, and how they use their work as a form of social action. Their narratives reveal a wide variety of strategies by which they negotiate the double consciousness and multiple relationships of their lives, balancing historically rooted values and traditions with modern ones. I attempt to develop a feminist interpretation that is respectful of the cultural values these women expressed in their conversations with me.
Publisher: [Florian Noetzel GmbH Verlag, VWB - Verlag für Wissenschaft und Bildung, Schott Music GmbH & Co. KG, Bärenreiter]

Considering Complexity in Canadian Civil Society: A Case Study of Studio XX - Gerlach, Neil; Hamilton, Sheryl (Revista Mexicana de Estudios Canadienses, 2002)

Virtually Civil: Studio XX, Feminist Voices, and Digital Technology in Canadian Civil Society - Gerlach, Neil; Hamilton, Sheryl N. (Civic Discourse and Cultural Politics in Canada, 2002)

Global Pop On The Move: The Fame of Céline Dion Within, Outside and Across Québec - Grenier, Line (Journal of Australian Canadian Studies, 2002)

L'homme qui fait chanter les femmes : Stéphane Venne - Joubert, Lucie (Lectures du genre, 2002)

Ma vie, je t'aime - Martel, Renée; Chapados, Dominique (Éditions Publistar, 2002)

New Games in the Digital Playground: Women Composers Learning and Teaching Electroacoustic Music - McCartney, Andra (Feminism & Psychology, 2002)
Publisher: SAGE Publications Ltd

Les cahiers noirs de Lynda Lemay - Paquette, Claude (Éditions Contreforts, 2002)

Chansons d'amour et roman sentimental populaire : quand l'air ne fait pas la chanson - Savoie, Chantal (Littérature populaire et culture médiatique, 2002)

Musical Life in Montreal's Judeo-Spanish Community - Cohen, Judith R. (Garland Encyclopedia of World Music, tome III : United States and Canada, 2001)

Des mondes religieux parallèles, un espace commun? Amérindiens et musique vocale européenne sous le Régime français - Dubois, Paul-André (Études d'histoire religieuse, 2001)
This article is devoted to the question of French religious music used by Christian Indians of New France during the 17th and 18th centuries. More particularly, it examines the surprising success of this religious and artistic practice in the post-contact North American world. It appears that cultural more than geopolitical or socioeconomic factors can explain the rapid adoption of European religious songs by Indians. In my opinion, only a better understanding of the role traditionally held by singing in the Indian culture could help us identify the cultural basis on which such a success is based. From there, it becomes possible to sustain a larger reflection about Catholicism's influence among Indians during the historical period.

Québec, vingtième siècle : La création musicale, une affaire de femmes ? - Galaise, Sophie (Musicanada 2000: A Celebration of Canadian Composers/Un hommage aux compositeurs canadiens, 2001)

La semaine annuelle de musique de Montréal sous les auspices du Delphic Study Club, 1923–1937 - Lefebvre, Marie-Thérèse (Canadian University Music Review / Revue de musique des universités canadiennes, 2001)
This study begins with an examination of the background against which was founded the annual Music-Week in Montreal (1923–1937), then presents an analysis of its system of operation, inspired by the American model created in 1920 by Charles Milton Tremaine. Information on the staff of the association, its sponsors, financial grants, concert venues, performers, repertory, and lecturers is discussed; the main points of the press reviews of the events are extracted. The anglophone-francophone cultural dualism with regard to the conception of music and of its role in education emerges clearly in the conclusion, which also highlights the active role of women in the running of organizations destined to spread music in Quebec.
Publisher: Canadian University Music Society / Société de musique des universités canadiennes

Chansons de cours-nu-pieds - Miville-Deschênes, Monique (Éditions Triptyque, 2001)

Three moments of love in Leonard Cohen and Bruce Cockburn - Nonnekes, Paul (Black Rose Press, 2001)
"Three Moments of Love is a series of reflections on the work of Leonard Cohen and Bruce Cockburn. These two artists, so different in style and temperament, are brought together in one work in order to compare and examine the way in which they approach the question of love and desire: in their art and in their life."

Popularité, identité et internationalisation : les phénomènes Plamondon et Dion - Oberhuber, Andrea; Poulin, Richard (Les frontières improbables de la chanson, 2001)

L’homosexualité dans la chanson : du bout des lèvres - Perron, Gilles (Québec français, 2001)
Publisher: Les Publications Québec français

Archéologie sonore. Chants amérindiens - Tremblay-Matte, Cécile; Rivard, Sylvain (Éditions Trois, 2001)
Traduit l'importance historique et culturelle des chants traditionnels des dix nations amérindiennes du Québec. Certains d'entre eux sont parvenus à passer outre l'évangélisation et l'influence de la culture européenne. Textes en langue autochtone et transcription des mélodies.

Céline Dion, national unity and the English-language press in Canada - Young, David (Media, Culture & Society, 2001)
The national unity crisis in Canada deepened during the 1990s; it became increasingly likely that the French-speaking province of Quebec might separate from the rest of the country. This article examines how press coverage of Céline Dion, the popular francophone singer from Quebec, has intersected with the national unity debate. After providing some background on the debate and Dion, the article explores the linkages between them in Canada's English-language press. The analysis suggests the existence of a pro-unity frame in coverage of Dion. It also identifies how news stories about Dion have been shaped by binary oppositions, quoting practices and other journalistic techniques. The article concludes by noting some similarities and differences between coverage of political events in the national unity debate (such as referendums or constitutional accords) and coverage of Dion which is associated with the debate.
Keywords: Canadian; Québécois; anglophone; francophone; music; newspapers; politics

Au-delà de la tradition... Rôle et fonction d'un chantre dans la survie d'une église : l'exemple de Iwan Semenovich Kozachok à l'église Sainte-Marie-la-Protectrice-de-Montréal - Berthiaume-Zavada, Claudette (From Chantre to Djak: Cantorial Traditions in Canada, 2000)

Les chants sacrés des Ursulines de Québec à l'époque de Marie Guyart - Courville, Louise (Marie Guyard de l’Incarnation. Un destin transocéanique (Tours, 1599-Québec, 1672), 2000)

Colloquy/Débat: Violet Archer, Jean Coulthard, and Barbara Pentland Remembered - Deaville, James (Canadian University Music Review, 2000)
In a bizarre coincidence, three important Canadian women composers from the same generation recently died within five weeks of each other: Barbara Pentland on 6 February 2000, Violet Archer on 22 February 2000, and Jean Coulthard on 9 March 2000. As a tribute to their lives and work, this colloquy gathers remembrances of them by friends and colleagues, ranging from brief anecdotes to extended memoirs. It is thus a collection of primary documents, which yield many new insights into the lives of our composers, ranging from personal habits to the way they taught composition.
Keywords: Canadian music; Careers; Composers; Composition; Music

Céline Dion. Ma vie, mon rêve - Dion, Céline; Germain, Georges-Hébert (Éditions Robert Laffont, 2000)
Enfant, j'avais deux rêves : devenir une star de la chanson, et connaître le grand amour, pour le meilleur et pour le pire, et pour toujours. J'ai eu beaucoup de chance...La chance de naître dans une famille de musiciens. Mes parents, mes treize frères et sœurs, à la maison tout le monde chantait ou jouait d'un instrument. Alors moi aussi je m'y suis mise très tôt, tout naturellement, et très vite je n'ai plus pensé qu'à ça : chanter. Je n'oublie jamais que c'est grâce à cette enfance heureuse et rieuse que j'ai pu devenir ce que je suis.Et puis la chance de rencontrer René Angélil, mon manager, mon pygmalion dans le monde du show business, mon amant, mon mari – l'homme de ma vie. Ensemble, nous avons fait des rencontres magnifiques, gravi toutes les marches du succès, traversé les plus dures épreuves. Et surtout bâti le grand amour de mes rêves de petite fille.À la veille de vivre notre bonheur le plus cher – la naissance de notre premier enfant –, j'ai eu envie de partager cette belle histoire. "Aujourd'hui, Céline Dion est une immense star. Son autobiographie lui ressemble : sincère et émouvante. Ses fans retrouveront celle qu'ils ont appris à connaître à travers les concerts, et les interviews. Mieux encore, ils découvriront l'intimité de celle qui se livre ici pour raconter ses passions, ses peurs, ses rêves...

Questions de renommée : les mises en mémoire du phénomène Céline Dion - Grenier, Line (Recherches féministes, 2000)
Dans cet article, l'auteure se penche sur le « phénomène Céline Dion » au Québec sous l'angle de la renommée. Au moyen de quelques fragments du discours qui a alimenté ce phénomène à la fin de la dernière décennie, l'auteure esquisse les contours de deux des figures concurrentes de la renommée que ce phénomène met en évidence : le « héros national » et l'« entrepreneur heureux ». Son analyse illustre comment ces figures de la renommée et les mises en mémoire auxquelles elles prêtent visibilité et valeur, lorsqu'elles sont en action dans la conjoncture québécoise contemporaine, opèrent une fusion, sinon une collusion entre la réussite individuelle et collective, entre l'intérêt personnel et national, et, par le fait même, rattachent différents ordres de matériel culturel au présent « passé » de certaines expériences privées, ressources locales et trajectoires publiques.
Publisher: Revue Recherches féministes

Le chant et la musique dans les maisons religieuses de femmes à l'époque de Marie Guyart - Hameline, Jean-Yves (Marie Guyard de l’Incarnation. Un destin transocéanique (Tours, 1599-Québec, 1672), 2000)

L’énigme de la correspondance d’Albani à Heugel - Langlois, Maryse (Les Cahiers de la Société québécoise de recherche en musique, 2000)

Quarante ans au cœur de l'Orchestre symphonique de Montréal - Lyse, Vézina (Varia, 2000)

Des cigales et des fourmis: histoire, actualité et informatisation de la chanson francophone de femmes. Bilan d'un projet de recherche - Oberhuber, Andrea (2000)
BAT – Das Bulletin des Archivs für Textmusikforschung

Les représentations sociales de l'enfant dans la chanson québécoise : l'exemple de Madame Bolduc et de Gilles Vigneault - Thivierge, Jacques (Université du Québec à Trois-Rivières, 2000)
Le présent mémoire porte sur les changements dans les représentations sociales de l'enfant, à l'intérieur du récit de la chanson québécoise. Le corpus de cette partie du discours culturel occupée par la chanson étant très vaste, nous avons limité notre recherche à l'étude des textes des chansons de Madame Bolduc et de Gilles Vigneault. Ces deux auteurs ont en commun le fait d'avoir amorcé leur carrière en des périodes particulièrement significatives de l'évolution de la société québécoise, soit la Crise de 1929 et la Révolution tranquille. Ces deux contextes socioéconomiques très typés nous ont permis d'aborder notre sujet de recherche dans une perspective diachronique. Au départ, nous posons l'hypothèse que l'enfant, représenté dans les chansons de Madame Bolduc, est un être que nous qualifions de subsumé, et que celui qui est représenté dans les chansons de Gilles Vigneault est un être que nous qualifions de sui generis. Pour faire la démonstration de cette hypothèse, notre mémoire se présente en deux grandes parties subdivisées en quatre chapitres. La première partie s'élabore autour des discours social et culturel et autour des rôles familiaux. Le premier chapitre aborde la chanson à travers les concepts de discours social, d'intertextualité , d'acceptabilité et de performance. On y retrouve aussi une mise en contexte des principaux artisans de la chanson québécoise ainsi que des outils de diffusion de cette chanson et ce, pour chacune des deux périodes étudiées. Dans le chapitre 2, en parlant des rôles familiaux et des relations parents/enfants, nous jetons un regard sur la famille et l'enfant au Québec. La deuxième partie de notre ouvrage s'intéresse directement aux chansons de Madame Bolduc et de Gilles Vigneault. Le chapitre 3 nous présente un panorama de la vie de Madame Bolduc ainsi qu'une analyse des représentations sociales de l'enfant et de la famille dans les textes de ses chansons. Cette présentation se répète au chapitre 4 mais , cette fois, relativement à Gilles Vigneault. Notre conclusion traite, dans une perspective diachronique, des changements dans les représentations sociales de l'enfant entre les chansons de Madame Bolduc et celles de Gilles Vigneault. Comme le soulevait notre hypothèse de départ, cette étude nous a permis de conclure que l'enfant, représenté dans les textes des chansons de Madame Bolduc, est un être subsumé et que, à l'opposé , les textes des chansons de Gilles Vigneault nous présentent un enfant sui generis.

Emma Albani - Vachon, Pierre (Éditions Lidec, 2000)
Biographie concise sur la carrière d'une illustre compatriote, Emma Lajeunesse dite Albani. Elle fut la première cantatrice québécoise à connaître une renommée internationale.

La carrière d’Emma Albani au Covent Garden de Londres - Vachon, Pierre (Les Cahiers de la Société québécoise de recherche en musique, 2000)